Efficient synthesis of ethyl levulinate from furfuryl alcohol using several biomass-based carbon - Kongde Li; Qikai Si; Guangyu Wu; Guijing Liu; Wei Jiang; Deyang Zhao; Ting Su; Hongwu Zhang; Zhenglong Yang; Christophe Len; Bin He (Biomass and Bioenergy, 2027)

Environmental dimensionality simplifies biological predictability under complex global change - Peixuan Liu; Bin Huang; Yuan Jia; Junyan Li; Enqi Zhang; Shuming Lin; Zihong Li; Jing Tian; Zijie Wei; Zihan Liu; Mengyao Liang; Runqian Jiang; et al. (Marine Pollution Bulletin, 2026)

Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

RHEBL1 expression is activated by the Oct4-Sox2 complex in oral squamous cell carcinoma - Feng Qiu; Yaqiu Chen; Peibo Li; Zhuo Chen; Alfred King-yin Lam; Yuwei Liang; Xiaojing Sun; Qian Jiang; Bin Qiao (Functional & Integrative Genomics, 2026)

Rosmarinic acid ameliorates radiation-induced intestinal injury through PI3K/AKT/NF-κB/MMP9 axis inhibition: From network pharmacology prediction to experimental validation - Xiaoxue Li; Jing Zhang; Yutong Dong; Zheng Zhou; Beier Jiang; Tianjiao Min; Bin Song; Gang Jin; Li Ma; Bolin Li; Luyao Yu; Ying He (Tissue and Cell, 2026)

Unveiling and steering Thiobacillus denitrificans metabolic network to tackle denitrification inhibition under antibiotic-heavy metal co-exposure - Xinyi Wang; Can Wang; Tianhong Bao; Kexin Zhang; Liyue Jiang; Bin Wu; Peng Bao; Fei Xu; Likai Hao; Shun Li (Bioresource Technology, 2026)

Integrative analysis of metabolome and transcriptome uncovers the effects of vanillic acid treatment on reducing surface browning of fresh-cut taro - Xiao Yuan; Liang Shuai; Yuanyuan Jiang; Jun Li; Bin Wang (Postharvest Biology and Technology, 2026)

Physics-regularized deep learning for passive sound speed inversion: Enhancing underwater acoustic navigation and communication in deep-sea environments - Xuerong Cui; Jia Tian; Juan Li; Shuai Cui; Lei Li; Bin Jiang (Ocean Engineering, 2026)

Numerical analysis of unsteady force characteristics and harmonic generation mechanism for a novel coupled propeller in an inhomogeneous wake - Liang Li; Yihong Chen; Hui Xia; Bin Zhou; Jingwei Jiang; Chao Wang (Ocean Engineering, 2026)

Comparison between microscale sealed vessel pyrolysis (MSSV) and gold tube pyrolysis for the simulation of oil cracking - Shufen Liu; Pufan Wang; Xinyan Fang; Hao Li; Wenmin Jiang; Bin Cheng; Yun Li; Liangliang Wu (Organic Geochemistry, 2026)

Transformation of antibiotics mediated by iron-bearing minerals: A review - Yu Fu; Tao Wang; Jiamin Cai; Jieyun Lin; Shi Chen; Jiang Li; Bin Wang; Shaoqi Zhou; Yuanyuan Liu (Journal of Environmental Sciences, 2026)

Stable chloroform emissions in southeastern China: insights from recent observations - Zhiwei Cao; Yonglong Lu; Pei Wang; Yunlei Zhang; Yulin Xu; Zhaoyang Wu; Xinyi Huang; Haojie Lei; Bin Sun; Jialong Li; Xudong Jiang; Yizhou Jiang (Journal of Environmental Sciences, 2026)

Unlocking enhanced oil recovery through the anomalous hydrodynamics of CO2 microbubbles under high pressure - Baocai Tong; Donglei Liu; Mengting Liao; Jintao Xu; Bin Ding; Jiazhong Wu; Yisong Li; Lanlan Jiang; Yongchen Song (Fuel, 2026)

Effect of low-temperature treatment on the physicochemical, interfacial, and foaming properties of wheat gliadin nanoparticles - Muhammad Asif Ismail; Tianxu Liu; Ying Jiang; Abel Wend-Soo Zongo; Mohamed Eid; Jing Li; Bin Li (Food Chemistry, 2026)

Engineering an efficient cellulolytic microbial consortium and optimizing multi-strain fermentation of vinegar residue to mitigate soybean meal deficit - Xinyi Li; Bin Jiang; Yuanyuan Liu; Yu Yan; Chunyu Li; Chunyang Wan; Firdoz Shaik (Food Bioscience, 2026)

Cometabolic degradation of ofloxacin by aerobic methane oxidation coupled with denitrification: Identification of degraders, helper bacteria, and metabolic networks - Shanshan Wei; Lele Wang; Yancheng Li; Bin Wang; Tao Wang; Jiang Li (Bioresource Technology, 2026)

The differentiated VOC species vertical profiles and regional source contributions induced by transport and their reactivities over Nanjing - Yanling Wang; Bin Zhu; Siqi Yang; Wen Lu; Shuangshuang Shi; Zhuyi Jiang; Li Xia; Chenyan Qian; Jinhui Gao (Atmospheric Environment, 2026)

In vitro regeneration via indirect organogenesis from aseptic seedling-derived explants of the rare Tibetan medicinal shrub Sibiraea angustata - Mengting Pi; Xue Yu; Hongchang Li; Yali Guo; Wuyang Lai; Leipeng Cao; Tao Jiang; Lingxia Xu; Fuhua Peng; Hongdong Liu; Fei Wang; Jianguo Hu; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Revelation of the mechanism by which charging of cotton leaves enhances electrospray deposition: systematic verification based on multi-physics field coupling simulation and high-speed camera observation - Xinming Wu; Miaomiao Xu; Jiang Wu; Junwei Li; Yongxu Yan; Falei He; Bin Hu; Xin Luo; Zhen Ma (Computers and Electronics in Agriculture, 2026)

The influence of replacing soybean meal with corn gluten meal on the digestive and absorptive capacity and amino acid metabolism of sub-adult grass carp (Ctenopharyngodon idella) - Yan Liu; Xiao-Qiu Zhou; Lin Feng; Wei-Dan Jiang; Hong-Yun Zhang; Yao-Bin Ma; Yang Liu; Shu-Wei Li; Wen-Jie Tang; Cheng-Bo Zhong; Pei Wu (Aquaculture, 2026)

A feature selection and per-indicator modeling framework for forecasting multivariate effluent water quality in wastewater treatment plant - Zewei Liu; Lei Zhang; Mingqian Cheng; Yue Zhao; Xingqiang Jiang; Zixian Pang; Xingping Yuan; Bin Li; Zhangwei He (Water Research, 2026)

A fully human antibody A140 neutralizes abrin toxin via lysosomal intracellular mechanisms, confers potent protection in vitro and in vivo, and reverses transcriptomic dysregulation with a Favorable safety profile - Feng Qin; Shi-You Chen; Peng Lin; Bin Wang; Xin Fu; Jian-Li Jiang; Hong-Yong Cui; Shi-Jie Wang (Toxicology and Applied Pharmacology, 2026)

Structurally diverse diterpenoids from Euphorbia milii: Discovery and RORγt-binding evaluation - Meng-Yuan Dai; Xue-Li Hu; Wen-Chang Li; Zhi Lu; Bin-Yuan Jiang; Hua-Mei Chen; Ying Zeng; Dong-Hua Cao (Phytochemistry, 2026)

Ni regulated LaMnO3 for selective nitrite to ammonia electroreduction - Kun Lang; Yuanyingxue Gao; Panzhe Qiao; Xudong Xiao; Mingyang Liu; Bin Wang; Xinrui Li; Wei Wu; Jingping Ge; Huiyuan Meng; Baojiang Jiang (Journal of Hazardous Materials, 2026)

Plasma-treated biomass carbon/zinc-manganese dual metal organic frameworks (MOFs) composite electrode for high-performance supercapacitors - Linlin Tai; Gaigai Duan; Qian Wei; Xiaoshuai Han; Weijun Li; Yong Huang; Bin He; Shuijian He; Shaohua Jiang (Fuel, 2026)

Tailoring lipases as versatile food biocatalysts to enhance their comprehensive performance: A state-of-the-art review - Jiaojiao Xia; Oussama Kouiti; Zhouyuan Zhao; Jiayi Chen; Sunjie Zhang; Luyi Chen; Yuzhe Xie; Zhi Li; Yi Hu; Ling Jiang; Rubing Huang; Bin Zou (Food Chemistry, 2026)

Mechanism of Botrytis cinerea inhibition by ultrasound combined with natamycin and its application in strawberry preservation - Xu Si; Wanqi Hong; Yiming Zhang; Hanqian Jiang; Dongnan Li; Yanqun Wang; Dingchen Shao; Bin Li (Food Control, 2026)

Thermally activated persulfate-driven rapid abiotic carbon source production of food waste: Performance, organic matter evolution and denitrification potential - Xu Xing; Xiupeng Jiang; Xiaoya Li; Yanyan Guo; Xiaochan Su; Youcai Zhao; Bin Xu; Tao Zhou (Environmental Research, 2026)

Sex-specific associations between prenatal PM2.5 exposure and reproductive hormone levels in offspring aged 1–2 years: A prospective birth cohort study - Wenpu Shao; Shengli Jiang; Yudiyang Ma; Ning Chen; Zhiping Niu; Rui Tang; Meiqi Xing; Lei Zheng; Xinru Zhao; Bin Sun; Haibo Li; Ziyi Zhou; et al. (Environmental Research, 2026)

The lnc40545-miR-965-CYP307A1 regulation pathway mediates imidacloprid resistance in Rhopalosiphum padi (L.) - Yong-Po Lv; Ren-Jie Li; Yu-Tai Jiang; Bai-Zhong Zhang; Yu-Yang Peng; Yong Sun; Dong-Mei Chen; Fan-Bin Kong; Run-Qiang Liu; Hai-Hong Gu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Static aqueous zinc-bromine batteries: Fundamental mechanisms, interfacial engineering, and future perspectives - Bin Wang; Yajiang Wang; Xiudong Chen; Ruizi Li; Yan Huang; Xiaoduo Jiang; Huanan Hu; Jin-Hang Liu; Yao Xiao (Chemical Engineering Journal, 2026)

Achieving 14.52% efficiency in Cu2ZnSn(S,Se)4 solar cells via a sandwich-structured precursor prepared from two different Ag/Cd co-doped Cu2ZnSnS4 solutions - Mengge Li; Bin Yao; Shuang Li; Yuhong Jiang; Yongfeng Li; Zhanhui Ding; Ruijian Liu; Hongmei Luan (Chemical Engineering Journal, 2026)

Titanate-functionalized separator enables an in-situ redox reaction toward intrinsically dendrite-free aqueous zinc-ion batteries - Tong Jiang; You Fu; Zhenyu Wang; Siqinhaolu Hao; Yaxin Li; Zilong Liu; Mingjie Jia; Yongjian Ai; Yinggang Jia; Guangwen Xu; Hong-bin Sun (Chemical Engineering Journal, 2026)

Effect of temperature on the performance of electrochemical oxygen pump in liquid lead–bismuth eutectic - Min Zhang; Wenyi Ding; Zhizhong Jiang; Lin Luo; Mingjie Zheng; Yang Li; Wangli Huang; Bin Wu; Xin Wu; Xingming Yang (Annals of Nuclear Energy, 2026)

Maternal and Neonatal Factors Impacting the Volume and Cellular Composition of Umbilical Cord Blood - Yu Li; Jia Liu; Ming Li; Chunyu He; Bin Guo; Ye Yang; Rongzhen Jiang (Stem Cell Reviews and Reports, 2026)

Impact of age on safety of pancreaticoduodenectomy: a nationwide cohort study stratified by surgical approach and anastomotic technique with optimal age cut-off analysis - Hongwei Huang; Feng Xia; Tianyin Shao; Baiyong Shen; Xinmin Yin; Xiaoqing Jiang; Deyu Li; Jing Li; Sen Qiao; Songqing He; Heshui Wu; Jiayun Ge; et al. (Science China Life Sciences, 2026)

Photoactive and self-sustaining: How soil organic matter drives the natural remediation of Cr(VI) via photochemical pathways at the soil-water interface - Yaoning Chen; Mengwei Luo; Yuanping Li; Jun Wang; Hongjuan Jiang; Mengyang Zhao; Yaoqin Nie; Bin Zou; Qianruyu Wang; Nianping Chi (Water Research, 2026)

Retraction notice to “Boronic acid-modified bacterial cellulose microspheres as packing materials for enveloped virus removal” [Sci. Total Environ. 859 (2023) 160341] - Zhiyang Lin; Linhan Li; Kaige Song; Bin Yang; Guoqing Zhou; Gengrong Zhang; Jiang Teng; Erlong Wang; Xiaoqiang Liu; Fei Ling; Gaoxue Wang; Tianqiang Liu (Science of The Total Environment, 2026)

Spatially coupled effects of urban vegetation on air pollution and heat islands in coastal cities across the globe - Kongming Li; Yonglong Lu; Bin Sun; Qi Wang; Yunting Xiong; Zhenjun Zhang; Xudong Jiang; James M. Bullock; Jingjing Yuan (Science Bulletin, 2026)

A star’s death by a thousand cuts: the runaway periodic eruptions of AT2023uqm - Yibo Wang; Tinggui Wang; Shifeng Huang; Jiazheng Zhu; Ning Jiang; Wenbin Lu; Rongfeng Shen; Shiyan Zhong; Dong Lai; Yi Yang; Xinwen Shu; Tianyu Xia; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Comparative evaluation of emerging and traditional thawing technologies on quality attributes, water migration, microstructure, and volatile compounds of frozen strawberries - Hanqian Jiang; Dongnan Li; Dingchen Shao; Ziqi Song; Xu Si; Bin Li (Food Chemistry, 2026)

Atomically precise ferrocene-based Fe/Mn nanocluster for solar-driven cycloaddition of epoxides with carbon dioxide - Xue-Feng He; Chun-Yang Li; Yu-Lin Jiang; Wan-Yu Zhu; Qiu-Hong Cheng; Kun Huang; Da-Bin Qin; Xiang-Yu Zhang (Chemical Engineering Journal, 2026)

IL-8-expressing recombinant Bacillus subtilis: A novel immunostimulant for improving production efficiency and disease resilience in Sebastes schlegelii aquaculture - Qing Yang; Hong-Yu Jiang; Ming-Tao Li; Bin-Tong Yang; Shu Li; Wei Cong; Yuan-Huan Kang (Aquaculture, 2026)

Failure characteristics and development mechanism of time-delayed rockburst in a tunnel excavated via the drilling and blasting method: A case study - Lei Hu; Wen-Fei Chang; Ben-Guo He; Wei Zhang; Jun Zhao; Zhi-Bin Yao; Meng-Fei Jiang; Hong-Pu Li; Lian-Jie Fu (Tunnelling and Underground Space Technology, 2026)

Pronounced molecular helicity as a design handle to accelerate spin-flip dynamics in B,N-embedded multi-resonance emitters toward ultra-high-efficiency OLEDs - Linfeng Jiang; Chao Feng; Jian Wu; Meng Li; Ge Gao; Zhengyang Bin; Jingsong You (Science Bulletin, 2026)

Haplotype-resolved long-read sequencing reveals parent-of-origin effects of tandem-repeat variation in autism spectrum disorder - Jinchen Li; Tengfei Luo; Xue Ren; Songyu Yang; Hui Quan; Yan Zhu; Senwei Tan; Xiangbin Jia; Pei Yu; Yuanfeng Huang; Zhaowei Jiang; Xudong Xiang; et al. (Science Bulletin, 2026)

An innovative urban drainage network pipe diameter optimization method based on an enhanced genetic algorithm and multi-stage disaster mitigation model - Weichao Yang; Maomao Li; Lingling Bin; Xuelian Jiang; Hao Wang; Meifang Ren; Haoyang Liang; Xiangdong Liu; Lin Yan (Journal of Hydrology, 2026)

Genome-wide interactions with cadmium exposure in dysglycemia: populational effects and molecular insights - Qi Jiang; Bin Li; Yunfei Ma; Wanying Shi; Liang Ding; Naifan Hu; Yunhao Zhao; Yingli Qu; Zheng Li; Peijie Sun; Yifu Lu; Donghui Zhang; et al. (Journal of Hazardous Materials, 2026)

Ecological implications of fishery-photovoltaic systems: Altered phytoplankton dynamics and reduced microbial network stability under photovoltaic coverage - Xinping Chen; Bin Li; Sheng Li; Yandong Xu; Bin Jiang; Chuangye Xie; Qianqian Du; Nan Wang; Li Gao; Tao Jiang; Di Zhang (Journal of Cleaner Production, 2026)

Dual-descriptor-guided acidic electrolyte additives for ultra-stable ah-level zinc-ion batteries - Yuxin Sun; Bin Cai; Fei Yu; Xuesong Li; Wei Lü; Yi Jiang (Chemical Engineering Journal, 2026)

Tailoring charge redistribution to suppress lattice oxygen release in Ni-rich single–crystal cathodes - Qianqian Jiang; Zhencheng Huang; Xi Chen; Tao Huang; Jingguo Gao; Yingqi Xu; Jinqi Dong; Wei Zeng; Haoran Wei; Feifan Wan; Lin Chen; Bin Liao; et al. (Chemical Engineering Journal, 2026)

Pesticide beta-cypermethrin impairs endometrial decidualization and embryo implantation by suppressing autophagy through oxidative stress - Li-Qing Wang; Huang-Nian You; Qiong-Jun Xu; Wen-Jie Yu; Xiao-Mei Wu; Xiao-Qing Pang; Xiao-Xi Chen; Wen-Bin Du; Qian-Feng Qiao; Jing-Ai Li; Yu-Meng Zhou; Yong-Jiang Zhou (Chemico-Biological Interactions, 2026)

Shifts in sources of non-methane hydrocarbons in the most ozone-polluted region of the Pearl River Delta, China (2020–2023) - Li Luan; Zhen Zhou; Shenlang Zhang; Jun Tao; Xihua Li; Shuzhen Su; Zhisheng Zhang; Guanghui Li; Bin Jiang; Daocheng Gong; Zhanyi Zhang; Boguang Wang (Atmospheric Pollution Research, 2026)

8-Me-PIQ Expands Cord Blood CD34+ Hematopoietic Stem and Progenitor Cells via Metabolic Suppression and Inhibition of Ribosome Biogenesis - Yu Li; Mengmeng Li; Bin Guo; Rongzhen Jiang (Stem Cell Reviews and Reports, 2026)

Alisertib exerts AURKA-independent antitumor activity in colon cancer by modulating immune-related pathways - Qi Gao; Xingyu Zhang; Kaiyuan Hui; Xun Zou; Luyao Li; Zien Yu; Yiwen Feng; Xiaozhu Shen; Xiaodong Jiang; Bin Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Intermittent Theta-Burst Stimulation (iTBS) Modulates Abnormal Brain Activity During Emotional Arousal in Adolescent Depression: A Pilot Study - Zeyang Zhao; Yuan Liu; Jiang Wang; Peiying Li; Zhi Yang; Ling Sun; Bin Zhang (Brain Topography, 2026)

Amino acid and appendicular skeletal muscle mass insufficiency are associated to cognitive decline in Chinese population - Ting Tang; Shuxian Zhang; Yanni Pu; Siquan Li; Bin Jiang; Huiting Liang; Kunmu Zheng; Yan Zheng; He Huang; Jin Li; Xiaodong Pan (GeroScience, 2026)

MnOx media and biologically formed MnOx on sand surface from Mn(II) oxidation significantly promote dissolved aluminum removal in filtration systems - Quanying Jiang; Xuyang Liu; Yuliang Su; Pei Cao; Yanan Huang; Bin Wu; Yili Wang; Jianwei Yu; Baoyou Shi; Guiwei Li (Water Research, 2026)

Shifting from concentration-based to health-oriented air pollution control in China - Zhaoxin Dong; Shuxiao Wang; Haotian Zheng; Fenfen Zhang; Shengyue Li; Yueqi Jiang; Jia Xing; Dian Ding; Dejia Yin; Qian Song; Bin Zhao; Yun Zhu; et al. (Science Bulletin, 2026)

Hepatoprotective and anti-inflammatory dibenzocyclooctadiene lignans from fruits of Kadsura coccinea - Guy Paulin M. Kemayou; Juan-jiang Wu; Wen-chao Zhou; Shi-qi Liu; Piao-piao Jiang; Hanwen Yuan; Wei Su; Bin Li; Simeon F. Kouam; Wei Wang; Yu-pei Yang (Phytochemistry Letters, 2026)

Optimizing nitrogen release patterns for direct-seeded rice: A life cycle assessment - Xinao Tang; Bo Lu; Xiaoyue Jiang; Zhengyang Wu; Ziyu Li; Yuhui Wang; Jie Sun; Hao Wu; Maomao Sun; Bin He; Shen Gao; Zhengrong Jiang; et al. (European Journal of Agronomy, 2026)

A power-law relationship between bulk modulus and permeability in fractured sandstone: Insights from tidal analysis - Xu-Lin Tang; Xiao-Wei Jiang; Zhe-Ming Shi; Zhi-Yu Qi; De-Qiang Mao; Xu-Sheng Wang; Yan Zhang; Li Wan; Hong-Bin Yan (Engineering Geology, 2026)

Circular upcycling of fly ash into silicon-tuned FAU zeolites for VOCs and CO2 capture - Hongyuan Ma; Sunwen Xia; Kexin Jia; Hongyuan Jiang; Bin Wang; Bing Li; Dong Wang; Junhua Li (Chemical Engineering Journal, 2026)

In-situ sulfur element-induced heterogeneous interface engineering for high-performance supercapacitors - Mingzhe Shan; Yi Jiang; Ruixiang Xu; Bin Cai; Yi Gao; Heju Zhao; Jiaming Wang; Yaozeng Lu; Xiqing Song; Surong Tan; Yishan Yuan; Zining Li; et al. (Chemical Engineering Journal, 2026)

Intercellular Mitochondrial Transfer as Endogenous Neuroprotection: Mechanisms and Therapeutic Implications in Ischemic Stroke - Yun-Fan Zhang; Di Zhao; Jing-Jing Wei; Xiao Liang; Liu-ding Wang; Jia-Wei Wang; Li-bin Jiang; Ju-Ying Chen; Yun-Ling Zhang; Yue Liu (Translational Stroke Research, 2026)

The improvement of long-chain polyunsaturated fatty acids (LC-PUFAs) content and its relationship with intestinal microbiota modulation by Bdellovibrio and like organisms (BALOs) supplementation in American eels (Anguilla rostrata) - Yanbiao Guo; Jingyin Liu; Lingxiao Li; Huixiang Chen; Jintao Lǚ; Bin Jiang; Haifu Zhang; Guiying Kuang (Animal Feed Science and Technology, 2026)

Probabilistic Retrieval of All-Day Overlapping Cloud Microphysical Properties - Jingwei Li; Baoxiang Pan; Feng Zhang; Bin Guo; Wenwen Li; Geng-Ming Jiang; Xin Wu; Quan Wang (Advances in Atmospheric Sciences, 2026)

YOLOv8m-CGSE: An Improved Lightweight YOLOv8m for Marine Oil Spill Detection - Qingyang Wang; Junjie Lu; Bin Yang; Chen Jiao; Tao Yue; Bo Song; Jianwu Jiang; Guoqing Zhou; Jingwen Li (Journal of Marine Science and Engineering, 2026)
Unmanned Aerial Vehicle (UAV) remote sensing images provide high-resolution and flexible monitoring data for oil spill detection. To address the high computational cost and low accuracy of traditional models, this study proposes an improved model, YOLOv8m-CGSE. The model replaces standard convolution with Group Shuffle Convolution (GSConv), substitutes the C2f module with SENetV2, and introduces a light-weight Cross-scale Context Fusion Module (CCFM) to enhance multi-scale feature representation while maintaining a lightweight structure. Mosaic augmentation was applied to the marine oil spill dataset, improving mAP50 and mAP50–95 to 85.4% and 62.0%, respectively. Based on YOLOv8m, the proposed YOLOv8m-CGSE achieved mAP50 and mAP50–95 of 91.2% and 73.3%, respectively, improving accuracy while reducing parameters by 16.1% and computational cost by 12.6%. Furthermore, a supplementary vulnerability test on highly deceptive oil-free sea surfaces demonstrated that the proposed model actively suppresses complex background clutter (e.g., ship wakes and wave anomalies), effectively reducing false positive detections from 21 (baseline) to 15. The results demonstrate that the proposed model effectively balances high precision, robustness against visual lookalikes and computational efficiency for real-time marine oil spill monitoring.

Tidal Influence on Seawater Intrusion in Underground Water-Sealed Oil Storage Caverns - Yutao Li; Laidi Li; Bin Zhang; Jiasheng Jiang; Jieyu Shuai (Journal of Marine Science and Engineering, 2026)
Building underground water-sealed oil storage (UWSOS) caverns on islands poses a potential risk of seawater intrusion. As UWSOS is mostly constructed within rock masses, research on seawater intrusion through rock fractures holds important engineering value. This study combines single-fracture model tests with numerical simulations to investigate patterns of seawater intrusion in fractured rocks. Results show that, due to the density difference between seawater and freshwater, a saltwater wedge forms in coastal zones. Under tidal action, an upper saltwater plume forms in the intertidal zone, with its scale positively correlated with tidal range. After cavern excavation, the saltwater–freshwater transition zone widens, and seawater gradually intrudes from the cavern bottom. The upper saltwater plume evolves into a “saltwater tongue” during intrusion, with a growth rate ranging from 921.89% to 5691.52%, while the lower saltwater wedge moves landward by 37.86% to 82.65%. The saltwater tongue scale increases with tidal amplitude, but the lower wedge scale shrinks. With the horizontal water curtain installed, the saltwater wedge area decreases by 45.42% to 57.33%; in contrast, installing a vertical water curtain can effectively block seawater intrusion. These results provide an important experimental foundation for seawater intrusion research in island UWSOS caverns.

Animal gut microbes and microbiomes in the 21st century and beyond - Zhigang Zhang; Feng Jiang; Zhipeng Li; Limei Lin; Bin Qi; Dandan Han; Chao Ran; Shengyong Mao; Junjun Wang; Zhigang Zhou; Min Wang; Jilian Li; et al. (Science China Life Sciences, 2026)
Animal gut microbiomes—comprising bacteria, archaea, fungi, viruses, and protozoa—are fundamental to host evolution, physiology, and ecosystem resilience. This review synthesizes 21st-century advances in their diversity, spatiotemporal dynamics, and functional roles across the animal kingdom. Although high-throughput metagenomics has transformed the field, major biases remain: most studies still focus on domesticated vertebrates and fecal samples, leaving substantial “microbial dark matter” in wild hosts, invertebrates, and non-bacterial domains unexplored. We highlight how gut microbiomes mediate adaptation to environmental extremes, including hypoxia, temperature stress, and toxins, and how industrialization disrupts these communities, contributing to biodiversity loss and disease risk. We further integrate eco-evolutionary theory, multi-omics, and spatial modeling to clarify cross-kingdom interactions and functional networks. Finally, we discuss translational applications—including probiotics, fecal microbiota transplantation (FMT), phage therapy, and synthetic consortia—and emphasize the need for global collaborative initiatives, artificial intelligence (AI)-driven discovery, and standardized databases to unlock the full potential of animal gut microbiomes for biodiversity conservation, climate resilience, and planetary health in the coming decades.

Metabarcoding analysis of eukaryotic microalgae communities in the surface sediments of an integrated multi-trophic aquaculture zone - Yongrui Pi; Fei Wang; Ke Sun; Xin Chen; Bin Li; Tao Jiang (Marine Pollution Bulletin, 2026)

Hydroxytyrosol preserves myofibrillar protein integrity in grass carp (Ctenopharyngodon idella): Implications for flesh quality enhancement - Yi-Wei Liao; Pei Wu; Wei-Dan Jiang; Hong-Yun Zhang; Yao-Bin Ma; Yang Liu; Shu-Wei Li; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2026)

ZmSWEET6A/6B are required for maize male fertility via balancing sugar and lipid metabolism during pollen and anther development - Shuangshuang Liu; Yilin Jiang; Canfang Niu; Fan Zhang; Lina Zhao; Quancan Hou; Ziwen Li; Yingwei Qu; Bin Ma; Qingping Jiang; Yan Long; Xueli An; et al. (Science Bulletin, 2026)

Speciated emissions of full-volatility organic compounds from plastic manufacturing: atmospheric impacts and toxicity generation - Dongyang Wu; Qing’e Sha; Luyun Liu; Citao Zhang; Shan Jiang; Qing Guo; Junhao Xu; Jialin Song; Renjun Li; Liufen Cai; Haoqi Chen; Guanghui Li; et al. (Journal of Environmental Sciences, 2026)

Selenium-enriched Lacticaseibacillus rhamnosus SHA113 alleviates fatigue under simulated high-altitude hypoxia in mice through intestinal microbiota and antioxidant modulation - Guanwen Liu; Yinghui Li; Chi Li; Mingliang Jin; Xiaoya Shang; Dongyan Shao; Chunmei Jiang; Lu Yan; Bin Jia; Dachuan Yin; Junling Shi (Food Bioscience, 2026)

The interaction mechanisms of arabinogalactan-protein with mucin to regulate sodium migration behavior: Effect of glycoprotein-to-glycan ratio in gum arabic - Xuyue Wang; Ying Jiang; Jing Li; Bin Zhou; Yan Li; Bin Li; Hongshan Liang (Food Hydrocolloids, 2026)

Leaf functional traits and wood density of evergreen and deciduous tree species in a tropical karst forest - Yu-Meng Gao; Shi-Jian Yang; Jiao-Lin Zhang; Yan-Juan Jiang; Shu-Bin Zhang; Amy Ny Aina Aritsara; Guo-Hao Hu; Pei-Li Fu; Ze-Xin Fan; Kun-Fang Cao (Flora, 2026)

Co-assembled organic phosphorescent crystals with ultralong phosphorescence in high-temperature and water environment - Bin Li; Ziyi Lu; Wensheng Xu; Run Wang; Jiang Liu; Linshuo Jiang; Yin Xiao; Jianchao Ma; Yang Li; Xilong Yan; Bowei Wang; Ligong Chen (Chemical Engineering Journal, 2026)

Sustainable bioprocess engineering for integrated inland water remediation and waste-to-product conversion - Li Jiang; Xiaoxiao Yan; Haijun Wang; Bin He; Xiaojun Yan; Roger Ruan; Pengfei Cheng (Bioresource Technology, 2026)

Exposure to magnesium oxide nanoparticles induces mitochondrial dysfunction and apoptosis in fish Megalobrama amblycephala by disrupting magnesium homeostasis - Ling Zhang; Zi-Shang Liu; Si-Si Xiong; Yan-Zou Dong; Yue-Yun Guo; Ding-Dong Zhang; Guang-Zhen Jiang; Wen-Bin Liu; Xiang-Fei Li (Aquatic Toxicology, 2026)

Isoliquiritigenin combined with gemcitabine inhibited lung cancer by suppressing JAK2/STAT3 signaling via lncRNA-p21/miRNA-4534 axis - Chenyue Xu; Cancan Gong; Cheng Wang; Meiping Xie; Mianhua Wu; Dengfeng Ge; Hao Ren; Bin Zhang; Zequn Jiang; Wenting Li (Journal of Natural Medicines, 2026)

Folic acid supplementation modulates hormone dynamics, biochemistry, gene expression, and folate concentrations in hormonally induced Japanese eel (Anguilla japonica) Broodstock: Insights from mucus as a non-invasive sampling matrix - Justice Frimpong Amankwah; Jingwei Liu; Mekonen Hailu; Kanghong Jiang; Bin Xie; Xiangbiao Zeng; Huan Han; Junming Zhang; Yanhe Liu; Tianwei Jiang; Zhenzhu Wei; Nawal Asif; et al. (Aquaculture, 2026)

Bridging cortical intentions: brain–computer interfaces for spinal cord injury recovery - Xuantao Hu; Jiale He; Na Li; Jian Mo; Senyu Yao; Yubao Lu; Mudan Huang; Pan Jiang; Mao Pang; Lei He; Jin Gong; Zifeng Liu; et al. (Science Bulletin, 2026)

Comprehensive understanding of new particle formation in China through advanced modeling - Jiewen Shen; Bin Zhao; An Ning; Wei Nie; Chao Yan; Yuyang Li; Runlong Cai; Alfonso Saiz-Lopez; Manish Shrivastava; Biwu Chu; Da Gao; Nanna Myllys; et al. (Science Bulletin, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Nanocarrier-delivered dsRNA targeting cuticular protein CPAP3-2 enhances Etoxazole efficacy in tetranychid mites - Haifeng Wang; Chenyu Jiang; Tianrong Xin; Yuehan Li; Bin Xia (Pesticide Biochemistry and Physiology, 2026)

CoagLite: A low-computational-cost integral model for simulating indoor ultrafine particle dynamics - Chen Chen; Chuanhao Wang; Wenxin Wang; Xiaomin Zhong; Linxi Li; Wenwei Zhang; Feng Shi; Jingkun Jiang; Bin Zhao (Journal of Hazardous Materials, 2026)

Distribution pattern and development of typical antibiotic resistance genes in the continuous-flow aerobic granular sludge-membrane bioreactor system - Yongsheng Jiang; Yu Zeng; Lei Shang; Dehong Bai; Liying Bin; Weirui Chen; Xinyi Chen; Shanglong Wen; Shaosong Huang; Ping Li; Bing Tang (Journal of Environmental Chemical Engineering, 2026)

Biogas slurry substitution for chemical fertilizer under fertigation enhances soil fertility and maize yield sustainability: A meta-analysis - Yue Jiang; Bin Shi; Run Xue; Hong Li; Bingyu Li; Luya Wang; Nuo Li (Journal of Environmental Management, 2026)

Synergistic and antagonistic interactions drive DOM dynamics in industrial effluents: Insights from double difference EEM analysis - Jiancheng Li; Bin Wang; Zhichao Yun; Yu Yang; Fu Xia; Xu Han; Qiyuan Liu; Yonghai Jiang; Junwen Hou (Journal of Environmental Chemical Engineering, 2026)

Dimensionality engineering of copper phthalocyanine-based covalent organic frameworks for enhanced electrocatalytic nitrate reduction - Mingrun Li; Mingyue Wang; Bin Han; Jianzhuang Jiang (Chemical Engineering Journal, 2026)

Dual regulation of surface termination and interlayer spacing of MXene for high-performance vanadium redox flow batteries - Tianxing Yuan; Xingrong Chen; Yanqin Zhao; Yingqiao Jiang; Bin Li; Ningning Zhao; Jing Zhu; Lei Dai; Ling Wang; Zhangxing He (Chemical Engineering Journal, 2026)

A novel all-weather photo–electric synergistic process for inactivating alga in fresh waters: Performance and mechanism - Tiantian Chen; Bin Qi; Xueze Guo; Ruixue Jiang; Erqin Yin; Shouping Zhou; Wenming Zhang; Xiaochen Li (Water, Air, & Soil Pollution, 2026)

Human Amniotic Mesenchymal Stromal Cells Promote Bone Regeneration via Regulating Ameloblastoma-Derived-Bone Marrow Mesenchymal Cells Crosstalk and Autophagy in Ameloblastoma Microenvironment - Yuhuan Xiao; Xiaofeng Fu; Weina Zhou; Jin Li; Bin Yan; Fei Jiang (Tissue Engineering and Regenerative Medicine, 2026)
Background: Growing evidence validates the vital function of mesenchymal stem cells (MSCs) in tumor development. Our previous findings have illustrated the role of MSCs in the invasion and recurrence of ameloblastoma. Stem cells can be transplanted to release paracrine factors in the tumor microenvironment (TME) to inhibit tumor progression and recurrence. The paracrine function of human amniotic mesenchymal stromal cells (HAMSCs) benefits bone regeneration. However, the dual function of HAMSCs in inhibiting tumor progression and promoting bone regeneration in the TME remains unknown. Methods: To analyze the role of HAMSCS in the cross-talk between mesenchymal ameloblastoma-derived cells (M-AMCs), human bone marrow mesenchymal stem cells (HBMSCs), and HAMSCs, an in vitro co-culture system of M-AMCs, HBMSCS, and HAMSCS was prepared. An in vivo ectopic transplantation model was employed further to detect the therapeutic effect of HAMSCs on bone regeneration. Results: A high-level basal autophagy was detected in the stroma of ameloblastoma. In the in vitro co-culture models, M-AMCs suppressed the proliferation, differentiation, migration, and autophagy of HBMSCs, and conversely, HBMSCs promoted the above phenotypes of M-AMCs. HAMSCs promoted the proliferation, differentiation, migration and autophagy of the co-cultured HBMSCs. Additionally, HAMSCs mediated the cross-talk between M-AMCs and HBMSCs. The in vivo ectopic transplantation model indicated that transplanted HAMSCs promoted bone regeneration by inhibiting the growth of M-AMCs and enhancing autophagy, as well as osteogenesis in bone defects of mice. Conclusions: The interaction of M-AMCs and HBMSCs may be associated with ameloblastoma recurrence. HAMSCs regulate the cross-talk between M-AMCs and HBMSCs to increase the autophagic level in the TME, thus inhibiting the progression and recurrence of ameloblastoma and promoting bone regeneration. Therefore, HAMSC-based therapy provides an alternative to facilitate bone regeneration and repair of ameloblastoma-induced bone defects.

Dynamic evolution of dominant channels and fine particle migration paths in granitie residual soil under seepage coupling using in-situ dynamic contrast CT scanning - Yun Que; Jin Tang; Ting Qiu; Zhenliang Jiang; Shanghui Li; Bin Weng; Jianbin Liu (Journal of Soils and Sediments, 2026)

Dietary Soy Isoflavones as a Pretreatment for Enhancing Ovarian Development in Female Japanese Eel (Anguilla japonica) Broodstock - Kanghong Jiang; Jingwei Liu; Zhenzhu Wei; Bin Xie; Xiangbiao Zeng; Justice Frimpong Amankwah; Tianwei Jiang; Yanhe Liu; Kang Li; Liping Liu (Fishes, 2026)
The gonadal development of Japanese eels (Anguilla japonica) plays a crucial role in the success of artificial breeding. Soy isoflavones, a class of phytoestrogens commonly found in aquafeeds, have shown potential in enhancing gonad development in fish. The present study evaluated the effects of dietary soy isoflavones on gonadal development, growth performance, histology, sex hormone levels, vitellogenin content, and expression of related genes in female Japanese eel broodstock. A 4-week feeding trial was conducted with 120 two-year-old female eels randomly assigned to four groups and fed diets containing 0 (C), 0.1 (L), 0.5 (M), and 0.9 (H) mg/g of soy isoflavones. The results indicated that gonadal development was enhanced in the M and H groups, as evidenced by a significantly higher gonadosomatic index (GSI) and increased oocyte cross-sectional area (CSA) in M group, and greater nutrient accumulation in both the M and H groups. The expression of er and cyp19a genes in the ovary was downregulated in the treatment groups, leading to decreased serum estradiol (E2) and increased testosterone levels. Furthermore, hepatic vtg gene expression was upregulated in the M and H groups, though VTG protein content remained unchanged, suggesting an initiation of vitellogenesis at the transcriptional level. In conclusion, dietary soy isoflavones at 0.5–0.9 mg/g provide an effective pretreatment strategy to enhance early ovarian development in Japanese eel broodstock, potentially improving their responsiveness to subsequent hormonal induction in artificial breeding programs.

Associations of adherence to the EAT-Lancet and plant-based diets with mortality and life expectancy: two nationwide cohort studies - Xiaoqin Xu; Jiang Li; Jie Li; Wenqi Shen; Xiao Tan; Fei Xu; Wen Zhang; Ningjian Wang; Yingli Lu; Bin Wang (GeroScience, 2026)

Environmental benefits and uncertainty analysis of full-depth reclamation in composite pavement rehabilitation - Bin Lei; Ying Liu; Bin Sun; Chaofeng Liang; Yizhe Wang; Dong Lu; Wengui Li; Wei Jiang (Transportation Research Part D: Transport and Environment, 2026)

A treasure waiting to be discovered: the potential of tourmaline's spontaneously polarized electric field for environmental applications - Mengyang Zhao; Yihuan Liu; Yaoning Chen; Yuanping Li; Huayue Kang; Longbo Jiang; Chen Zhao; Bin Zou; Nianping Chi; Jingxia Huang; Tianyun Zhou (Journal of Environmental Management, 2026)

Elucidation of formation mechanisms and key reaction pathways for sulfur-containing hazardous gases during coal combustion - Bin Li; Yun Lei; Wantong Jiang; Shiqi Zhang; Zhixin Yang; Qiang Yang; Jinzhang Jia; Wei Zhang; Xuetian Li (Fuel, 2026)

Tungsten-Induced High-Valent doping activates lattice oxygen in spinel oxides for efficient water oxidation - Yu Zhong; Mingze Ou; Bin Chen; Xiantuo Chen; Zhou Shi; Huanan Wang; Daolei Wang; Cheng Peng; Chaoen Li; Jiang Wu (Fuel, 2026)

Mechanistic insights into structural evolution of goji berry (Lycium barbarum L.) during pulsed vacuum drying procedure via moisture migration and cell wall polysaccharide transformations - An-An Zhang; Li-Zhen Deng; Long Xie; Ze-Kang Peng; Ming-Qiang Xu; Wan-Liang Hao; Yu-Hao Jiang; Wen-Bin Ze; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Dietary silymarin improves gut–liver health by enhancing intestinal barrier integrity and modulating TLR4/NF-κB and NLRP3-mediated inflammatory responses in Aeromonas hydrophila–infected grass carp - Feng Jia; Li Wei; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Hong-Yun Zhang; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Fish & Shellfish Immunology, 2026)

Bimetallic atom incorporation in MOFs: Real-time patch to existing synthesis/characterization insights and initial observations on their applications in water purification - Bin Zou; Yaoning Chen; Huayue Kang; Yuanping Li; Mengyang Zhao; Hongjuan Jiang; Jun Wang; Yihuan Liu; Xuyang Jia; Nianping Chi; Li Zhu (Environmental Research, 2026)

Berlin green decorated PVDF membrane with reversible wettability for on-demand oil/water separation and fouling mitigation - Hongguo Zhao; Longfei Zhang; Wenqing Li; Weiguo Kong; Hongyu Chen; Bin Jiang; Luhong Zhang; Yong Liu (Chemical Engineering Journal, 2026)

Chondrocyte-targeting hydrogel loaded with puerarin limits osteoarthritis development by maintaining mitochondrial function - Yunpeng Wan; Kai Shen; Jishi Jiang; Dan li; Mingming Ma; Chengmin Liang; Jie Cao; Bin Liu; Yu Ge; Lei Li; Yaguang Wang; Haiyang Yu (Chemical Engineering Journal, 2026)

Study on mining pressure law and its influencing factors of deep super-long gangue backfilling working face - Yang Kang; Zhang Qiang; Zou Mingjun; Cui Pengfei; Zong Tingcheng; Zhang Bin; Lv Haonan; Bai Yu; Deng Panbo; Li Jiang (Arabian Journal of Geosciences, 2026)

Large Potential for CH 4 Mitigation and Yield Improvement in China's Paddies Through Locally Optimized N Management - Haoyu Qian; Zhengqi Yuan; Xiangcheng Zhu; Yuanfa Huang; Min Li; Jiarui Li; Yuxin Ren; Jinfei Feng; Shan Huang; Wenjun Dong; Feng Jin; Jiping Gao; et al. (Global Change Biology, 2026)
Nitrogen (N) management is critical for ensuring food security and mitigating greenhouse gas (GHG) emissions. In rice paddies, the effectiveness of N management in maximizing yields and minimizing N losses is highly dependent on local environmental conditions and thus varies widely across regions. However, the influence of optimized, site‐specific N management on methane (CH 4 ) emissions remains poorly quantified and is not reflected in current IPCC Tier 1 methodologies. Here, we synthesize data from multiregional field experiments and conduct a meta‐analysis to show that locally optimized N management practices—such as delayed fertilizer application, reduced N input, and deep placement—reduce CH 4 emissions from rice paddies by 16%–21%. The experiments further show that these practices suppress CH 4 emissions by lowering soil N availability and organic matter decomposition, thereby limiting substrates for methanogenesis. Combining survey data from 155 counties with machine learning models, we estimate that implementing optimized N strategies across China's rice‐growing regions could reduce CH 4 emissions by 16% while simultaneously increasing rice yields by 7%. These findings underscore the dual benefits of locally optimized N management for agricultural productivity and climate change mitigation, and provide a foundation for improving CH 4 emission estimates under diverse management regimes.

Functional characterization of aldo-keto reductase genes from Lycoris aurea that participate in galantamine biosynthesis - Yiyu Xiang; Xiaoran Jiang; Jie Li; Bin Sun; Zhengtai Liu; Dongming Li; Mingzhu Wu; Ren Wang; Sheng Xu (Plant Science, 2026)

GONs-based delivery of a fused dsRNA targeting key cuticular genes (PcCPAP3-E and PcFTZ-F1): A novel strategy for Panonychus citri control - Haifeng Wang; Tianrong Xin; Chenyu Jiang; Yuehan Li; Bin Xia (Pesticide Biochemistry and Physiology, 2026)

Spatiotemporal evolution of natural gas leakage and explosion in confined buildings: Insights from accident-driven full-cycle simulation - Minghua Chi; Diya Hou; Fangzhou He; Bin Chen; Wei Li; Yuhao Tan; Hongye Jiang; Xiangguo Zeng (Fuel, 2026)

A microenvironment-responsive chitosan based injectable hydrogel with synergistic anti-inflammatory effects of triptolide and copper ions for spinal cord injury repair - Han-Jian Hu; Zhenming Tian; Zeng-Lin Li; Chun Cheung Chan; Hongyan Zhang; Shipeng Tang; Yu Chen; Zhaoyin Chen; Tian Hu; Bin Liu; Gang-Biao Jiang (Carbohydrate Polymers, 2026)

Experimental Investigation of Porosity and Permeability of Reservoir Rock Under the Action of CO2 and Its Oil Displacement Effect - Bin Zhang; Jun Luo; Fajian Nie; Liang Wang; Xi Jiang; Wei Li; Ya Meng (Natural Resources Research, 2026)

Amino-modified gangue-derived NaX zeolite for enhanced stabilization of lead and cadmium in contaminated soils: synthesis, performance, and leaching stability - Weiwei Zhu; Jingyi Xiong; Zhuoxi Huangfu; Jiang Yu; Pengxinyue Hang; Cheng Han; Ming Chen; Bin Li; Tao Gao; Junwei Yang; Yao Du (Environmental Geochemistry and Health, 2026)

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

Biogeochemical controls on the co-occurrence of mid-depth pH and DO minima in the inner shelf of the East China Sea - Dewang Li; Zhongqiang Ji; Bin Wang; Chen Zeng; Haiyan Jin; Zhibing Jiang; Xiao Ma; Qinyu Liu; Yixuan Tao; Yanbin Tang; Hongliang Li; Feng Zhou; et al. (Marine Pollution Bulletin, 2026)

Effects of different monochromatic light colours on growth performance, feeding, antioxidant capacity, transcriptomic response and gut microbiota of juvenile spotted sea bass (Lateolabrax maculatus) - Jichang Zheng; Bin Ma; Yan Jiang; Aijun Cui; Yongjiang Xu; Xin Cai; Bin Wang; Kaili Jiao; Tengkun Li; Hang Liu; Han Yan; Heting Zhou (Aquaculture, 2026)

Isolation and application of Bdellovibrio and like organisms (BALOs) for controlling Aeromonas hydrophila in the American eel (Anguilla rostrata) rearing water - Yanbiao Guo; Bin Jiang; Huixiang Chen; Haifu Zhang; Jingyin Liu; Jintao lǚ; Lingxiao Li; Wenxi Zhong; Shichao Wen; Chunlan Liang; Yi Huang; Zhiping Liang; et al. (Aquaculture, 2026)

An adaptive stratification algorithm for sound velocity profile based on NSGA-II multi-objective optimization - Xuerong Cui; Tongyu Zhou; Juan Li; Meiqi Ji; Lei Li; Bin Jiang; Shibao Li; Jianhang Liu (Ocean Engineering, 2026)

Dynamic response of a monopile offshore wind turbine under aero-hydrodynamic interaction - Zhiyuan Wu; Kai Gao; Changbo Jiang; Wei Pan; Bin Li; Chunlei Li; Zhichao Dong; Bin Deng; Jie Chen (Ocean Engineering, 2026)

Variational microeukaryotic community diversity through wide-bound Antarctic water masses - Jiyuan Wan; Furong Cao; Wangxinze Shu; Zhengang Liu; Bin Kong; Dong Li; Xiao-hua Zhang; Qian Liu; Mingjian Liu; Xiaochong Shi; Yong Jiang (Marine Environmental Research, 2026)

Short-term optimal scheduling rules extraction for hydro-solar-pumped storage complementary power systems based on orthogonal experimental design and a physics-constrained LSTM model - Lingwei Zhu; Bin Xu; Xinrong Wang; Huili Wang; Xinman Qin; Jiayi Jiang; Jinshu Li; William W.-G. Yeh; Shanshui Yuan; Wei Zhi (Journal of Hydrology, 2026)

Corrigendum to ‘Metabolic flexibility of rhizobacteria drives soil nutrient cycling and enhances rare earth elements hyperaccumulation in ferns colonizing degraded mine ecosystems’ [J. Environ. Manag. 395 (2025) 128013] - Yong-He Han; Xi-Wen Cui; Hai-Bin Han; Yang-Long Jiang; Li-Chao Tong; Jian-Fei Chen; Hong Zhang; Yong Zhang; Zhibiao Chen (Journal of Environmental Management, 2026)

Purification and identification of angiotensin-converting enzyme inhibitory peptides from fermented buffalo milk with Lactobacillus plantarum B - Qi Li; Shurou Chen; Bin Cao; Zhenyu Chen; Xiuren Tang; Tiemin Jiang; Hock Eng Khoo; Xinhong Dong (International Dairy Journal, 2026)

α-Octene grafting modification of discarded polypropylene masks and its resource utilization in heavy crude oil - Jingying Liang; Bin Li; Xiaolei Guo; Chenrui Jiang; Xia Wang; Yunlei Zang; Yefei Wang; Gang Chen (Fuel, 2026)

Core-Shell structural regulation and freshness indicating-keeping functions of starch-based Fiber membrane and its application in fresh-cut kiwifruits - Yao Ma; Yahua Xiao; Yuxi Lang; Yiwen Bao; Jiaxin Li; Yifan Guo; Honglin Jiang; Xinwei Wang; Chunting Qu; Wenzhuo Jin; Bin Li; Xu Si (Food Research International, 2026)

Substrate-driven microbial diversity and functional potential of plastisphere biofilms in a dynamic coastal ecosystem of northeastern Taiwan - Priyanka Muthu; Sakcham Bairoliya; Gowri Krishna Girija; Li-Chun Tseng; Bin Cao; Jiang-Shiou Hwang; Ying-Ning Ho (Environmental Pollution, 2026)

Optimized phosphorus partitioning enhances phosphorus use efficiency in strip-intercropped soybean - Li Wang; Yang Gao; Bin Cheng; Yi Yang; Huan Yang; Mei Xu; Yushan Wu; Weiguo Liu; Xiaochun Wang; Feng Yang; Taiwen Yong; Jiang Liu; et al. (European Journal of Agronomy, 2026)

Engineering uniform micro-nanochannels via superamphiphilic carbon nanotubes – A hydrogel evaporator with solar space management for salt-free desalination - Shuo Wang; Xiang Li; Wei Wang; Hongli Ma; Bin Hou; Yuying Deng; Hongqin Wang; Honglei Fan; Hongliang Liu; Lei Jiang (Chemical Engineering Journal, 2026)

Corrigendum to “Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment” [Chem. Eng. J. Volume 515, 1 July 2025, 163509/CEJ-D-25-01484R1] - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2026)

Exploring the mediating role of oxidative stress in the relationship between PM2.5 components and adverse pregnancy outcomes: Impacts on nucleic acids, proteins, and lipids - Yan Jiang; Deyan Wu; Yuqi Guo; Jia Xu; Hongjuan Liu; Aifeng Jia; Chen Li; Duan Ju; Liqiong Guo; Xueli Yang; Qiang Zhang; Bin Han; et al. (Atmospheric Pollution Research, 2026)

Determination of optimal biochar application and irrigation rate for tomatoes based on the EWM-TOPSIS evaluation method - Yue Jiang; BingYu Li; XuYing Wang; Bin Shi (Irrigation Science, 2026)

Identification of lncRNAs Associated with Imidacloprid Resistance in the Grain Aphid Rhopalosiphum padi (L.) (Hemiptera: Aphididae) - Ling-Ling Cui; Yong-Po Lv; Ren-Jie Li; Yu-Tai Jiang; Bai-Zhong Zhang; Yu-Yang Peng; Jin-Song Zheng; Fan-Bin Kong; Run-Qiang Liu (Neotropical Entomology, 2025)

Study on nitrogen and phosphorus adsorption from biogas slurry by biochars derived from different feedstocks - Jingjing Luo; Wenyu Jiang; Huan Ma; Mingfeng Wang; Qingfa Zhang; Bin Li; Weiwei Liu (Environment, Development and Sustainability, 2025)

Dynamic behaviors of fertilizer droplets impacting tea leaf surfaces - Bin Hu; Hong Li; Yue Jiang; Longfei Du (Computers and Electronics in Agriculture, 2025)

Decoding periodate-driven phototransformation of dissolved organic matter in sunlit waters: Multidimensional property shifts and molecular network reconfiguration - Kaiting Zhang; Ruiqi Zheng; Lihua Li; Bin Jiang; Mingbao Feng (Water Research, 2025)

A novel deep learning system for STEMI prognostic prediction from multi-sequence cardiac magnetic resonance - Yifan Chen; Meng Jiang; Chao Xia; Hang Zhao; Panpan Ke; Sheng Chen; Heng Ge; Keran Li; Xu Wang; Yufei Wang; Yezi Chai; Qiming Liu; et al. (Science Bulletin, 2025)

Dual-frequency multi-scale based submarine pipeline side-scan sonar image enhancement algorithm - Xuerong Cui; Xiaosen Liu; Lei Li; Juan Li; Jingyao Zhang; Bin Jiang; Shibao Li; T. Aaron Gulliver (Ocean Engineering, 2025)

Corrigendum to “An upscaling approach for estimating field-level irrigation water use through the Budyko framework” [J. Hydrol. 661 (2025) 133785] - Jingwen Zhang; Kaiyu Guan; Murugesu Sivapalan; Chongya Jiang; Ming Pan; Bin Peng; Wang Zhou; Trenton E. Franz; Xiaohong Chen; Kairong Lin; Zejun Li (Journal of Hydrology, 2025)

Integrated probabilistic forecasting framework for long-term reservoir outflow through dynamic coupling of meteorological–hydrological–engineering processes - Jiaying Tan; Bin Xu; Jian Zhu; Ping-an Zhong; Ran Mo; Jiangyuan Li; Yuanheng Dong; Xinman Qin; Jiayi Jiang; Huili Wang; Lingwei Zhu (Journal of Hydrology, 2025)

Metabolic flexibility of rhizobacteria drives soil nutrient cycling and enhances rare earth elements hyperaccumulation in ferns colonizing degraded mine ecosystems - Yong-He Han; Xi-Wen Cui; Hai-Bin Han; Yang-Long Jiang; Li-Chao Tong; Jian-Fei Chen; Hong Zhang; Yong Zhang; Zhibiao Chen (Journal of Environmental Management, 2025)

Identifying conservation gaps and proposing climate-smart strategies for amphibians and reptiles on the Qinghai-Tibet Plateau - Lu-Lu Sui; Zhong-Yi Yao; Shun Ma; Sheng-Chao Shi; Xiu-Dong Shi; Li-Wen Liang; Song Tan; Jie Wang; Bo Cai; Feng Xie; Jing-Feng Chen; Bin Wang; et al. (Journal of Environmental Management, 2025)

Vacuum carbothermal nitridation of secondary aluminum dross: Achieve efficient separation and targeted conversion of hazardous waste in one step - Yuanyuan Chen; Li Liu; Ronggang Sun; Kangming Wu; Liangliang Gu; Wei Liu; Hao Huang; Xiumin Chen; Chunsheng Zhang; Baoqiang Xu; Wenlong Jiang; Bin Yang (Journal of Environmental Chemical Engineering, 2025)

pH dual responsive electrospun fiber loading anthocyanin and nisin for food preservation and monitoring: Regulation in dynamic schiff base networks based on different oxidized sodium alginate - Jiaxin Li; Yiwen Bao; Qiao Jiang; Liang Wang; Ying He; Xu Si; Bin Li (Food Chemistry, 2025)

Electrospun oral fiber membranes for oral-derived postbiotic delivery: Physicochemical properties, antibacterial and cytoprotective effects - Yiwen Bao; Xu Si; Jiaxin Li; Qiao Jiang; Baoru Yang; Zhongxia Li; Bin Li (Food Chemistry, 2025)

Emission characteristics of full-volatility organic compounds from China's aluminum-products industry and their impacts on secondary organic aerosol and ozone potentials - Dongyang Wu; Qing'e Sha; Shan Jiang; Luyun Liu; Citao Zhang; Jialin Song; Junhao Xu; Haoqi Chen; Guanghui Li; Zhangmin Xiang; Bin Jiang; Zhuangmin Zhong; et al. (Environmental Research, 2025)

Amino-functionalized electrospinning separator tailors desolvation kinetics and Zn2+ transport for high-performance aqueous zinc-ion batteries - Zhuoqun Liu; Luxin Yu; Zhenying Zhang; Yang Feng; Bin Li; Yingqiao Jiang; Ningning Zhao; Jing Zhu; Lei Dai; Ling Wang; Zhangxing He (Chemical Engineering Journal, 2025)

Targeted-nanoformulation of cannabidiol attenuates endothelial injury and platelet hyperactivation for combating silicosis - Sirong Chang; Yue Sun; Wenyue Zhang; Yi Guo; Huning Zhang; Nan Li; Ran An; Mengsi Xiao; Siwei Zou; Na Zhang; Kai Wang; Anning Yang; et al. (Chemical Engineering Journal, 2025)

Effect of turbulence induced shear on continuous synthesis of imidazolium ionic liquid 1-butyl-3-methylimidazolium bromide ([BMIM]Br) in a high shear rate Taylor-Couette flow reactor - Rui Jiang; Guang Li; Bin Li; Yanhong Guo; Xiaogang Yang (Chemical Engineering Journal, 2025)

Lithium isotope systematics of South China granites unveil impacts of the asynchronous rollback of the paleo-Pacific plate on Li-mineralization - Qian-Ling Zhou; Yilin Xiao; Yang-Yang Wang; Jack G. Murphy; Xiaoyong Yang; Dong-Yong Li; Bin Li; Dong-Bo Tan; Shichu Zhao; Lingling Jiang; Haili Li (Chemical Geology, 2025)

PGC1α alleviates M1 macrophage polarization through dual regulation of succinate metabolism and TRAF5 expression to mitigate TLR4/NF-κB-driven inflammatory cascades and myocardial ischemia/reperfusion injury - Jiajie Leng; Zhenrui Cao; Letai Li; Dingheng Hu; Yuxiang Luo; Bin Tu; Xiaoying Cao; Rui Tao; Yingjiu Jiang; Hongtao Tie (Inflammation Research, 2025)

Fine-Tuning FuXi with CMA’s Reanalysis Data to Improve Forecasting - Zeping Zhang; Wei Han; Lei Chen; Hao Li; Lipeng Jiang; Bin Zhao (Journal of Meteorological Research, 2025)

Detection of mercury in single mammalian cells at attogram level by SC-ICP-MS - Xueyan Wang; Po Tang; Hao Liu; Yingying Li; Hua Guo; Pengyang Li; Deming Han; Nian Liu; Lihong Liu; Bin He; Ligang Hu; Guibin Jiang (Analytica Chimica Acta, 2025)

Glycemic status-dependent proteomic signatures of biological aging for health risk prediction - Jiang Li; Jie Li; Xiaoqin Xu; Yuefeng Yu; Wenqi Shen; Ying Sun; Yanqi Fu; Xiao Tan; Ningjian Wang; Yingli Lu; Bin Wang (GeroScience, 2025)

The connection between skeletal muscle and spinal canal membrane of Takifugu rubripes and its anatomical and physiological significance - Yang Song; Wen-Bin Jiang; Yu-Yu Xiong; Chun-Zhuo Shi; Hua-Xun Lai; Jing-Xian Sun; Lin-Lin Chen; Bo Liu; Yan-Yan Chi; Ji-Hang Li; Yi-Tong Sun; Xu-Hui Zhang; et al. (Frontiers in Marine Science, 2025)
Introduction The myodural bridge (MDB) is considered one of the circulatory dynamics of cerebrospinal fluid (CSF). Initially identified in the human neck, it has since been documented across diverse vertebrates, including fish with analogous “MDB-like” structures. The teleost Takifugu rubripes , which exhibits a high degree of genetic homology with humans, serves as an excellent model for such comparative studies. Investigating its MDB-like structure can therefore provide a morphological basis for elucidating the mechanism of CSF circulation and its evolution during the vertebrate land–water transition. Methods In this study, the morphology, development, and ultrastructure of MDB-like structure of Takifugu rubripes were explored. Three fresh adult T. rubripes were selected for gross anatomy. After incubation, 33 T. rubripes aged 13–120 days after hatching (dah) were fixed in 10% formalin solution. The samples aged 50–120 dah were further decalcified with EDTA for histological paraffin sectioning and Masson staining. Four cases aged 106 dah were fixed with 2.5% glutaraldehyde, two of which were observed by scanning electron microscopy, and two cases were observed by transmission electron microscopy. Results Through light microscopy and electron microscopy, the results of the current study is that there are three types of fiber connections (MDB-like) between skeletal muscle and the spinal canal membrane in T. rubripes : (1) The fibers from the myocomma attach to the spinal canal membrane; (2) The epimysium connects to the spinal canal membrane directly or connects to the spinal canal membrane through reticular, filamentous fibers, or fibers emitting from the perimysium; and (3) The fibers from the end of the muscle bundle stop at the spinal canal membrane. These connections mainly exist on the sides of each vertebral interspace and may function similarly to the MDB. Discussion Developmentally, “MDB-like” structures appeared in T. rubripes hatched at 18 dah, began to transmit force at 21 dah, and may have a positive correlation in development with the muscle and spinal canal membrane. This experiment provides developmental morphological information for comparative studies on the conservation and interspecies differences of MDB in evolution and provides informational support to explore the physiological function of MDB in humans.

Ocean density anomaly reconstruction using a physics-constrained dual-link operator learning network - Yu Zhang; Xuerong Cui; Juan Li; Lei Li; Bin Jiang (Ocean Engineering, 2025)

Different AOM processes driving the formation of carbonate crusts and nodules in the Okinawa Trough - Yucheng Zhou; Hong Cao; Zhilei Sun; Wei Geng; Chenhui Liu; Xilin Zhang; Cuiling Xu; Taiheng Lv; Shixing Li; Ye Chen; Xuejun Jiang; Dong Zhang; et al. (Marine and Petroleum Geology, 2025)

An upscaling approach for estimating field-level irrigation water use through the Budyko framework - Jingwen Zhang; Kaiyu Guan; Murugesu Sivapalan; Chongya Jiang; Ming Pan; Bin Peng; Wang Zhou; Trenton E. Franz; Xiaohong Chen; Kairong Lin; Zejun Li (Journal of Hydrology, 2025)

Evaluation of multimodel averaging approaches for ensembling evapotranspiration and yield simulations from maize models - Viveka Nand; Zhiming Qi; Liwang Ma; Matthew J. Helmers; Chandra A. Madramootoo; Ward N. Smith; Tiequan Zhang; Tobias K.D. Weber; Elizabeth Pattey; Ziwei Li; Jiaxin Wang; Virginia L. Jin; et al. (Journal of Hydrology, 2025)

The properties of alginate-cyclodextrin hybrid bubble hydrogel for ethylene gas encapsulation and storage - Zhanpeng Liu; Hongxin Jiang; Renyong Zhao; Xinwei Wang; Bin Zhang; Qiang Huang; Hao Li; Paul Van der Meeren (Food Research International, 2025)

Collagen peptides from Skipjack tuna (Katsuwonus pelamis) bones: Composition, characterization, and mechanism of high-fat diet-induced NAFLD amelioration - Yu-Lin Jiang; Shuang-Yi Zhang; Bin Wang; Yu-Hui Zeng; Li Xu; Chang-Feng Chi (Food Research International, 2025)

Preparation of pinolenic acid-embedded Lactiplantibacillus plantarum H6 Pickering emulsions stabilized with different concentrations of sodium alginate - Shengdong Bao; Lidan Guo; Jingjing Xuan; Liu Yang; Yue Li; Bin Jiang; Dayong Ren (Food Bioscience, 2025)

Observations and potential source regions of HFC-152a in southeastern China - Yulin Xu; Zhiwei Cao; Yonglong Lu; Pei Wang; Zhaoyang Wu; Xinyi Huang; Yunlei Zhang; Zhenjun Zhang; Xudong Jiang; Haojie Lei; Bin Sun; Jialong Li (Environmental Research, 2025)

Preparation of MUF/α-ZrP@MnHP@APP composite nanolayered flame retardant coating for application on expanded polystyrene (EPS) foam - Wei Zhang; Yifu Xiang; Wantong Jiang; Zhixin Yang; Linlin Zhang; Bin Li (Chemical Engineering Journal, 2025)

Pronounced thermodynamic inhibitory effect of clay-bound water on CO₂ hydrate formation: Underlying mechanisms and mitigation strategies towards CO₂ sequestration - Zhibo Jiang; Meixue Liu; Hao Xing; Qingping Li; Bin Wang; Lunxiang Zhang; Lei Yang; Shouwei Zhou; Yongchen Song (Chemical Engineering Journal, 2025)

Smart stimuli-responsive biomaterials for oral and maxillofacial tissue repair and regeneration - Yixuan Jiang; Xingrui Li; Zhuozhen Li; Hanyu Jiang; Bin Wang; Lin Xiang (Chemical Engineering Journal, 2025)

3D Magnetic resonance image denoising using nonlocal and nonconvex tensor train regularization - Li Wang; Yun Zhao; Liang Zhao; Bin Jiang; Qinling Xia (Medical & Biological Engineering & Computing, 2025)

Sex differences in brain network functional connectivity and their association with gene expression profiles in major depressive disorder: a REST-meta-MDD project-based study - Jiang Wang; Chengfeng Chen; Shiying Wang; Yuan Liu; Peiying Li; Bin Zhang (Brain Imaging and Behavior, 2025)

Real-time tracker of chicken for poultry based on attention mechanism-enhanced YOLO-Chicken algorithm - Daqi Jiang; Hong Wang; Tan Li; Mohamed Amin Gouda; Bin Zhou (Computers and Electronics in Agriculture, 2025)

2.2-billion-year-old KREEP-rich volcanism on the Moon - Mu-Han Yang; Qian W.L. Zhang; Qiu-Li Li; Ross N. Mitchell; Richard W. Carlson; Zhu-Yin Chu; Yu Liu; Yi Chen; Shun Guo; Ding-Shuai Xue; Bin Su; Xu Tang; et al. (Science Bulletin, 2025)

UV-guided separation of polyacetylenol glycosides from the edible roots of Codonopsis pilosula and their anti-inflammatory activity - Xilan Jiang; Lun Wang; Yao Chen; Yi Zuo; Mengdan Liu; Bin Chen; Dong Fu; Yujiao He; Mingkui Wang; Ting Shen; Fu Li (Phytochemistry, 2025)

Interfacial electron modulation of FeCo LDH@CoS heterojunction for efficient oxygen evolution reaction - Zhen Guan; Hengzhong Chen; Bin Chen; Lingchen Kong; Zhou Shi; Yu Zhong; Wenjie Li; Wencan Qian; Rui Zhang; Jiang Wu; Zaiguo Fu (Journal of Environmental Chemical Engineering, 2025)

Heteroatom-doped, vinegar residue-derived fluorine/chlorine Co-doped vertical graphene-supported carbon quantum dots as high-efficiency all-carbon electrodes for water electrolysis hydrogen production - Han Yin; Yang An; Chunyu Li; Yu Yan; Rui Su; Chunyang Wan; Bin Jiang; Shanshan Bai; Firdoz Shaik (Journal of Environmental Chemical Engineering, 2025)

Effect of pulsed electric field pre-treatment combined with static magnetic field freezing on strawberry quality - Hanqian Jiang; Dongnan Li; Dingchen Shao; Xu Si; Bin Li (Innovative Food Science & Emerging Technologies, 2025)

Frying characteristics of beef tallow as a potential alternative for intermittent deep-fat frying - Fenfen Lei; Meiyu Zheng; Tianyu Zhang; Timothy J. Tse; Martin J.T. Reaney; Shu Wang; Xiaoming Jiang; Bin Li; Zhigang Hu; Dongping He; Sihong Zhang; Qinfeng Zhang; et al. (Food Chemistry, 2025)

Dietary biotin facilitates collagen deposition and myofiber growth and development, improving muscle chewiness and hardness in grass carp (Ctenopharyngodon idella) - Yang Yang; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Sheng-Yao Kuang; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng; Xiao-Qiu Zhou (Food Bioscience, 2025)

A new strategy for the preparation of long-term stable “Capillary foam” from egg white protein microgel particles - Xiaorui Zhou; Ying Jiang; Jing Li; Bin Li; Fuchao Zhan (Food Hydrocolloids, 2025)

Unraveling the absorption properties and driving mechanisms of atmospheric brown carbon in coastal air masses - Siyuan Li; Dantong Liu; Yangzhou Wu; Kang Hu; Shitong Zhao; Xiaotong Jiang; Ping Tian; Bin Xu (Environmental Pollution, 2025)

Dual regulation of surface electronegativity and interlayer structural feature in fluorinated COFs for efficient gold recovery - Xiaoning Zhan; Yucheng Jin; Bin Han; Dongdong Qi; Chunli Li; Rong Jiang; Xiaonan Pang; Guoqing Xu; Mingyue Wang; Qi Zhang; Jianzhuang Jiang (Chemical Engineering Journal, 2025)

Revisiting the role of solution aggregation in CO₂ desorption: Insights of mass transfer and energy consumption in phase-change absorbents - Bin Xu; Xiaoyi Gao; Wufeng Jiang; Xi Tang; Xiaoshan Li; Cong Luo; Fan Wu; Liqi Zhang (Chemical Engineering Journal, 2025)

Nitrate‐iron co-modification nickel hydroxide with strong built-in electric field for oxygen evolution - Xin-Jie Tian; Wen Jiang; Yue-Ming Li; Yanbin Qi; Xin Wen; Chen Zhang; Denghao Ouyang; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2025)

Polyphenol-synthesized nanoparticles with ALDH3A1 delivery ability for activating estrogen signaling for diabetic wound healing - Xiaoxuan Ma; Yiqiong Liu; Jingsi Jiang; Yi Ru; Ying Luo; Jiankun Song; Zhan Zhang; Ying Zhang; Dan Yang; Haotian Xu; Haiqing Dong; Yongyong Li; et al. (Chemical Engineering Journal, 2025)

Catalytic role of biochar surface groups in phenol formation from lignin pyrolysis: Experimental and DFT insights - Ding Jiang; Hongping Li; Xiaoxue Cheng; Pietro Bartocci; Arman Amani Babadi; Minggao Xu; Yang Pan; Bin Cao; Osvalda Senneca; Shuang Wang (Chemical Engineering Journal, 2025)

High-efficiency room-temperature phosphorescence with long lifetime and tunable color based on intramolecular charge transfer - Jiang Liu; Wensheng Xu; Li Gao; Bin Li; Jiayi Zhang; Mengfei Zong; Yang Li; Ligong Chen; Xilong Yan; Bowei Wang (Chemical Engineering Journal, 2025)

Understanding diurnal variability in organic matter processing by microalgal-bacterial granular sludge in lake water remediation - Changqing Chen; Yuting Shi; Bingheng Chen; Anjie Li; Quan Meng; Yu Jiang; Bin Ji (Bioresource Technology, 2025)

Effects of uniform rocking motion on VLPO regional GABA/Glu contents and sleep in rats - Guang-yao Luo; Xian Jiang; Yu-lian Jin; Feng-ying Li; Ti-peng Wang; Bin Wen; Yao-wen Zhang (Sleep and Biological Rhythms, 2025)
Recent research has found that rocking promotes sleep in mice, but there is a lack of information on whether rocking also promotes sleep in rats and the neurophysiological mechanisms involved. The purpose of the present experiment was to elucidate the effects of rocking on sleep–wake staging in rats. EEG recordings were made on a platform with a frequency of 1.5 HZ and a displacement of 20 mm for 12 h of rocking and 12 h of stillness in rats, and the proportion of each sleep phase in the 24-h EEG was analyzed. The contents of glutamate and GABA in the VLPO region of rats were measured during shaking. The results showed that at a shaking frequency of 1.5 HZ, the proportion of non-rapid eye movement (REM) sleep increased and wakefulness decreased in the first 12 h of the rats, and there was no significant effect in the last 12 h. In the experiments, GABA levels in the VLPO region of awake rats gradually increased after the onset of uniform rocking exercise and began to decrease after reaching a peak at 20 min. After 40 min, GABA levels leveled off and did not change significantly above 60 min, but had no effect on glutamate levels. These results suggest that 1.5 HZ of rocking promotes NREM sleep and reduces wakefulness in rats, and that rocking may be related to GABAergic neurons in promoting sleep in rats.

Bacterial Extracellular Vesicles: Emerging Regulators in the Gut–Organ Axis and Prospective Biomedical Applications - Bingqi Zhang; Mingyan Liu; Lingxin Jiang; Ziqiu Chen; Wei Tian; Kaidi Li; Bin Yu; Wenlan Zhang; Sirui Li; Yuzhu Zhou; Huhu Li; Yilan Xu; et al. (Current Microbiology, 2025)

Efficient permanganate activation under UV 222 nm irradiation for enhanced pollutant abatement - Haochen Zhang; Peng Su; Maoju Jiang; Chenlong Liu; Qixiao Lv; Wenqi Li; Xiangyang Hou; Junhui Zhou; Shuo Li; Bin Zhang; Bei Zhang; Jun Ma; et al. (Water Research, 2025)

Lipid droplet clearance inhibits esophageal cancer growth via metabolic reprogramming - Yan Pu; Yi Wan; Yuhua Fu; Kai Li; Yijiao Chen; Yunzhi Wang; Bin Li; Lingling Li; Zhaoyu Qin; Jingyan Xu; Dongxian Jiang; Yan Li; et al. (Science Bulletin, 2025)

Effect of magnetic field treatment on the softening of strawberries during cold storage - Yiming Zhang; Wanqi Hong; Hanqian Jiang; Dingchen Shao; Xu Si; Yanqun Wang; Dongnan Li; Bin Li (Postharvest Biology and Technology, 2025)

Influences of nutrients on summer algal bloom in the Changjiang plume revealed by high-resolution profiles - Chen Zeng; Dewang Li; Bin Wang; Haiyan Jin; Ruijie Ye; Qianwen Sun; Zhibing Jiang; Yixuan Tao; Xiao Ma; Qinyu Liu; Hongliang Li; Jianfang Chen (Marine Environmental Research, 2025)

Microbial diversity and interaction networks in polar Sediments: Insights from the Circum-Antarctic, Antarctic Peninsula and Arctic - Zhengang Liu; Furong Cao; Jiyuan Wan; Xing Chen; Bin Kong; Dong Li; Xiao-Hua Zhang; Yong Jiang; Xiaochong Shi (Marine Environmental Research, 2025)

Multi-objective optimal Bi-level scheduling of hybrid mobile-stationary energy storage systems for flexible distribution network - Bo Yang; Guo Zhou; Shuai Zhou; Yuanweiji Hu; Bin He; Zhengxun Guo; Zhibiao Luo; Hongbiao Li; Dengke Gao; Jingbo Wang; Lin Jiang (Journal of Cleaner Production, 2025)

Novel mass transfer kinetics model for predicting phase separation behavior in CO2 capture with energy-saving biphasic absorbents - Bin Xu; Xiaoyi Gao; Wufeng Jiang; Xi Tang; Xiaoshan Li; Cong Luo; Fan Wu; Liqi Zhang (Journal of Cleaner Production, 2025)

Effect of anticyclonic eddies on the production and emission of marine dimethylsulfide in the northern South China Sea - Jin-Wei Wu; Feng Xu; Shi-Bo Yan; Gao-Bin Xu; Yu-Cheng Jiang; Xiao-Ran Li; Xing Zhai; Li-Min Zhou; Hong-Hai Zhang; Zhao-Hui Chen (Global and Planetary Change, 2025)

Coffee mitigated cognitive impairments in sleep-deprived mice by regulating circadian rhythm, inflammation, oxidative stress, and intestinal ecology - Hui-Bin Jiang; Fen-Fen Wei; Wen-Ting Li; Zi-Han Lin; Chuang Zhu; Yan Wu; Ying Wang; Li-Hua Song (Food Bioscience, 2025)

Piezo1-mediated iron overload in the oxidative damage to the liver in hypobaric hypoxia and the alleviation by selenium synthesized by Lactobacillus rhamnosus SHA113 - Guanwen Liu; Hongfang Lv; Yinghui Li; Qiongyao Xu; Xiaoya Shang; Dongyan Shao; Chunmei Jiang; Bin Jia; Dachuan Yin; Junling Shi (Food Bioscience, 2025)

Phase separation prediction modeling and structure-activity relationship of CO2 capture by biphasic amine absorbents based on phase separation load - Xiaoyi Gao; Bin Xu; Wufeng Jiang; Xi Tang; Muyi Li; Fan Wu; Cong Luo; Xiaoshan Li; Liqi Zhang (Chemical Engineering Journal, 2025)

Rationally designed and facilely constructed CoFe2O4@SiO2 yolk@shell heterostructure spherical jars as interlayer achieve high-performance Li S batteries via “3 + 1” modal anchoring & catalyzing coupled with microreactor - Yingying Bao; Bin Yue; Lin Li; Shan Jiang; Hong Shao; Yunrui Xie; Qianli Ma; Wensheng Yu; Jinxian Wang; Xiangting Dong (Chemical Engineering Journal, 2025)

Research on the path of atmospheric pollutants and greenhouse gas cooperative control in megacities - A case study of Chengdu - Zihang Zhou; Chengwei Lu; Ye Deng; Qinwen Tan; Xia Jiang; Bin Zhao; Fei Fang; Hefan Liu; Danlin Song; Xiaoling Zhou; Xuan Liu; Xin Zhang; et al. (Atmospheric Pollution Research, 2025)

Transcriptome and Metabolome Conjoint Analysis Revealed that PaGLK Affects Photosynthesis and Composition of Root Exudates in Poplar - Xiang-dong Bai; Yu Zheng; Li Cao; Wei Wang; Jing Jiang; Qi-bin Yu; Chuan-ping Yang; Gui-feng Liu (Plant Molecular Biology Reporter, 2025)

lncRNA PVT1 regulates chondrocyte proliferation and apoptosis through the glycolysis process mediated by miR-552-3p/PKM2 to promote osteoarthritis - Demiao Zeng; Bin Li; Longhua Zhang; Guodong Zhang; Xiangjia Yan; Mengshi Huang; Jun Jiang; Zenggao Han (In Vitro Cellular & Developmental Biology - Animal, 2025)

Prediction of yellow flesh peach firmness using a novel device and data augmentation acoustic vibration multi-domain images array Swin Transformer (DA-AVMDIA-SwinT) - Chen Nan; Liu Zhi; Le Dexiang; Lai Qingrong; Jiang Bingnian; Li Bin; Wu Jian; Song Yunfeng; Liu Yande (Computers and Electronics in Agriculture, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Quantitative modeling of substrate velocity effects on deposition efficiency and precursor consumption in spatial ALD - Geng Ma; Zhaojie Wang; Yuan Gao; Zoushuang Li; Xuewei Jiang; Yanwei Wen; Bin Shan; Fan Yang; Rong Chen (Chemical Engineering Journal, 2025)

Numerical investigations of the micro-sized lunar dust deposition in the human truncated whole lung airways - Lei Jiang; Zhangyu Liu; Hao Jing; Yuan Xue; Bin Wu; Yinghui Li; Honglei Ma; Xinxing He; Jintao Wang; Xinguang Cui (Building and Environment, 2025)

Overexpression of MEOX2 inhibits breast cancer cell metastasis by targeting oxidative stress-induced RGS5 - Yujun Tang; Jie Luo; Bin Jiang; Jian Deng; Jiehua Li; Liuqing Qin (In Vitro Cellular & Developmental Biology - Animal, 2025)

Peripheral Blood miRNA Expression in Patients with Essential Hypertension in the Han Chinese Population in Hefei, China - Bin Cheng; Ronglu Yang; Hui Xu; Li Wang; Nan Jiang; Tingting Song; Changwu Dong (Biochemical Genetics, 2025)
Primary hypertension is a significant risk factor for cardiovascular diseases. However, the pathogenesis of primary hypertension involves multiple biological processes, including the nervous system, circulatory system, endocrine system, and more. Despite extensive research, there is no clear understanding of the regulatory mechanism underlying its pathogenesis. In recent years, miRNAs have gained attention as a regulatory factor capable of modulating the expression of related molecules through gene silencing. Therefore, exploring differentially expressed miRNAs in patients with essential hypertension (EH) may offer a novel approach for future diagnosis and treatment of EH. This study included a total of twenty Han Chinese population samples from Hefei, China. The samples consisted of 10 healthy individuals and 10 patients with EH. Statistical analysis was conducted to analyze the general information of the two-sample groups. High-throughput sequencing and base identification were performed to obtain the original sequencing sequences. These sequences were then annotated using various databases including Rfam, cDNA sequences, species repetitive sequences library, and miRBase database. The number of miRNA species contained in the samples was measured. Next, TPM values were calculated to determine the expression level of each miRNA. The bioinformatics of the differentiated miRNAs were analyzed using the OECloud tool, and RPM values were calculated. Furthermore, the reliability of the expression was analyzed by calculating the area under the Roc curve using the OECloud tools. Statistical analysis revealed no significant differences between the two samples in terms of age distribution, gender composition, smoking history, and alcohol consumption history ( P > 0.05). However, there was a notable presence of family genetic history and high BMI in the EH population ( P

Plasma technology modifies the surface properties of desalted duck egg white and applied as a novel oleogel stabilizer - Xiaohan Dai; Bo Song; Xiaoqing Xiang; Bin Jiang; Dongmei Li; Chunhong Liu; Zhibiao Feng (Food Chemistry, 2025)

Comprehensive insights into the mechanism of flavor formation in mandarin fish (Siniperca chuatsi) with inoculated fermentation - Ke-Xun Guo; Bin Hu; Yi Jiang; Zeng-Yong Li; Jun Qi; Man-Man Yu (Food Chemistry, 2025)

Alveolar surfactant-mimicking inhaled biomimetic nanovaccine with alveolar macrophage-targeting property potentiates anti-mpox immunity - Bin Li; Jiamei Wang; Judun Zheng; Wei Wang; Lingjie He; Yan Yan; Xinting Fu; Xingjie You; Man Gu; Han Duan; Yue Jia; Qin Gu; et al. (Chemical Engineering Journal, 2025)

Bacterial-targeting liposomes for synergistic nitric oxide/methicillin therapy in MRSA-infected osteomyelitis - Kai Lv; Zhen Wang; Wenjun He; Zijing Feng; Hui Xing; Yuanfang Jiang; Yingtong Lu; Jingjie Shang; Bin Guo; Hao Xu; Guowei Li; Bo Ning; et al. (Chemical Engineering Journal, 2025)

Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia-bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2025)

Suppressing the progression of bladder cancer using cyclovirobuxine D based on network pharmacology and bioinformatics approaches - Ke Gao; Hanbing Jiang; Chao Zhang; Lin Li; Yuhong Qi; Nan Yang; Xiaoshun Li; Yongshun Wang; Bin Wu; Qiuju Shao; Guojun Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

A nutritional strategy for improving sub-adult grass carp (Ctenopharyngodon idella) flesh flavor: The role of α-lipoic acid in regulating muscle nucleotide and fatty acid metabolism - Yang Zhang; Pei Wu; Wei-Dan Jiang; Yang Liu; Yao-Bin Ma; Sheng-Yao Kuang; Shu-Wei Li; Ling Tang; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2025)

Eucalyptus oil: A promising anticoccidial agent with multifaceted protective effects - Jun-jie Huang; Jie-yu Shi; Kai-yuan Li; He Zheng; Wen-hai Zhang; Xiao-bin Yi; Ming-jiang Liu; Ruo-nan Bo; Jin-gui Li (Veterinary Parasitology, 2025)

Influencing factors and risk assessment of polycyclic aromatic hydrocarbons in the sediments of Beilianchi Lake, China - Xiaohua Ma; Changchun Huang; Yanyan Li; Shuaidong Li; Quanliang Jiang; Can Zhang; Bin Xue; Hao Yang (Science of The Total Environment, 2025)

Discovery of structurally intriguing diterpenoids as anti-neuroinflammatory agents from mangrove plant Excoecaria agallocha L. via inhibiting macrophage polarization and inflammasome - Jun-Yi Li; Ming-Bin Chen; Ting-Ting Fu; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Jing Zhou; Yong Rao; Zhong-Ping Jiang; Ling Huang (Phytochemistry, 2025)

Pan-genome and haplotype map of cassava cultivars and wild ancestors provide insights into its adaptive evolution and domestication - Zhiqiang Xia; Zhenglin Du; Xincheng Zhou; Sirong Jiang; Tingting Zhu; Le Wang; Fei Chen; Luiz Carvalho; Meiling Zou; Luis Augusto Becerra Lopez-Lavalle; Xiaofei Zhang; Liangye Xu; et al. (Molecular Plant, 2025)

Enhancing regional-scale simulation accuracy of paddy runoff by coupling water balance models with remote sensing - Housheng Wang; Rui Ren; Xiang Gao; Huazhan Zhang; Wei Jiang; Xuerong Lang; Xian Hu; Xiaosan Jiang; Kun Zhao; Bin Zhang; Zhipeng Liu; Wenjuan Zheng; et al. (Journal of Hydrology, 2025)

Effects of multiple novel bisphenol S analogs on adipogenesis in 3T3-L1 cells - Zhendong Sun; Shengnan Zhang; Jiefeng Liang; Chuanhai Li; Xiaoxi Yang; Qian S. Liu; Qunfang Zhou; Jianbo Shi; Bin Zhao; Guibin Jiang (Journal of Hazardous Materials, 2025)

Regional transport characteristics of PM2.5 pollution events in Beijing during 2018–2021 - Dejia Yin; Qian Song; Yuanxi Guo; Yueqi Jiang; Zhaoxin Dong; Bin Zhao; Shuxiao Wang; Da Gao; Xing Chang; Haotian Zheng; Shengyue Li; Yunting Li; et al. (Journal of Environmental Sciences, 2025)

Chemical property, bioactive constituent and volatile compound changes of beef tallow during an improved flavor-retaining refining approach - Li Zhou; Meiyu Zheng; Tianyu Zhang; Shu Wang; Xiaoming Jiang; Bin Li; Zhigang Hu; Timothy J. Tse; Martin J.T. Reaney; Qiangsheng Nie; Dongping He; Chuanrong Hu; et al. (Food Chemistry, 2025)

Circulating MicroRNAs in association with urinary arsenic: A community-based multi-center study in China - Wending Li; Zhaoyang Li; Jixuan Ma; Xuedan Xu; Bin Wang; Pinpin Long; Qin Jiang; Yutong You; Jingli Qu; Yufei Wang; Yaxin Wang; Meian He; et al. (Environmental Research, 2025)

Visible light can also efficiently activate chlorine dioxide for the abatement of micropollutants - Bin Zhang; Zhiyun Long; Ge Zeng; Wenjun Zhang; Peng Su; Xiangyang Hou; Qixiao Lv; Wenqi Li; Jin Jiang; Zihao Wu; Tao Yang (Chemical Engineering Journal, 2025)

Energy characteristics of coal damage deformation under triaxial compression - Yao Zhang; Bobo Li; Bin Wang; Chonghong Ren; Jiang Xu (Bulletin of Engineering Geology and the Environment, 2025)

Discovery of phenoxazine congeners as novel α-glucosidase inhibitors and identification of their biosynthetic gene cluster from Streptomyces sp. CB00316 - Lin Jiang; Pingzhi Huang; Aijie Li; Bin Fen; Yani Zhong; Caijun Tang; Guangling Wu; Wenlei Wang; Yuhan Chen; Jian Pan; Genyun Tang; Hong Pu (Archives of Microbiology, 2025)

Record High Temperatures in the Ocean in 2024 - Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Huai-Min Zhang; Andrea Storto; Karina Von Schuckmann; Yuying Pan; Yujing Zhu; Michael E. Mann; Jiang Zhu; Fan Wang; et al. (Advances in Atmospheric Sciences, 2025)
Heating in the ocean has continued in 2024 in response to increased greenhouse gas concentrations in the atmosphere, despite the transition from an El Niño to neutral conditions. In 2024, both global sea surface temperature (SST) and upper 2000 m ocean heat content (OHC) reached unprecedented highs in the historical record. The 0–2000 m OHC in 2024 exceeded that of 2023 by 16 ± 8 ZJ (1 Zetta Joules = 10 21 Joules, with a 95% confidence interval) (IAP/CAS data), which is confirmed by two other data products: 18 ± 7 ZJ (CIGAR-RT reanalysis data) and 40 ± 31 ZJ (Copernicus Marine data, updated to November 2024). The Indian Ocean, tropical Atlantic, Mediterranean Sea, North Atlantic, North Pacific, and Southern Ocean also experienced record-high OHC values in 2024. The global SST continued its record-high values from 2023 into the first half of 2024, and declined slightly in the second half of 2024, resulting in an annual mean of 0.61°C ± 0.02°C (IAP/CAS data) above the 1981–2010 baseline, slightly higher than the 2023 annual-mean value (by 0.07°C ± 0.02°C for IAP/CAS, 0.05°C ± 0.02°C for NOAA/NCEI, and 0.06°C ± 0.11°C for Copernicus Marine). The record-high values of 2024 SST and OHC continue to indicate unabated trends of global heating.

Underwater Time Delay Estimation Based on Meta-DnCNN with Frequency-Sliding Generalized Cross-Correlation - Meiqi Ji; Xuerong Cui; Juan Li; Lei Li; Bin Jiang (Journal of Marine Science and Engineering, 2025)
In underwater signal processing, accurate time delay estimation (TDE) is of crucial importance for ensuring the reliability of data transmission. However, the complex propagation of sound waves and strong noise interference in the underwater environment make this task extremely challenging. Especially under the condition of low signal-to-noise ratio (SNR), the existing methods based on cross-correlation and deep learning struggle to meet requirements. Aiming at this core issue, this paper proposed an innovative solution. Firstly, a multi-sub-window reconstruction is performed on the frequency-sliding generalized colorboxpinkcross-correlation (FS-GCC) matrix between signals to capture the time delay characteristics from different frequency bands and conduct the enhancement and extraction of features. Then, the grayscale image corresponding to the generated FS-GCC matrix is used, and the multi-level noise features are extracted by the multi-layer convolution of denoising convolutional neural network (DnCNN), effectively suppressing the noise and improving the estimation accuracy. Finally, the model-agnostic meta-learning (MAML) framework is introduced. Through training tasks under various SNR conditions, the model is enabled to possess the ability to quickly adapt to new environments, and it can achieve the desired estimation accuracy even when the number of underwater training samples is limited. Simulation validation was conducted under the NOF and NCS underwater acoustic channels, and results demonstrate that our proposed approach exhibits lower estimation errors and greater stability compared with existing methods under the same conditions. This method enhances the practicality and robustness of the model in complex underwater environments, providing strong support for the efficient and stable operation of underwater sensor networks.

Self-assembled nanoparticle vaccine based on the grass carp ferritin remarkably enhance the protective immune responses against GCRV type II infection - Fei-Fan Xu; Zhu-Yang Deng; Jing-Kai Li; Le-Yang Chen; Yong-Qi Liu; Hai-Feng Jiang; Bin Zhu (Aquaculture, 2025)

New perspectives on the immune regulatory role of dietary silymarin in the intestines of juvenile grass carp (Ctenopharyngodon idella) - Feng Jia; Li Wei; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Grand challenges of mitigating O3-related mortality in China by 2060 - Yueqi Jiang; Yisheng Sun; Shengyue Li; Dejia Yin; Zhaoxin Dong; Haotian Zheng; Bin Zhao; Shuxiao Wang (Science Bulletin, 2025)

Crystal facet effect of the support in Ni/La2O2CO3 catalysts for toluene steam reforming - Shou-Yong Jiang; Yang Du; Yun-Jie Li; Zhi-Bin Wang; Hong-Xia Fan; Shou-Dong Xu; Zhen-Yi Du; M.D. Isobaev; Wen-Ying Li (Fuel, 2025)

Provincial anthropogenic emission inventory of carbonyl sulfide (COS) in China from 2015 to 2021 - Yunhao Jiang; Bin Chen; Shaoqiang Wang; Tingyu Li; Shiliang Chen; Lunche Wang; Lizhe Wang (Journal of Geographical Sciences, 2025)

Reproductive and detoxifying responses of Panonychus citri (Acari: Tetranychidae) to sulfoxaflor stress - Tianrong Xin; Xinyan Kong; Chenyu Jiang; Zhenzhen Li; Zhiwen Zou; Bin Xia (Crop Protection, 2025)

Advances in tellurium recovery and purification: A comprehensive review of separation methods and emerging technologies - Huiming Zhang; Zhichao Li; Yichao Yang; Guozheng Zha; Baoqiang Xu; Dachun Liu; Bin Yang; Wenlong Jiang (Resources, Conservation and Recycling, 2025)

Recovery of platinum group metals from spent automotive catalysts: Review of conventional techniques and vacuum metallurgy - Bo Xv; Zhichao Li; Guozheng Zha; Dachun Liu; Bin Yang; Wenlong Jiang (Resources, Conservation and Recycling, 2025)

Strategic approach to reduce environmental damage by CO2 and air pollution based on Energy-Material-Emission Nexus: Insights from Beijing - Daiwei Ouyang; Qingru Wu; Shuxiao Wang; Kaiyun Liu; Shengyue Li; Yao Li; Xinyun Chen; Kun Wang; Wenhao Wu; Zhaoxin Dong; Yueqi Jiang; Yanning Zhang; et al. (Resources, Conservation and Recycling, 2025)

The consequence distance of liquid ammonia release from a pipeline in complex terrain - Lin Teng; Kangkang Wang; Bin Liu; Weidong Li; Pengbo Yin; Zhenchao Li; Xin Huang; Yu Luo; Lilong Jiang (Process Safety and Environmental Protection, 2025)

Two new compounds from Pentadesma butyracea and their biological activities - Yue Yang; Li Hua Gong; Fu Hua Peng; Tao Jiang; Jian Guo Hu; Hong Dong Liu; Bin Li; Yin Xia Yang; Jing Ying Peng; Xue Mei Gao (Phytochemistry Letters, 2025)

Colloids fractionation and characterization of arsenic (As) and dissolved organic matter (DOM) in surface water around a closed arsenic mine - Zhenzhen Yu; Chaoyang Wei; Fen Yang; Zhiying Li; Bin Jiang; Weijie Dai; Changyuan Tang; Yizhang Zhang (Journal of Hazardous Materials, 2025)

In-situ constructed ZnAl2O4/A-MoS2 Z-scheme heterojunction for visible-light-thermo cascade catalytic CO2 cycloaddition - Congcong Zhang; Bin Jiang; Runjia Mou; Haochen Shen; Qi Zhou; Longfei Zhang; Jingshuai Li; Na Yang; Luhong Zhang (Journal of Environmental Chemical Engineering, 2025)

Trace phospholipid and fatty acid differences between dairy and plant-based milk products by 1H and 31P NMR spectroscopy combined with multivariate statistical analysis - Tongtong Wang; Gang Chen; Sijia Tan; Liang Li; Bin Jiang; Dan Wang; Qingyi Liu (Food Chemistry, 2025)

Optimization of the quality of sea buckthorn juice by enzymatic digestion and inoculation sequence - Jianfeng Wang; Yu Zhang; Bin Zhang; Yuqi Han; Jixin Li; Bo Zhang; Yumei Jiang (Food Chemistry, 2025)

Purification and identification of antioxidant activity and angiotensin converting enzyme (ACE) inhibitory activity peptide of peanut protein based on ultrafiltration (UF) membrane separation - Bin Cao; Qi Li; Zhenyu Chen; Xiuren Tang; Hock Eng Khoo; Tiemin Jiang; Yueming Jiang; Jing Li; Xinhong Dong (Food Bioscience, 2025)

Dietary pyridoxine promoted muscle protein deposition relating to PI3K/AKT/TOR pathway and the ubiquitin proteasome system in grass carp (Ctenopharyngodon idella) - Li-Fu Gong; Xiao-Qiu Zhou; Lin Feng; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Fa-Li Wu; Yang Liu (Food Bioscience, 2025)

A review of antibiotic resistance genes in major river basins in China: Distribution, drivers, and risk - Wenjia Li; Bin Wang; Tao Wang; Jiang Li; Junmin Qi; Jiwei Luo; Ting Zhang; Xiaoyi Xu; Li'an Hou (Environmental Pollution, 2025)

Compositional complexity of heterogeneous impact glasses in lunar soils: significance and pitfalls - Qian W. L. Zhang; Bin Su; Pierre Lanari; Jia-Hui Liu; Jia-Long Hao; Yu Liu; Liu-Yang Chen; Di Zhang; Jiang-Yan Yuan; Juan Wang; Xian-Hua Li; Qiu-Li Li (Contributions to Mineralogy and Petrology, 2025)
Heterogeneous impact glass beads are abundant in lunar soils and have been extensively used to study the geological processes that shaped the Moon’s surface. In this study, we examine the compositional complexity of three heterogeneous glass beads containing undigested zirconolite and zircon, using EPMA, Nano-SIMS mapping, and SIMS U–Pb isotope analyses. The undigested zircon and zirconolite crystals document three key volcanic events in the lunar history: at ~ 4.31 Ga the formation of alkali-suite rocks from the highlands, and at ~ 3.92 Ga, and ~ 2.04 Ga mare basalts, indicating that the U–Pb system in these zirconium-bearing crystals remains undisturbed during the ultra-high-temperature, short-duration impact melting events. EPMA and Nano-SIMS mapping reveal significant compositional inhomogeneity in the glass matrices, which complicates accurate provenance determination based on in-situ analysis. Bulk composition calculated from quantitative maps, however, provides a more reliable reference for inferring the origins of these beads. The high proportions of common Pb in the heterogeneous glass matrices, originating from diffusion-controlled processes during partial melting of impact involved minerals, introduce substantial uncertainties in U–Pb dating, complicating the interpretation of impact event ages. These findings highlight the challenges of U–Pb dating in heterogeneous glass beads and provide new insights into the preservation of pristine age information in lunar impact materials.

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Large language models for diabetes training: a prospective study - Haoxuan Li; Zehua Jiang; Zhouyu Guan; Yuqian Bao; Yuexing Liu; Tingting Hu; Jiajia Li; Ruhan Liu; Liang Wu; Di Cheng; Hongwei Ji; Yong Wang; et al. (Science Bulletin, 2025)

The Arabidopsis heterotrimeric G protein α subunit binds to and inhibits the inward rectifying potassium channel KAT1 - Jiang-Fan Guo; Hui Zhou; Zhuo-Ran Hu; Ya-Lan Yang; Wen-Bin Wang; Yan-Ru Zhang; Xue Li; Nuerkaimaier Mulati; Ying-Xin Li; Lu Wu; Yu Long; Jun-Min He (Plant Science, 2025)

RNA interference-mediated silencing of GNBP2 reduces the immunity of stored pest Tribolium castaneum against bacteria - Jingxiu Bi; Xiangjun Ma; Yuying Jiang; Pingxiang Liu; Rui Gao; Tong Zhao; Xuexia Yuan; Haining Hao; Bin Li; Yutao Wang (Pesticide Biochemistry and Physiology, 2025)

Chloroplast state transitions modulate nuclear genome stability via cytokinin signaling in Arabidopsis - Yajun Zeng; Sujuan Duan; Yawen Wang; Zhifeng Zheng; Zeyi Wu; Meihui Shi; Manchun Wang; Lan Jiang; Xue Li; Hong-Bin Wang; Hong-Lei Jin (Molecular Plant, 2025)

Extractable organic matter from PM2.5 inhibits cardiomyocyte differentiation via AHR-mediated m6A RNA methylation - Xiaoxiao Li; Shoushuang Zhao; Mengya Zhai; Yuqin Ma; Bin Jiang; Yan Jiang; Tao Chen (Journal of Hazardous Materials, 2025)

Mitigating LPS-induced stress in Chinese mitten crab (Eriocheir sinensis) with P4’ peptide-bearing Bacillus subtilis - Chao-Fan He; Ye Yang; Yong Liu; Xiang Liu; Xiang-Fei Li; Guang-Zhen Jiang; Wen-Bin Liu (Fish & Shellfish Immunology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Enhancement of OH– ion transport by the built-in electric field in NiCoCu-LDH@CoSe2 heterostructure for high-rate and long-cycle supercapacitors - Yuxin Sun; Bin Cai; Liying Wang; Xijia Yang; Xuesong Li; Yi Jiang; Xiaohan Zhang; Wei Lü (Chemical Engineering Journal, 2025)

The structure–activity relationship for CO2 absorption heat of chain diamines: Effects of amino types, methyl/ethyl groups, and chain lengths - Xi Tang; Ge Gao; Wufeng Jiang; Bin Xu; Fan Wu; Cong Luo; Xiaoshan Li; Liqi Zhang (Chemical Engineering Journal, 2025)

Broad-spectrum anti-inflammatory and antioxidant therapy of inflammatory-storm actuated diseases via programmable self-derived cryo-dead neutrophils - Bin Li; Qiuxia Gao; Yunxia Wu; Hongyi Lei; Shengchao Ma; Wei Wang; Hang Sun; Weifeng Ma; Judun Zheng; Chenchen Yuan; Yunlong Zhang; Yue Jia; et al. (Chemical Engineering Journal, 2025)

A “rigid-flexible” iontronic pressure sensor with high sensitivity and wide response range for hand dysfunction rehabilitation training - Ximeng Zhao; Mengjuan Yang; Fangquan Li; Long Xu; Yan Jiang; Xu Jin; Huijie Zhang; Gaoling Jin; Zheng Zhang; Bin Wang; Ying Wang; Xiuqin Zhang (Chemical Engineering Journal, 2025)

Changes in root-associated bacterial communities across growth stages of salt-tolerant and salt-sensitive rice grown in coastal saline-alkali soils - Qing Li; Jihui Jiang; Haoyang Cheng; Bin Zhang; Yang Zhang; Jian Hu (World Journal of Microbiology and Biotechnology, 2025)

Differences in plant responses to nitrogen addition between the central and edge populations of invasive Galinsoga quadriradiata in China - Xing-Jiang Song; Xin-Di Li; Yu Chen; Jia Wang; Jia-Bin Zou; Zhi-Hong Zhu; Gang Liu (Journal of Plant Research, 2025)

Deploying an Integrated Fiber Optic Sensing System for Seismo-Acoustic Monitoring: A Two-Year Continuous Field Trial in Xinfengjiang - Siyuan Cang; Min Xu; Jiantong Chen; Chao Li; Kan Gao; Xingda Jiang; Zhaoyong Wang; Bin Luo; Zhuo Xiao; Zhen Guo; Ying Chen; Qing Ye; et al. (Journal of Marine Science and Engineering, 2025)
Distributed Acoustic Sensing (DAS) offers numerous advantages, including resistance to electromagnetic interference, long-range dynamic monitoring, dense spatial sensing, and low deployment costs. We initially deployed a water–land DAS system at the Xinfengjiang (XFJ) Reservoir in Guangdong Province, China, to monitor earthquake events. Environmental noise analysis identified three distinct noise zones based on deployment conditions: periodic 18 Hz signals near surface-laid segments, attenuated low-frequency signals (

KCNJ15 inhibits chemical-induced lung carcinogenesis and progression through GNB1 mediated Hippo pathway - Hong-qiang Chen; Na Wang; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Ya-wen Li; Shuang-wu Deng; Zi-yuan Zhou; Wen-bin Liu (Toxicology, 2025)

2.08 Ga andesitic gneisses in the southwestern Yangtze Block: Unveiling new insights into its geological evolution - Jun-Ping Liu; Zai-Bo Sun; Wei-Ke Li; Hua-Li Luo; Shi-Jun He; Shao-Bin Hu; Jiang-Tai Zhao; Hai-bao Yan; Ming-Guo Zhai; Hai-Long He (Precambrian Research, 2025)

Episodic cooling of the Hannan-Micangshan Dome at the northern margin of the Yangtze Block, Central China: Response to progressive convergence in the eastern Tethys since the Mesozoic - Kui Tong; Zhiwu Li; Shugen Liu; Jinxi Li; Dong Sun; Bin Deng; Wenhui Wu; Yuehao Ye; Zijian Wang; Xun Jiang; Yin Li; Xiao Sun (Journal of Asian Earth Sciences, 2025)

Improved uptake of anthocyanins-loaded nanoparticles based on phenolic acid-grafted zein and lecithin - Zhiying Li; Jinlong Tian; Qilin Tian; Zhihuan Zang; Yumeng Wang; Qiao Jiang; Yi Chen; Baoru Yang; Shufang Yang; Yiyun Yang; Bin Li (Food Chemistry, 2025)

Effects of different ratios of water and glycerol on the physicochemical properties of starch-based straws - Pengfei Liu; Yue Li; Deyin Wang; Ruoxuan Xu; Yandu Jiang; Xinyu Qiao; Wei Gao; Bin Yu; Bo Cui (Food Chemistry, 2025)

Single-cell transcriptome sequencing analysis of physiological and immune profiling of crucian carp (Carassius auratus) gills - Zhi-Guang Hou; Meng-Chao Xing; Jia-Xing Luo; Yi-Huan Xu; Li-Han Zhang; Xiao-Wei Gao; Jiang-Jiang Wang; Fazhan Hanafiah; Waiho Khor; Xin Hao; Xin Zhao; Cheng-Bin Wu (Fish & Shellfish Immunology, 2025)

Improving the real-time energy matching performance of PV-based home energy system: A multi-time resolution scheduling method utilizing flexibility of thermostatically controlled loads and batteries - Bin Zou; Yijing Lei; Jinqing Peng; Kai Wang; Ji Li; Renge Li; Haihao Jiang; Bin Hao (Energy and Buildings, 2025)

Scalable deposition of SnO2 ETL via SALD for large-area inverted perovskite solar modules - Xuewei Jiang; Bin Shan; Geng Ma; Yan Xu; Xing Yang; Wenbin Zhou; Chenhui Li; Fan Yang; Rong Chen (Chemical Engineering Journal, 2025)

Insights into the formation and development of membrane fouling in a continuous flow aerobic granular sludge membrane bioreactor - Mengci Ni; Juan Jiang; Biao Yang; Bingduo Wang; Liying Bin; Weirui Chen; Ping Li; Shaosong Huang; Bing Tang (Chemical Engineering Journal, 2025)

Multiple-stage W mineralization in the Guanfang W deposit, southeastern Yunnan Province, China: Insights from scheelite in-situ trace elemental and Sr isotopic analyses - Bin Sun; Yi Liu; Zhigang Kong; Xuelong Liu; Xiaojun Jiang; Chao Li; Wenchang Li (Acta Geochimica, 2025)

The size-fractionated composition of particulate biogenic silica and its ecological significance in the Changjiang Estuary area - Xizhen Liu; Bin Wang; Siyang Chen; Haiyan Jin; Yanpei Zhuang; Zhibing Jiang; Hongliang Li; Jianfang Chen (Frontiers in Marine Science, 2025)
The concentrations and distributions of particulate biogenic silica (PBSi) and its size-fractionated composition (>20 μm, 0.8–20 μm) of the Changjiang Estuary and its adjacent area were investigated during the summer of 2011. PBSi, primarily produced by diatoms in the surface waters of oceans, was examined for correlations with hydrographic conditions, nutrients, particulate organic carbon, and dissolved oxygen. The distribution of PBSi showed distinct patterns: high levels in nearshore, but relatively low further offshore; low concentrations in the surface layer, whereas relatively high concentrations in the bottom layer. Large-sized PBSi (>20 μm) prevailed in the surface layer, whereas small-sized PBSi (0.8–20 μm) dominated in the bottom layer. Temperature and nutrients were crucial factors controlling the grain size structure and distribution of PBSi. Further, we observed that the distinct zones of high PBSi values in the surface waters were affected by the Changjiang freshwater flushing, and those in the bottom waters were affected by the Yellow Sea Cold Water masses. Moreover, in the area where >20-μm PBSi prevailed, the silicate-to-nitrate ratio was less than 1 at most sampling stations, rendering silicate the limiting nutrient in this area. The PBSi/particulate organic carbon values in the surface waters of the study area ranged from 0.01 to 0.3. Areas exhibiting values exceeding 0.13 primarily clustered in nearshore waters, which was characterized by a dominance of large-sized (>20 μm) PBSi. The nearshore benthic waters exhibited anoxic conditions, where diatoms predominantly comprised the phytoplankton biomass and organic matter featured marine phytoplankton. Consequently, the proliferation of diatoms (siliceous phytoplankton) in the midupper water significantly contributed to the hypoxic conditions at the bottom, as diatoms underwent dissolution during sedimentation, leading to oxygen depletion.

Advancing diurnal analysis of vegetation responses to drought events in the Yangtze River Basin using next-generation satellite data - Tingyu Li; Shaoqiang Wang; Zhuoying Deng; Jinghua Chen; Bin Chen; Zhewei Liang; Xuan Chen; Yunhao Jiang; Peng Gu; Leigang Sun (Science of The Total Environment, 2025)

pH-dependent cadmium binding to hemoglobin: Implications for human excretion - Min Yuan; Qiying Nong; Hua Guo; Yu Li; Haozhong Tian; Jiaao Zhang; Lihong Liu; Bin He; Ligang Hu; Guibin Jiang (Science of The Total Environment, 2025)

Preparation of a Bi12TiO20/U6M1/PES composite membrane for rhodamine B degradation under visible-light irradiation - Jinyang Liu; Qiqi Liao; Chengcai Li; Xueliang Jiang; Jiuming Li; Wangyong Jin; Guojin Liu; Yuhai Guo; Bin Yu; Hailin Zhu (Process Safety and Environmental Protection, 2025)

Thinking beyond general greenness: The nuanced associations between a variety of greenspaces and cardiovascular diseases across urbanicity - Yuwen Yang; Bin Jiang; Lan Wang; Yuyu Zhou; Bo Li; Peng Gong (Landscape and Urban Planning, 2025)

A forecasting tool for optimized emission control strategies to achieve short-term air quality attainment - Zhaoxin Dong; Shuxiao Wang; Yueqi Jiang; Jia Xing; Dian Ding; Fenfen Zhang; Dejia Yin; Qian Song; Jingyu An; Hongli Wang; Cheng Huang; Qian Wang; et al. (Journal of Environmental Management, 2025)

Probability analysis of shallow landslides in varying vegetation zones with random soil grain-size distribution - Hu Jiang; Qiang Zou; Yong Li; Yao Jiang; Junfang Cui; Bin Zhou; Wentao Zhou; Siyu Chen; Zihao Zeng (Environmental Modelling & Software, 2025)

3D-printed flexible thermoplastic polyurethane membrane for ultrafast oil/water separation - Junpeng Zhang; Yingying Li; Bin He; Tao Zhang; Bingqian Yang; Wenzheng Yu; Ligang Hu; Guibin Jiang (Chemical Engineering Journal, 2025)

Changes in accumulation of land-based organic matter under recent climate change and anthropogenic impact: A tropical coastal perspective - Ming Liu; Yazhi Bai; Li Jiang; Limin Hu; Bin Wu; Shuqing Qiao; Weini Chong; Narumol Kornkanitnan; Somkiat Khokiattiwong; Xuefa Shi (CATENA, 2025)

Expression patterns and evidence of the expansion of Nicotiana tabacum L. TALE genes in the Solanaceae family - Yanru Song; Decai Kong; Youqing Dai; Kangkang Song; Bin Li; Jiazhu Jiang; Chunyan Xiao; Long Yang (Genetic Resources and Crop Evolution, 2025)
The three-amino-acid-loop-extension (TALE) proteins are a class of transcription factors that regulate meristem differentiation during plant growth and development. In this study, we identified a total of 45 members of the tobacco TALE ( NtTALE ) transcription factor family. Based on domain type, the NtTALE genes were divided into BELL subfamily and KNOX subfamily. Cis -acting element analysis showed that the NtTALE gene promoters had a variety of response elements, including light-responsive elements, hormonal and abiotic stresses responsive elements, plant development related elements. Among the 45 NtTALE genes, the expression patterns of various plant tissues at different stages were different, 10 responded to alkali stress, 19 responded to dehydration treatment, 14 responded to cold stress, two responded to salt stress, and 17 responded to Ralstonia solanacearum infection. Phylogenetic analysis showed that the number of TALE genes in Nicotiana was significantly expanded compared with that in other Solanaceae . The KNOXIII subfamily members ( NtTALE29 , NtTALE45 ) were found only in Nicotiana tabacum . This study provides a theoretical basis for further research on the biological function of NtTALE genes.

Evolutionary characteristics of the fracture network in rock slopes under the combined influence of rainfall and excavation - Qihang Li; Yunmin Wang; Xiaoshuang Li; Shibin Tang; Bin Gong; Song Jiang (Bulletin of Engineering Geology and the Environment, 2025)

Intramolecular distance-regulated G4 DNA enzymatic activity-based chromophotometric system for visual monitoring of diquat - Ya You; Wei-Guo Yang; Shun Zhang; Ming-Li Su; Qi-Lin Peng; Wan-Jiang Zhao; Ruo Yuan; Shang-Cheng Xu; Wen-Bin Liang (Analytica Chimica Acta, 2025)

Food-derived extracellular vesicles: natural nanocarriers for active phytoconstituents in new functional food - Qiao Jiang; Li Wang; Jinlong Tian; Weijia Zhang; Huijun Cui; Hailong Gui; Zhihuan Zang; Bin Li; Xu Si (Critical Reviews in Food Science and Nutrition, 2024)

Conjugated diamine cation based halide perovskitoid enables robust stability and high photodetector performance - Xin Yang; Xu-Dong Wang; Wen-Guang Li; Yu-Hua Huang; Ling-Bin Wang; Jia-Min Liu; Long Jiang; Dai-Bin Kuang (Science Bulletin, 2024)

Deciphering the evolution and biogeography of ant-ferns Lecanopteris s.s - Li-Ju Jiang; Jing Zhao; Jia-Guan Wang; Sven Landrein; Ji-Pu Shi; Chuan-Jie Huang; Miao Luo; Xin-Mao Zhou; Hong-Bin Niu; Zhao-Rong He (Molecular Phylogenetics and Evolution, 2024)

Paleogeographic reconstruction and sedimentary evolution of tidal-dominated estuarine depositional systems: Insights from the campanian M1 sandstone formation, Oriente Basin, Ecuador - Sicheng Zhu; Panke Sun; Kexin Zhang; Chaoqian Zhang; Qi Zhang; Bin Li; Jiang Wang; Shiyi Jiang; Liyin Bao; Guangbin Jing; Zhangxing Chen; Huaimin Xu (Marine and Petroleum Geology, 2024)

Structure-guided discovery and rational design of a new poly(ethylene terephthalate) hydrolase from AlphaFold protein structure database - Wei Liu; Chuang Li; Bin Li; Liying Zhu; Dengming Ming; Ling Jiang (Journal of Hazardous Materials, 2024)

Indicator-enhanced starch-based intelligent film for nondestructive monitoring of beef freshness: Different structural phenolic acids copigment anthocyanin - Jiaxin Li; Yiwen Bao; Qiao Jiang; Bo Wen; Liang Wang; Ying He; Xu Si; Bin Li (Journal of Food Engineering, 2024)

Biointerfacial supramolecular self-assembly of whey protein isolate nanofibrils on probiotic surface to enhance survival and application to 3D printing dysphagia foods - Ye Zhang; Yexuan Wang; Xiaohan Dai; Ying Li; Bin Jiang; Dongmei Li; Chunhong Liu; Zhibiao Feng (Food Chemistry, 2024)

Histidine is effective in promoting muscle growth and protein deposition: In vivo and in vitro experimental models of grass carp (Ctenopharyngodon idella) - Xin Zeng; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Ling Tang; Shu-Wei Li; Sheng-Yao Kuang; Lin Feng (Food Bioscience, 2024)

Dynamic high pressure microfluidization modified oat dietary fiber: Texture modulation and its mechanistic in whole grain oat milk - Ziyue Kang; Ning Meng; Ming Liu; Yanxiang Liu; Ping Jiang; Xiaotong Zhai; Yanan Fei; Li Wang; Juanli Shen; Bin Tan (Food Hydrocolloids, 2024)

Corrigendum to “A critical review on graphene oxide membrane for industrial wastewater treatment” [Environ. Res. 223 (2023) 115409] - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2024)

Blood cadmium levels and overactive bladder in middle-aged and older adults in the United States: Insights from NHANES 2007–2020 data - Fan Gao; Yin Lu; Qiang Cheng; Qing Ai; Bin Jiang; Zhen-Jun Luo; Guo-Rong Yang; Kai-Kai Lv; Qing Yuan; Hong-Zhao Li (Environmental Pollution, 2024)

Enhanced peracetic acid activation under Far-UVC Radiation: Micropollutant degradation and radical assessment - Tao Yang; Maoju Jiang; Peng Su; Qixiao Lv; Wenqi Li; Chenlong Liu; Bin Zhang; Haochen Zhang; Linlin Zang; Minchao Liu; Jun Ma (Chemical Engineering Journal, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Cattle manure composting driven by a microbial agent: A coupled mechanism involving microbial community succession and organic matter conversion - Zichun Zhang; Huaikai Yang; Meilin Linghu; Jiang Li; Chao Chen; Bin Wang (Science of The Total Environment, 2024)

Intercomparison of measured and modelled photochemical ozone production rates: Suggestion of chemistry hypothesis regarding unmeasured VOCs - Jun Zhou; Wenjie Wang; Yan Wang; Zhen Zhou; Xiongzhou Lv; Meijin Zhong; Bowen Zhong; Minhui Deng; Bin Jiang; Junqing Luo; Jiahua Cai; Xiao-Bing Li; et al. (Science of The Total Environment, 2024)

Rapid and extensive SARS-CoV-2 Omicron variant infection wave revealed by wastewater surveillance in Shenzhen following the lifting of a strict COVID-19 strategy - Yinghui Li; Chen Du; Ziquan Lv; Fuxiang Wang; Liping Zhou; Yuejing Peng; Wending Li; Yulin Fu; Jiangteng Song; Chunyan Jia; Xin Zhang; Mujun Liu; et al. (Science of The Total Environment, 2024)

Burden of biliary tract carcinoma in China (1990–2021): Findings from the 2021 Global Burden of Disease Study - Wei Zhang; Yi-Jun Wang; Jiang-Mei Liu; Xu-Heng Sun; Yan Jiang; Fang Shen; Li-Juan Shen; Jing Xiang; Jun-Feng Zhang; Lin-Hua Yang; Wen-Guang Wu; Tao Chen; et al. (Science Bulletin, 2024)

Composition and temporal dynamics of the phytoplankton community in Laizhou Bay revealed by microscopic observation and rbcL gene sequencing - Huihui Zhang; Nan Wang; Di Zhang; Fei Wang; Shiji Xu; Xiaokun Ding; Yixuan Xie; Jinghuan Tian; Bin Li; Zhengguo Cui; Tao Jiang (Marine Environmental Research, 2024)

Anthocyanin-loaded milk-derived extracellular vesicles nano-delivery system: Stability, mucus layer penetration, and pro-oxidant effect on HepG2 cells - Qiao Jiang; Yongxin Sun; Xu Si; Huijun Cui; Jiaxin Li; Yiwen Bao; Li Wang; Bin Li (Food Chemistry, 2024)

pH-Dependent interactions between β-casein and blueberry anthocyanins based on typical thermal processing conditions: Stability, structural characterization, and binding mechanisms - Meili Xin; Liang Wang; Ying He; Hongzhou Jiang; Jinlong Tian; Bin Li (Food Hydrocolloids, 2024)

RNA reading protein YTHDF2 mediates Benzo(k)fluoranthene induced male reproductive injury by regulating the stability of BCL2 - Ya-wen Li; Dan-dan Wang; Hong-qiang Chen; Yong Zeng; Na Wang; Yu Shi; Jiang-ying Li; Ni-ya Zhou; Da-peng Wang; Qing Chen; Xue Han; Jia Cao; et al. (Environmental Pollution, 2024)

New insights into the functional group influence on CO2 absorption heat and CO2 equilibrium solubility by piperazine derivatives - Xi Tang; Bin Xu; Wufeng Jiang; Xiaoshan Li; Ge Gao; Fan Wu; Cong Luo; Liqi Zhang (Chemical Engineering Journal, 2024)

In situ regulating the interfacial work function of Ag doped Ni(OH)2 via trace of Fe2+ for efficient water splitting - Min Li; Runlin Huang; Chao Feng; Longfei Sun; Yanan Zhou; Haijun Liu; Chi Jiang; Yingli Wang; Jie Dou; Qiyao Guo; Yuanyuan Zhao; Jialong Duan; et al. (Chemical Engineering Journal, 2024)

A phase separation prediction model for CO2 capture by biphasic amine absorbents - Xiaoyi Gao; Wufeng Jiang; Bin Xu; Yongsheng Fan; Cong Luo; Fan Wu; Xiaoshan Li; Liqi Zhang (Chemical Engineering Journal, 2024)

PbHfO3-based antiferroelectric materials: Fundamentals, properties, and advanced applications - Dong-Liang Li; Xin-Gui Tang; Shui-Feng Li; Xiao-Bin Guo; Dan Zhang; Qi-Jun Sun; Wen-Hua Li; Zhen-Hua Tang; Yan-Ping Jiang; Qiu-Xiang Liu (Chemical Engineering Journal, 2024)

Analysis of the potential of marine bioblue carbon storage and their regional contributions in Shanghai marine areas - Yifei Shen; Ruitong Jiang; Caicai Liu; Min Li; Gangwei Jiao; Bin Li; Meiqin Wu; Jianheng Zhang; Liu Shao; Chuner Cai; Liyan Shi; Peimin He (Marine Pollution Bulletin, 2024)

Stable microbial community diversity across large-scale Antarctic water masses - Zhengang Liu; Furong Cao; Jiyuan Wan; Xing Chen; Bin Kong; Dong Li; Xiao-Hua Zhang; Yong Jiang; Xiaochong Shi (Science of The Total Environment, 2024)

Impacts of chloride ions on the electrochemical decomplexation and degradation of Cr(III)-EDTA: Reaction mechanisms of HO• and RCS - Shujie Zheng; Jiani Yao; Ying Huang; Jiaqi Ren; Yang Hou; Bin Yang; Lecheng Lei; Jianjie Fu; Abdulaziz Al-Anazi; Guibin Jiang; Zhongjian Li (Journal of Hazardous Materials, 2024)

FTO mediates bisphenol F-induced blood-testis barrier impairment through regulating ferroptosis via YTHDF1/TfRc and YTHDF2/SLC7A11 signal axis - Yu Shi; Li Yin; Jiang-ying Li; Shi-meng Zhou; Na Wang; Hong-qiang Chen; Yong Zeng; Ya-wen Li; Wen-bin Liu (Environmental Pollution, 2024)

Epoxy resin gel particles with adjustable stickiness and deformability for pesticide delivery - Jiang Du; Da-Xia Zhang; Li-Jian Hao; Kun Zhuang; Feng Liu; Chao-Bin Xue (Chemical Engineering Journal, 2024)

Insights into the dual effect of an amphiphilic additive on hydrate formation from a water structure perspective - Zhibo Jiang; Meixue Liu; Dawei Guan; Weixin Pang; Qingping Li; Bin Wang; Lunxiang Zhang; Jiafei Zhao; Lei Yang; Shouwei Zhou; Yongchen Song (Chemical Engineering Journal, 2024)

Upcycling of polyethylene/polypropylene mixtures promoted by well-controlled multiblock olefin copolymers - Yuze Kang; Hanlin Wang; Fanmao Meng; Shangtao Chen; Bin Du; Zihao Jiang; Jiajia Wu; Kebin Zhang; Huan Gao; Li Pan; Yuesheng Li (Chemical Engineering Journal, 2024)

Facile synthesis of hierarchical Fe–S co-doped carbon-based composites with superior microwave absorption - Mengyang Liu; Bin Gu; Yukun Jiang; Weiyang Xue; Jingmei Li; Huangzhao Wei; Chenglin Sun (Chemical Engineering Journal, 2024)

Identification and characterization of QSFS.sau-MC-5A for sterile florets genetically independent of fertile ones per spike in wheat - Jieguang Zhou; Yuanjiang He; Wei Li; Bin Chen; Longxing Su; Yuxin Lan; Lei Yan; Ying Wang; Md Nahibuzzaman Lohani; Yanlin Liu; Huaping Tang; Qiang Xu; et al. (Theoretical and Applied Genetics, 2024)

TNF-α and RPLP0 drive the apoptosis of endothelial cells and increase susceptibility to high-altitude pulmonary edema - Yi-Ling Ge; Pei-Jie Li; Ying-Rui Bu; Bin Zhang; Jin Xu; Si-Yuan He; Qing-Lin Cao; Yun-Gang Bai; Jin Ma; Lin Zhang; Jie Zhou; Man-Jiang Xie (Apoptosis, 2024)
High-altitude pulmonary edema (HAPE) is a fatal threat for sojourners who ascend rapidly without sufficient acclimatization. Acclimatized sojourners and adapted natives are both insensitive to HAPE but have different physiological traits and molecular bases. In this study, based on GSE52209, the gene expression profiles of HAPE patients were compared with those of acclimatized sojourners and adapted natives, with the common and divergent differentially expressed genes (DEGs) and their hub genes identified, respectively. Bioinformatic methodologies for functional enrichment analysis, immune infiltration, diagnostic model construction, competing endogenous RNA (ceRNA) analysis and drug prediction were performed to detect potential biological functions and molecular mechanisms. Next, an array of in vivo experiments in a HAPE rat model and in vitro experiments in HUVECs were conducted to verify the results of the bioinformatic analysis. The enriched pathways of DEGs and immune landscapes for HAPE were significantly different between sojourners and natives, and the common DEGs were enriched mainly in the pathways of development and immunity. Nomograms revealed that the upregulation of TNF-α and downregulation of RPLP0 exhibited high diagnostic efficiency for HAPE in both sojourners and natives, which was further validated in the HAPE rat model. The addition of TNF-α and RPLP0 knockdown activated apoptosis signaling in endothelial cells (ECs) and enhanced endothelial permeability. In conclusion, TNF-α and RPLP0 are shared biomarkers and molecular bases for HAPE susceptibility during the acclimatization/adaptation/maladaptation processes in sojourners and natives, inspiring new ideas for predicting and treating HAPE.

The source of lithium in Lakkor Co Salt Lake on Qinghai-Tibet Plateau, China: evidence from hydrochemical characteristics and boron isotope - Zheng Yan Li; Bin Kai Li; Mao-Yong He; Xue Qin Wen; Jiang Di Zhou (Acta Geochimica, 2024)

Chemical constituents from the roots of Dolomiaea souliei - Zhe Wang; Li-Dan Zhang; Gang-Gang Zhou; Qi-Zheng Zhong; Yun-Bin Jiang; Guo-Wei Wang; Zhi-Hua Liao; Fan-Cheng Meng; Min Chen (Natural Product Research, 2024)

Selenium nanoparticles alleviates cadmium induced hepatotoxicity by inhibiting ferroptosis and oxidative stress in vivo and in vitro - Chunyan Shao; Tongwang Luo; Shujie Wang; Zhuoyue Li; Xiaoqiang Yu; Ya Wu; Sheng Jiang; Bin Zhou; Quanjiang Song; Shengzhe Song; Xiaodu Wang; Houhui Song (Chemosphere, 2024)

Benzo(a)pyrene promotes the malignant progression of malignant-transformed BEAS-2B cells by regulating YTH N6-methyladenosine RNA binding protein 1 to inhibit ferroptosis - Na Wang; Hong-qiang Chen; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Shi-meng Zhou; Ya-wen Li; Shuang-wu Deng; Xue Han; Zi-yuan Zhou; Mao-lin Yao; et al. (Toxicology, 2024)

A combined extended triple collocation and cumulative distribution function merging framework for improved daily precipitation estimates over mainland China - Linyong Wei; Shanhu Jiang; Jianzhi Dong; Liliang Ren; Bin Yong; Bang Yang; Xueying Li; Zheng Duan (Journal of Hydrology, 2024)

Tracing residual patterns and microbial communities of pharmaceuticals and personal care products from 17 urban landfills leachate in China - Lin-Hui Zhang; Jin-Nong Li; Yi-Hao Li; Xi-Ze Min; De-Yong Kong; Yue Han; Chao Jiang; Hang Xiao; Bin Liang; Zi-Feng Zhang (Journal of Hazardous Materials, 2024)

Effect of ammonia environment on the quality of boxed non-dairy cream - Lan Chen; Bin Liu; Lingling Pang; Yuqian Jiang; Xihong Li; Jianfei Song; Dan Zhou (International Journal of Refrigeration, 2024)

Reaction mechanism and kinetics of kerogen dehydrogenation and cyclization investigated by density functional theory - Yuxuan Zhang; Yushu Jiang; Guisheng Li; Xuezhi Duan; Bin Chen (Fuel, 2024)

Characterization of hydrogel beads constructed from gelatinized lotus rhizome starch and sodium alginate by calcium cross-linking - Xin-Yu Jiang; Lin Li; Jia-Nan Yan; Li-Chao Zhang; Ce Wang; Bin Lai; Hai-Tao Wu (Food Hydrocolloids, 2024)

Natural pyrethrins induce cytotoxicity in SH-SY5Y cells and neurotoxicity in zebrafish embryos (Danio rerio) - Wei-Guo Wang; Shou-Lin Li; Bin Liu; Ning Tang; Cheng Zhang; Xu-Feng Jiang; Li-Ming Tao; Wen-Ping Xu; Yang Zhang (Environmental Research, 2024)

Spodumene nanosheets@ZrO2-SiO2 heterostructure nanofibers modified separator for long-cycle lithium-sulfur batteries - Lin Li; Bin Yue; Yingying Bao; Shan Jiang; Hong Shao; Qianli Ma; Wensheng Yu; Jinxian Wang; Xiangting Dong (Chemical Engineering Journal, 2024)

Diversity of Fungal Community and Its Constraints in the Yifeng Lithium Mines, Eastern China - Qiaoyun Jiang; Ting Zhao; Zixuan Kong; Bingqing Kong; Junyao Chen; Bin Zhao; Yumei Li; Xiangjie Cui; Zhe Yin; Xiancai Lu; Dongmei Zhang (Current Microbiology, 2024)

Unleashing the potential of urban jogging: Exploring the synergistic relationship of high-density environments and exercise on Residents' Health - Qikang Zhong; Bo Li; Bin Jiang; Tian Dong (Journal of Cleaner Production, 2024)

Study of the catalytic pyrolysis mechanism of guaiacol over seaweed-derived carbon catalyst: Based on density function theory and machine learning - Ding Jiang; Xuping Yang; Arman Amani Babadi; Xiaoxue Cheng; Qifan Ling; Hongping Li; Sirong He; Bin Cao; Xun Hu; Shuang Wang (Fuel, 2024)

Deep learning prediction of rainfall-driven debris flows considering the similar critical thresholds within comparable background conditions - Hu Jiang; Qiang Zou; Yunqiang Zhu; Yong Li; Bin Zhou; Wentao Zhou; Shunyu Yao; Xiaoliang Dai; Hongkun Yao; Siyu Chen (Environmental Modelling & Software, 2024)

Lateral holding behaviour of torpedo piles in spatially variable soil: Development of a probabilistic design approach - Jiang Tao Yi; Shi Jie Xu; Wu Hao Liu; Lin Ding; Zhen Wang; Hong Yu Tang; Xiao Bin Li (Computers and Geotechnics, 2024)

Cation-permselective membranes enabled by synergistic ion channels of crown ethers and anionic sites - Yanran Zhu; Bin Wu; Qian Chen; Guanyin Gao; Xingya Li; Chenxiao Jiang; Rongqiang Fu; Zhaoming Liu; Liang Ge; Tongwen Xu (Chemical Engineering Journal, 2024)

Analyzing sleep thermal comfort with an attention-based gated recurrent unit neural network - Jishen Tang; Jilei Li; Jiang Wang; Yunhao Li; Yimin Yang; Zuoting Song; Meirong Ma; Bin Deng (Building and Environment, 2024)

From characteristics to practical applications of skin temperature in thermal comfort research – A comprehensive review - Jiaqi Zhao; Rui Wang; Yeyu Wu; Chaoyi Zhao; Yun Qi; Sishi Li; Haihua Jiang; Bin Cao (Building and Environment, 2024)

HCMV IE1/IE1mut Therapeutic Vaccine Induces Tumor Regression via Intratumoral Tertiary Lymphoid Structure Formation and Peripheral Immunity Activation in Glioblastoma Multiforme - Xiaoli Yang; Shasha Jiang; Fengjun Liu; Zonghui Li; Wenxuan Liu; Xianjuan Zhang; Fulong Nan; Jun Li; Meng Yu; Yunyang Wang; Bin Wang (Molecular Neurobiology, 2024)
Glioblastoma multiforme (GBM), a highly malignant invasive brain tumor, is associated with poor prognosis and survival and lacks an effective cure. High expression of the human cytomegalovirus (HCMV) immediate early protein 1 (IE1) in GBM tissues is strongly associated with their malignant progression, presenting a novel target for therapeutic strategies. Here, the bioluminescence imaging technology revealed remarkable tumor shrinkage and improved survival rates in a mouse glioma model treated with HCMV IE1/IE1mut vaccine. In addition, immunofluorescence data demonstrated that the treated group exhibited significantly more and larger tertiary lymphoid structures (TLSs) than the untreated group. The presence of TLS was associated with enhanced T cell infiltration, and a large number of proliferating T cells were found in the treated group. Furthermore, the flow cytometry results showed that in the treatment group, cytotoxic T lymphocytes exhibited partial polarization toward effector memory T cells and were activated to play a lethal role in the peripheral immunological organs. Furthermore, a substantial proportion of B cells in the draining lymph nodes expressed CD40 and CD86. Surprisingly, quantitative polymerase chain reaction indicated that a high expression of cytokines, including chemokines in brain tumors and immune tissues, induced the differentiation, development, and chemokine migration of immune cells in the treated group. Our study data demonstrate that IE1 or IE1mut vaccination has a favorable effect in glioma mice models. This study holds substantial implications for identifying new and effective therapeutic targets within GBM.

Characterization of adaptive expression regulation of yellowtail kingfish (Seriola lalandi) leptin, receptor, and receptor overlapping transcript genes in response to fasting and re-feeding strategies - Xin Cai; Ying Li; Aijun Cui; Yan Jiang; Bin Wang; Zhaojun Meng; Yongjiang Xu (Fish Physiology and Biochemistry, 2024)

Impact of high-altitude environments on the motion and settling characteristics of wet-mix shotcrete dust in tunnels - Guoliang Zhang; Zhongan Jiang; Xiaocuan Li; Ya Chen; Bin Yang; Mingli Si; Rui Feng; Ming Wang (Tunnelling and Underground Space Technology, 2024)

Zinc-associated phospholipid metabolic alterations and their impacts on ALT levels in workers - Yuanyuan Wang; Yiling Li; Qiying Nong; Guohuan Zhang; Nian Liu; Hua Guo; Qinghao He; Lihong Liu; Guangbo Qu; Bin He; Ligang Hu; Guibin Jiang (Science of The Total Environment, 2024)

New insights into the influences of firework combustion on molecular composition and formation of sulfur- and halogen-containing organic compounds - Caiqing Yan; Haibiao Chen; Fei Xu; Qinglong Fu; Ying Zhou; Ruizhi Zhou; Ruiyu Li; Mei Zheng; Mingjie Xie; Bin Jiang; Zhisheng Zhang; He Meng; et al. (Science of The Total Environment, 2024)

Elucidation of the beneficial role of co-fermented whole grain quinoa and black barley with Lactobacillus on rats fed a western-style diet via a multi-omics approach - Zi-Han Lin; Ling-Yue Zhong; Hui-Bin Jiang; Chuang Zhu; Fen-Fen Wei; Yan Wu; Li-Hua Song (Food Research International, 2024)

Water effect on CO2 absorption mechanism and phase change behavior in [N1111][Gly]/EtOH anhydrous biphasic absorbent: In density functional theory and molecular dynamics view - Wufeng Jiang; Ge Gao; Xiaoyi Gao; Bin Xu; Fan Wu; Xiaoshan Li; Liqi Zhang; Cong Luo (Chemical Engineering Journal, 2024)

Roles of THEM4 in the Akt pathway: a double-edged sword - Wen Xie; Weidong Liu; Lei Wang; Bin Zhu; Cong Zhao; Ziling Liao; Yihan Li; Xingjun Jiang; Jie Liu; Caiping Ren (Journal of Zhejiang University-SCIENCE B, 2024)

microRNA-3037 targeting CYP6CY2 confers imidacloprid resistance to Sitobion miscanthi (Takahashi) - Bai-Zhong Zhang; Yu-Tai Jiang; Ling-Ling Cui; Gui-Lei Hu; Xin-An Li; Pei Zhang; Xiang Ji; Ping-Chuan Ma; Fan-Bin Kong; Run-Qiang Liu (Pesticide Biochemistry and Physiology, 2024)

Overexpression of a nuclear receptor HR96 contributes to spirodiclofen susceptibility in Panonychus citri (McGregor) - Si-chen Li; Lu-yan Cheng; Qi-qi Yang; Ze-hao Huang; Bin-bin Shao; Shi-jiang Yu; Li-li Ding; Qi Pan; Shuang Lei; Liu Liu; Lin Cong; Chun Ran (Pesticide Biochemistry and Physiology, 2024)

Deep soil desiccation hinders nitrate leaching to groundwater in the global largest apple cultivation area - Dong Ge; Xiaodong Gao; Pengyan Jiang; Bin Li; Nana He; Yabiao Wu; Qinghai He; Yaohui Cai; Changjian Li; Xining Zhao (Journal of Hydrology, 2024)

Synergistic effect mechanism of biomass ash-derived K-Ca-Si catalytic system on syngas production and reactivity characteristics of high-sulfur petroleum coke gasification - Jiawei Sun; Jingcheng Zhang; Deliang Xu; Shu Zhang; Peng Lv; Yu Jiang; Xudong Song; Felix Merime Bkangmo Kontchouo; Yue Jiao; Bin Li; Guangsuo Yu; Guangyu Xu; et al. (Fuel, 2024)

Post-self-assemble of whey protein isolation nanofibrils and its contribution to the stability of pickering emulsion - Chunhong Liu; Yexuan Wang; Xiaohan Dai; Ye Zhang; Yue Yang; Bin Jiang; Dongmei Li; Zhibiao Feng (Food Hydrocolloids, 2024)

Effects of static magnetic field-prolonged supercooling preservation on blueberry quality - Hanqian Jiang; Wanqi Hong; Yiming Zhang; Shian Liu; Hongzhou Jiang; Sijin Xia; Xu Si; Bin Li (Food Bioscience, 2024)

Hydrophilic phthalocyanine covalent organic frameworks for enhanced electrocatalytic H2O2 production - Rong Jiang; Qianjun Zhi; Bin Han; Ning Li; Kang Wang; Dongdong Qi; Wenjun Li; Jianzhuang Jiang (Chemical Engineering Journal, 2024)

A low-temperature stretchable XNBR film containing Li-TFSI doped PEDOT:PSS for electromagnetic interference shielding - Xin Jiang; Zhaopeng Hu; Shichao Xu; Bin Hu; Benteng Liu; Qiao Li; Yihu Song; Qiang Zheng (Chemical Engineering Journal, 2024)

Bio-formulated chitosan nanoparticles enhance disease resistance against rice blast by physiomorphic, transcriptional, and microbiome modulation of rice (Oryza sativa L.) - Rahila Hafeez; Junning Guo; Temoor Ahmed; Hubiao Jiang; Mubashar Raza; Muhammad Shahid; Ezzeldin Ibrahim; Yanli Wang; Jiaoyu Wang; Chengqi Yan; Qianli An; Jason C. White; et al. (Carbohydrate Polymers, 2024)

Experimental study on thermal and humidity properties of modified rammed earth buildings in winter - Bin Jiang; Renzi Lu; Maqi Jiang; Liang Wang; Liang Chun; Li Wan (Building and Environment, 2024)

Vertical transport of ultrafine particles and turbulence evolution impact on new particle formation at the surface & Canton Tower - Hao Wu; Zhanqing Li; Shangfei Hai; Yang Gao; Jingkun Jiang; Bin Zhao; Maureen Cribb; Dongmei Zhang; Dongyang Pu; Mengqi Liu; Chunling Wang; Jing Lan; et al. (Atmospheric Research, 2024)

Creating a zero amylose barley with high soluble sugar content by genome editing - Yun Li; Yanyan Jiang; Dong Cao; Bin Dang; Xijuan Yang; Shiting Fan; Yuhu shen; Genying Li; Baolong Liu (Plant Molecular Biology, 2024)

New Record Ocean Temperatures and Related Climate Indicators in 2023 - Lijing Cheng; John Abraham; Kevin E. Trenberth; Tim Boyer; Michael E. Mann; Jiang Zhu; Fan Wang; Fujiang Yu; Ricardo Locarnini; John Fasullo; Fei Zheng; Yuanlong Li; et al. (Advances in Atmospheric Sciences, 2024)
The global physical and biogeochemical environment has been substantially altered in response to increased atmospheric greenhouse gases from human activities. In 2023, the sea surface temperature (SST) and upper 2000 m ocean heat content (OHC) reached record highs. The 0–2000 m OHC in 2023 exceeded that of 2022 by 15 ± 10 ZJ (1 Zetta Joules = 10 21 Joules) (updated IAP/CAS data); 9 ± 5 ZJ (NCEI/NOAA data). The Tropical Atlantic Ocean, the Mediterranean Sea, and southern oceans recorded their highest OHC observed since the 1950s. Associated with the onset of a strong El Niño, the global SST reached its record high in 2023 with an annual mean of ∼0.23°C higher than 2022 and an astounding > 0.3°C above 2022 values for the second half of 2023. The density stratification and spatial temperature inhomogeneity indexes reached their highest values in 2023.

Deciphering the removal of antibiotics and the antibiotic resistome from typical hospital wastewater treatment systems - Dahai He; Jiang Li; Weihai Yu; Yingyuan Zhang; Bin Wang; Tao Wang; Huaikai Yang; Yuntao Zhang; Weijie Chen; Yancheng Li; Faming Feng; Li-An Hou (Science of The Total Environment, 2024)

Overexpressing peach PpePAO1 gene improves the nutrient value of tomato and enhances resistance against Botrytis cinerea - Zhenguo Cui; Yabo Jiang; Yang Chen; Xin Cheng; Bin Tan; Jun Cheng; Langlang Zhang; Xia Ye; Xiaobei Wang; Zhiqian Li; Xianbo Zheng; Jiancan Feng; et al. (Postharvest Biology and Technology, 2024)

6PPDQ induces cardiomyocyte senescence via AhR/ROS-mediated autophagic flux blockage - Baoqiang Fu; Tao Chen; Bin Jiang; Haobin Feng; Ziyu Zhu; Min Li; Guoxing Zhang; Yan Jiang (Environmental Pollution, 2024)

Visible-light induced ofloxacin photodegradation catalyzed by the S-scheme Bi2MoO6/NH2-MIL-68(In) heterojunction: Interfacial engineering, DFT calculations, and toxicity assessment - Huaikai Yang; Zichun Zhang; Jiang Li; Lei Song; Bin Wang (Chemical Engineering Journal, 2024)

Scientometrics and visualized analysis of 3D food printing: A boost to future food customized development - Mingshuang Wang; Yiwen Bao; Dongnan Li; Yuanyuan Bian; Xu Si; Ningxuan Gao; Zhen Cheng; Hailong Gui; Wenjiang Dong; Hongzhou Jiang; Bin Li (Food Bioscience, 2024)

The polyphenols profile of co-fermented quinoa and black barley with Lactobacillus kisonensis and its in vitro bioactivities - Hui-Bin Jiang; Pan Nie; Zi-Han Lin; Chuang Zhu; Ling-Yue Zhong; Fen-Fen Wei; Yan Wu; Li-Hua Song (Food Bioscience, 2024)

Development of electrospun nanofiber films based on pullulan/polyvinyl alcohol incorporating bayberry pomace anthocyanin extract for aquatic products freshness monitoring - Lijun Jiang; Chenyu Wang; Fan Zhao; Shuangdie Li; Di Sun; Qingbao Ma; Zhongjie Yu; Bin Zhang; Yu Liu; Wei Jiang (Food Bioscience, 2024)

Enhancing the physical stability and bioaccessibility of curcumin emulsions through the interaction of whey protein isolate and soybean lecithin - Yue Pan; Lu Liu; Jiayu Li; Bin Zhu; Xiaodong Li; Jinju Cheng; Muhammad Muneeb; Kouadio Jean Eric-parfait Kouame; Xin Jiang (Food Bioscience, 2024)

CoTe2/NiTe2 heterojunction embedded in N-doped hollow carbon nanoboxes as high-efficient ORR/OER catalyst for rechargeable zinc-air battery - Mingyang Liu; Qi Li; Xudong Xiao; Xuena Ma; Xiaoqin Xu; Yihang Yin; Bin Zhang; Minghui Ding; Jinlong Zou; Baojiang Jiang (Chemical Engineering Journal, 2024)

Construction of dual functional CuAl-LDHs nanocomposite loaded with IGF2BP3 siRNA for enhanced therapy of gastric cancer - Haiping Li; Yuying Zhang; Bo Huang; Feifei Yang; Qiang Ma; Xiaolin Wang; Yuying Liu; Junwu Ren; Xiaojuan Pan; Ce Liang; Shimin Wang; Hao Ning; et al. (Chemical Engineering Journal, 2024)

Highly-sensitive, broad-range, and highly-dynamic MXene pressure sensors with multi-level nano-microstructures for healthcare and soft robots applications - Boqing Jia; Zhikang Li; Tengfei Zheng; Jiaxiang Wang; Zhi-Jun Zhao; Libo Zhao; Bin Wang; Jijian Lu; Kang Zhao; Guoxi Luo; Min Li; Qijing Lin; et al. (Chemical Engineering Journal, 2024)

Customized development of 3D printed anthocyanin-phycocyanin polychromatic oral film via chondroitin sulfate homeostasis: A platform based on starch and κ-carrageenan - Yiwen Bao; Mingshuang Wang; Xu Si; Dongnan Li; Hailong Gui; Qiao Jiang; Jiaxin Li; Shufang Yang; Yiyun Yang; Zhongxia Li; Bin Li (Carbohydrate Polymers, 2024)

Interaction of life-time and early-life exposure to antibiotics and indoor environmental factors on childhood plant allergy - Chan Lu; Mengju Lan; Lin Wang; Ying Jiang; Bin Li; Faming Wang (Building and Environment, 2024)

Highly efficient copper ions removal by sodium alginate/sodium humate@Polyacrylamide: adsorption behavior and removal mechanism - Hongyu Wang; Mengyuan Huang; Lu Li; Bin Wang; Can Jiang; Xiaoling Hu; Yi Xie; Rongfan Chen; Wenbin Guo; Henglin Xiao; Mingfei Wang; Dao Zhou (Water, Air, & Soil Pollution, 2024)

Fabrication of Polyethyleneimine-Functionalized Chitosan Composite Microspheres for Efficient Removal of Diclofenac Sodium from Water: Behavior and Mechanism Study - Hongyu Wang; Yi Xie; Henglin Xiao; Lu Li; Shujia Zhang; Bin Wang; Can Jiang; Xiaoling Hu; Dao Zhou; Dongyun Nan (Water, Air, & Soil Pollution, 2024)

Study and application of deeply optimized neural network in roof stability evaluation - Huiyong Yin; Shuo Li; Guoliang Xu; Daolei Xie; Cheng Jiang; Fangying Dong; Houchen Wang; Bin Wu (Earth Science Informatics, 2024)

Examination of the effects of triacylglycerol lipase on astaxanthin conversion in the black tiger prawn Penaeus monodon - Xin-Tao Li; Li-Shi Yang; Shi-Gui Jiang; Qi-Bin Yang; Song Jiang; Fa-Lin Zhou; Yun-Dong Li; Jian-Zhi Shi; Xu Chen; Yu-kai Yang; Jian-Hua Huang (Aquaculture, 2024)

Molecular signatures and formation mechanisms of water-soluble chromophores in particulate matter from Karachi in Pakistan - Jiao Tang; Jun Li; Shizhen Zhao; Guangcai Zhong; Yangzhi Mo; Hongxing Jiang; Bin Jiang; Yingjun Chen; Jianhui Tang; Chongguo Tian; Zheng Zong; Jabir Hussain Syed; et al. (Science of The Total Environment, 2024)

Separator designs for aqueous zinc-ion batteries - Bin Li; You Zeng; Weisong Zhang; Bingan Lu; Qi Yang; Jiang Zhou; Zhangxing He (Science Bulletin, 2024)

Large language models for diabetes care: Potentials and prospects - Bin Sheng; Zhouyu Guan; Lee-Ling Lim; Zehua Jiang; Nestoras Mathioudakis; Jiajia Li; Ruhan Liu; Yuqian Bao; Yong Mong Bee; Ya-Xing Wang; Yingfeng Zheng; Gavin Siew Wei Tan; et al. (Science Bulletin, 2024)

Nickel oxide nanoparticles: A new generation nanoparticles to combat bacteria Xanthomonas oryzae pv. oryzae and enhance rice plant growth - Yasmine Abdallah; Solabomi Olaitan Ogunyemi; Ji'’an Bi; Fang Wang; Xuan Huang; Xianbo Shi; Jiefeng Jiang; Ezzeldin Ibrahim; Mohamed Mohany; Salim S. Al-Rejaie; Chengqi Yan; Bin Li (Pesticide Biochemistry and Physiology, 2024)

Origins of volatiles and helium fluxes from hydrothermal systems in the Eastern Himalayan Syntaxis and constraints on regional heat and tectonic activities - Yiman Li; Xiaocheng Zhou; Tianming Huang; Jiao Tian; Miao He; Xiaoyi Zhu; Jiang Li; Yongxian Zhang; Zhongliang Wu; Bin Li; Yucong Yan; Yuwen Wang; et al. (Journal of Hydrology, 2024)

New perspectives on organic carbon storage in lake sediments based on classified mineralization - Jiang Quanliang; Ma Xiaohua; Li Zhichun; Li Shuaidong; Huang Changchun; Huang Tao; Xue Bin; Yang Hao (CATENA, 2024)

Research on Quantitative Characterization of 3D Fractures Induced by Hydraulic Fracturing: Insights from Experimental Analysis and Mathematical Models - Li Jia; Shoujian Peng; Bin Wu; Jiang Xu; Fazhi Yan; Qixian Li; Yuexia Chen (Rock Mechanics and Rock Engineering, 2024)

Single-Cell RNA Sequencing Transcriptomics Revealed HCMV IE2-Related Microglia Responses in Alzheimer’s-Like Disease in Transgenic Mice - Fengjun Liu; Zhifei Wang; Delei Niu; Xianjuan Zhang; Fulong Nan; Shasha Jiang; Jun Li; Meng Yu; Xiaoli Yang; Shuyun Zhang; Xiaoqiong Zhou; Hui Wang; et al. (Molecular Neurobiology, 2024)
Although multiple factors are known to concur with Alzheimer’s disease (AD), the relationship between human cytomegalovirus (HCMV) and AD-like disease is unclear. Here, we propose a hypothesis that HCMV immediate-early 2 (IE2) protein promotes microglia activation and thus leads to AD-like disease. We successfully constructed IE2 transgenic mice expressing IE2 in the hippocampus. Single-cell sequencing analysis revealed that IE2 promoted the activation of microglia and upregulated the expression of disease-associated microglia genes. Differentially expressed gene analysis and pathway enrichment revealed that IE2 upregulated immune and nervous system disease-related genes. Immunohistochemical analysis showed that the expressions of both amyloid precursor protein (APP) and p-Tau were significantly upregulated in the brains of IE2 mice and were markers of AD. Taken together, these findings provide useful insights into AD-like disease activated by HCMV IE2.

Newcastle disease virus suppresses antigen presentation via inhibiting IL-12 expression in dendritic cells - Fulong Nan; Wenlong Nan; Xin Yan; Hui Wang; Shasha Jiang; Shuyun Zhang; Zhongjie Yu; Xianjuan Zhang; Fengjun Liu; Jun Li; Xiaoqiong Zhou; Delei Niu; et al. (Journal of Zhejiang University-SCIENCE B, 2024)

Natural variation of Grain size 3 allele differentially functions in regulating grain length in xian/indica and geng/japonica rice - Yong-Bin Peng; Chen-Yang Du; Ya-Nan He; Chong-Ke Zheng; Wei Sun; Jin-Jun Zhou; Li-Xia Xie; Cong-Hui Jiang; Jian-Di Xu; Fang Wang; Xian-Zhi Xie (Euphytica, 2024)

Image-based vegetation analysis of desertified area by using a combination of ImageJ and Photoshop software - Jin Tong; Longying Wu; Bin Li; Nan Jiang; Jin Huang; Di Wu; Lihong Zhou; Qingwen Yang; Yuan Jiao; Ji Chen; Ke Zhao; Xiangjun Pei (Environmental Monitoring and Assessment, 2024)

Exploring the adverse effects of 1,3,6,8-tetrabromo-9H-carbazole in atherosclerotic model mice by metabolomic profiling integrated with mechanism studies in vitro - Tong Xu; Yu Jiang; Hualing Fu; Guanglei Yang; Xiaoxu Hu; Yangsheng Chen; Qian Zhang; Yuxi Wang; Yilan Wang; Heidi Qunhui Xie; Fang Han; Li Xu; et al. (Chemosphere, 2024)

Density affects plant size in the Gobi Desert - Yonghua Li; Zhiming Xin; Bin Yao; Ruibing Duan; Xue Dong; Yanfeng Bao; Xinle Li; Yuan Ma; Yaru Huang; Fengmin Luo; Xing Li; Xu Wei; et al. (Science of The Total Environment, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

Investigation on the reaction characteristics and influencing factors of thermal runaway of di-tert-butyl peroxide - Shunyao Wang; Xu Peng; Lin Jiang; Bin Li (Process Safety and Environmental Protection, 2024)

Structurally diverse rearranged sesquiterpenoids, including a pair of rare tautomers, from the aerial parts of Daphne penicillata - Peng Zhao; Ben-Song Xin; Li Ye; Zhen-Tao Ma; Guo-Dong Yao; Rui Shi; Xia-Hong He; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2024)

Four pairs of neolignan enantiomers with distinctive isochroman moiety from the fruits of Crataegus pinnatifida and their protective activities against H2O2-induced SH-SY5Y cells - Peng Zhao; Shi-Fang Li; Jiao-Yang Hou; Shu-Yan Qin; Jia-Yi Li; Xiao-Fang Zhou; Xuan Liu; Jin-Le Hao; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2024)

An integrated capacitive deionization and photocatalysis system for efficient ammonium removal from low-concentration wastewater - Bin Xu; Kaixiang Jiang; Yonghai Gan; Kegui Zhang; Jie Zhang; Jun Luo; Hui Xu; Zhihao Chen; Wenzhong Yang; Honglin Li; Xinzhe Lu (Journal of Water Process Engineering, 2024)

Electrochemical activation of peroxydisulfate by Ti/IrTaO2 anode for quick degradation of xanthate - Cairu Shao; Shuai Li; Hongyang Cao; Lijuan Duan; Wendong Lv; Dongxing Wang; Shuai Rao; Kuifang Zhang; Yusi Jiang; Bin Cai (Journal of Environmental Chemical Engineering, 2024)

Novel metal sulfide sorbents for elemental mercury capture in flue gas: A review - Dongjing Liu; Chaoen Li; Tao Jia; Jiang Wu; Bin Li (Fuel, 2024)

The source of rock moisture in a sandstone cave in arid northern China: rainfall infiltration or vapor condensation? - Xiao-Wei Jiang; Kai-Gao Ouyang; Xu-Lin Tang; Shu-Cong Tan; Jia-Xin Shi; Na Li; Hong-Bin Yan; Jian-Guang Ren; Li Wan (Hydrogeology Journal, 2024)

Interactive effects of dietary leucine and isoleucine affect amino acid profile and metabolism through AKT/TOR signaling pathways in blunt snout bream (Megalobrama amblycephala) - Mang-mang Wang; Yang-yang Huang; Wen-bin Liu; Kang Xiao; Xi Wang; Hui-xing Guo; Yi-lin Zhang; Jing-Wei Fan; Xiang-fei Li; Guang-zhen Jiang (Fish Physiology and Biochemistry, 2024)

Oxygen-regulated spontaneous solid electrolyte interphase enabling ultra-stable solid-state Na metal batteries - Keshuang Cao; Yufan Xia; Haosheng Li; Huiqin Huang; Sikandar Iqbal; Muhammad Yousaf; Ben Bin Xu; Wenping Sun; Mi Yan; Hongge Pan; Yinzhu Jiang (Science Bulletin, 2024)

The miR156-SPL4/SPL9 module regulates leaf and lateral branch development in Betula platyphylla - Bin Yan; Fangrui Li; Qing Ma; Tingting Shen; Jing Jiang; Huiyu Li (Plant Science, 2024)

Geochemical properties, mechanism of formation, and source of solid bitumen in the Ediacaran Dengying Formation from the central to northern Sichuan Basin, China - Xinyan Fang; Bin Deng; Ansong Geng; Shufen Liu; Pufan Wang; Xiao Liang; Yun Li; Bin Cheng; Wenmin Jiang; Liangliang Wu (Marine and Petroleum Geology, 2024)

Flexible catabolism of monoaromatic hydrocarbons by anaerobic microbiota adapting to oxygen exposure - Zhiming Wu; Xin Yu; Yanhan Ji; Guiping Liu; Ping Gao; Lei Xia; Pengfa Li; Bin Liang; Shiri Freilich; Lifeng Gu; Wenjing Qiao; Jiandong Jiang (Journal of Hazardous Materials, 2024)

Microwave-mediated ultrafast solid-state construction of O vacancies enriched cobalt oxide/nitrogen carbon aerogel toward efficient tetracycline degradation with peroxymonosulfate - Chuan Gan; Qian Zhou; Meilin Sheng; Zujie Hu; Yue Li; Jinghang Zhou; Fengxia Bian; Bin Sun; Heyan Jiang (Journal of Cleaner Production, 2024)

Complexes of glycated casein and carboxymethyl cellulose enhance stability and control release of anthocyanins - Huijun Cui; Qiao Jiang; Ningxuan Gao; Jinlong Tian; Yunan Wu; Jiaxin Li; Shufang Yang; Shugang Zhang; Xu Si; Bin Li (Food Research International, 2024)

Initial soil moisture prewinter affects the freeze–thaw profile dynamics of a Mollisol in Northeast China - Yanru Wen; Bao Liu; Heng Jiang; Ting-Yong Li; Bin Zhang; Wenbin Wu (CATENA, 2024)

Systematic exploring domestic waste sorting behavior and influence mechanism of international students in China: based on the PKIC analysis framework - Qiong Zhang; Yun Li; Lei Ding; Bin Jiang (Environment, Development and Sustainability, 2023)

Effects of Recombinant Leptin Proteins on the Expression of Key Genes in the HPG Axis and Liver of Tongue Sole In Vitro - Xin Cai; Yaxing Zhang; Bin Wang; Aijun Cui; Yan Jiang; Zhaojun Meng; Yuting Li; Yongjiang Xu (Fishes, 2023)
Leptin (Lep) plays a crucial role in controlling food intake and maintaining energy balance in mammals. While several studies have shown the presence of multiple leptin genes in teleosts, limited information is currently available on how sex steroid hormones regulate the expression of these genes in fish. In this study, we used two previously expressed and purified leptin proteins to incubate four tissues in vitro (hypothalamic-pituitary-gonadal axis and liver) and used the RT-qPCR method to detect the expression of genes related to growth and reproduction in tongue sole (Cynoglossus semilaevis). The results showed that both recombinant LepA and LepB proteins of tongue sole almost entirely suppressed the expression of genes related to growth and reproduction in the hypothalamic-pituitary-gonadal axis and liver, while LepB may have had a positive role on steroid synthesis in gonads. Further, a high concentration of LepA facilitated the expression of IGF-Ι in liver. At the same time, we utilized human leptin to incubate four tissues in vitro; although most of them had trends similar to those stimulated with tongue sole leptins, there were still some differences, indicating differences among leptin homologs between humans and fishes. To our knowledge, this is the first study to explore the function of tongue sole LepA and LepB within the hypothalamic-pituitary-gonadal axis and liver in vitro. Our results provide a valuable resource and foundation for future studies.

Tissue-specific populations from amniotic fluid-derived mesenchymal stem cells manifest variant in vitro and in vivo properties - Nengqing Liu; Yi Cheng; Ding Wang; Hongmei Guan; Diyu Chen; Juan Zeng; Dian Lu; Yuanshuai Li; Yinghong Yang; Qian Luo; Lifen Zhu; Bin Jiang; et al. (Human Cell, 2023)
Amniotic fluid derived mesenchymal stem cells (AFMSCs), shed along the fetal development, exhibit superior multipotency and immunomodulatory properties compared to MSCs derived from other somatic tissues (e.g., bone marrow and fat). However, AFMSCs display heterogeneity due to source ambiguity, making them an underutilized stem cells source for translational clinical trials. Consequently, there is an urgent need to identify a method to purify the AFMSCs for clinical use. We found that the AFMSCs can be categorized into three distinct groups: kidney-specific AFMSCs (AFMSCs-K), lung-specific AFMSCs (AFMSCs-L), and AFMSCs with an undefined tissue source (AFMSCs-X). This classification was based on tissue-specific gene expression pattern of single cell colony. Additionally, we observed that AFMSCs-X, a minority population within the AFMSCs, exhibited the highest multipotency, proliferation, resistance to senescence and immuno-modulation. Our results showed that AFMSCs-X significantly improved survival rates and reduced bacterial colony forming units (CFU) in cecal ligation and puncture (CLP)-induced septic mice. Therefore, our study introduces a novel classification method to enhance the consistency and efficacy of AFMSCs. These subpopulations, originating from different tissue source, may offer a valuable and innovative resource of cells for regenerative medicine purposes.

A navigation method for paddy field management based on seedlings coordinate information - Shuanglong Wu; Zhaoguo Chen; Kemoh Bangura; Jun Jiang; Xingang Ma; Jiyu Li; Bin Peng; Xiangbao Meng; Long Qi (Computers and Electronics in Agriculture, 2023)

Occurrence of liquid crystal monomers in indoor and outdoor air particle matters (PM10): Implications for human exposure indoors - Li-Li Yao; Jun-Li Wang; Rong-Fa Xu; Ming Zhu; Yan Ma; Bin Tang; Qi-Yuan Lu; Feng-Shan Cai; Xiao Yan; Jing Zheng; Yun-Jiang Yu (Science of The Total Environment, 2023)

Structurally diverse terpenoids from Elephantopus scaber L. and their acetylcholinesterase inhibitory activities - Jia-Yi Li; Shu-Hui Dong; Xin Zhang; Zi-Jian Liu; Jin-Le Hao; Bin Lin; Ming Bai; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

Characteristics of bound biomarkers released from pyrobitumens generated from the cracking of different types of crude oils - Xinyan Fang; Liangliang Wu; Ansong Geng; Yun Li; Wenmin Jiang; Bin Cheng; Shufen Liu; Pufan Wang (Organic Geochemistry, 2023)

Effect of 3D titanium substrates with TiO2 nanotube arrays on photoelectrocatalysis degradation of phenol - He Li; Man Li; Bin Jiang; Ru Liu; Qi Li; Firdoz Shaik (Journal of Environmental Chemical Engineering, 2023)

From an oil with “antifoaming” properties to stabilization for foam: A novel approach for establishing a long-term stable foam system - Fuchao Zhan; Xiaorui Zhou; Ying Jiang; Jing Li; Bin Li (Food Hydrocolloids, 2023)

Genome-wide association mapping combined with gene-based haplotype analysis identify a novel gene for shoot length in rice (Oryza sativa L.) - Tifeng Yang; Jingfang Dong; Junliang Zhao; Longting Zhang; Lian Zhou; Wu Yang; Yamei Ma; Jian Wang; Hua Fu; Jiansong Chen; Wenhui Li; Haifei Hu; et al. (Theoretical and Applied Genetics, 2023)
Key message Genome-wide association mapping revealed a novel QTL for shoot length across multiple environments. Its causal gene, LOC_Os01g68500 , was identified firstly through gene-based haplotype analysis, gene expression and knockout transgenic verification. Abstract Strong seedling vigor is an important breeding target for rice varieties used in direct seeding. Shoot length (SL) is one of the important traits associated with seedling vigor characterized by rapid growth of seedling, which enhance seedling emergence. Therefore, mining genes for SL and conducting molecular breeding help to develop varieties for direct seeding. However, few QTLs for SL have been fine mapped or cloned so far. In this study, a genome-wide association study of SL was performed in a diverse rice collection consisting of 391 accessions in two years, using phenotypes generated by different cultivation methods according to the production practice, and a total of twenty-four QTLs for SL were identified. Among them, the novel QTL qSL-1f on chromosome 1 could be stably detected across all three cultivation methods in the whole population and indica subpopulation. Through gene-based haplotype analysis of the annotated genes within the putative region of qSL-1f , and validated by gene expression and knockout transgenic experiments, LOC_Os01g68500 (i.e., Os01g0913100 in RAP-DB) was identified as the causal gene for SL, which has a single-base variation (C-to-A transversion) in its CDS region, resulting in the significant difference in SL of rice. LOC_Os01g68500 encodes a DUF538 (Domain of unknown function) containing protein, and the function of DUF538 protein gene on rice seedling growth is firstly reported in this study. These results provide a new clue for exploring the molecular mechanism regulating SL, and promising gene source for the molecular breeding in rice.

Genome-Wide Identification and Expression Profiling of the FORMIN Gene Family Implies Their Potential Functions in Abiotic Stress Tolerance in Rice (Oryza sativa) - Bin Li; Zhiye Du; Nan Jiang; Shan He; Yang Shi; Kai Xiao; Lijia Xu; Kaishun Wang; Xin Wang; Longying Wu; Ji Chen; Jin Huang (Plant Molecular Biology Reporter, 2023)

Tree species mixture effect on extracellular enzyme kinetics varies with enzyme type and soil depth in subtropical plantations - Xue-Li Jiang; Rong Mao; Zhong-Liang Li; Fu-Sheng Chen; Bin Xu; Jin He; Yu-Xin Huang; Xiang-Min Fang (Plant and Soil, 2023)

High-fat diet alters intestinal microbiota and induces endoplasmic reticulum stress via the activation of apoptosis and inflammation in blunt snout bream - Kenneth Prudence Abasubong; Guang-Zhen Jiang; Hui-xing Guo; Xi Wang; Xiang-Fei Li; Dong Yan-zou; Wen-bin Liu; Hesham Eed. Desouky (Fish Physiology and Biochemistry, 2023)

17β-Estradiol Mediates Staphylococcus aureus Adhesion in Vaginal Epithelial Cells via Estrogen Receptor α-Associated Signaling Pathway - Lina Yan; Can Rui; Bin Zhuang; Xia Liu; Ting Luan; Lisha Jiang; Zhiyong Dong; Qing Wang; Aiwen Wu; Ping Li; Xinyan Wang; Xin Zeng (Current Microbiology, 2023)

Analysis of the stress field in the reactor vessel of the China Initiative Accelerator Driven System during postulated ULOF and UTOP transients - Zi-Nan Huang; Yun-Xiang Li; Song Li; Bin Xi; You-Peng Zhang; Lu Meng; Di-Si Wang; Bo Liu; Long Gu; Tian-Ji Peng; Lu Zhang; Wei Jiang; et al. (Annals of Nuclear Energy, 2023)

Prioritizing agronomic practices and uncertainty assessment under climate change for winter wheat in the loess plateau, China - Tengcong Jiang; Bin Wang; Xiaoning Duan; De Li Liu; Jianqiang He; Liang He; Ning Jin; Hao Feng; Qiang Yu (Agricultural Systems, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Identification of lead-binding proteins as carriers and potential molecular targets associated with systolic blood pressure - Qiying Nong; Baowei Chen; Yongshun Huang; Yiling Li; Yuanyuan Wang; Lihong Liu; Bin He; Tiangang Luan; Ligang Hu; Guibin Jiang (Chemosphere, 2023)

Applying sheet iron to enhance the treatment efficiency of digested effluent with continuous flow and the corresponding mechanism - Cong Ding; Li-bin Chen; Li-ping Yu; Ru Wang; Lin-jiang Yuan; Lan Wang; Liang-wei Deng (Chemosphere, 2023)

A low-cost 3D reconstruction and measurement system based on structure-from-motion (SFM) and multi-view stereo (MVS) for sewer pipelines - Duo Ma; Hongyuan Fang; Niannian Wang; Gaozhao Pang; Bin Li; Jiaxiu Dong; Xue Jiang (Tunnelling and Underground Space Technology, 2023)

Vehicle emissions in a megacity of Xi'an in China: A comprehensive inventory, air quality impact, and policy recommendation - Qishang Zhou; Jiang Yun; Xiaoping Li; Xu Zhang; Bin Liu; Shuang Zhang; Xueming Zheng; Wen Yue; Xiangyu Li; Weixi Zhang (Urban Climate, 2023)

Stress distribution properties and deformation–fracture mechanisms in hydraulic fracturing of coal - Xiaojie Fang; Caifang Wu; Hewei Zhang; Jiang Han; Geng Li; Bin Gao; Xiuming Jiang (Fuel, 2023)

Interaction and binding mechanism of cyanidin-3-O-glucoside to lysozyme in varying pH conditions: Multi-spectroscopic, molecular docking and molecular dynamics simulation approaches - Hailong Gui; Qiao Jiang; Jinlong Tian; Zang Zhihuan; Shufang Yang; Yiyun Yang; Meili Xin; Min Zhao; Jian Dai; Bin Li (Food Chemistry, 2023)

Hygrothermal parameters measurement and building performance study of modified rammed earth materials - Bin Jiang; Jiaye Tan; Li Wan; Liang Wang; Renzi Lu; Maqi Jiang (Energy and Buildings, 2023)

Super-strong Zn and S atomic terminals in an organic/inorganic hybrid S-scheme polyimide based heterojunction for efficient photocatalytic treatment of mixed pollutant wastewater - Siyi Li; Yushu Wang; Hongli An; Junjun Lin; Shuang Jiang; Tianyong Zhang; Bin Li (Chemical Engineering Journal, 2023)

Utilizing internal resonant scattering to improve photoluminescence energy outcoupling of CsPbBr3/Cs4PbBr6 perovskite phosphor - Zong-Tao Li; Bo-Jia Li; Jia-Sheng Li; Cun-Jiang Song; Xin-Rui Ding; Hai-Long Yuan; Bin-Hai Yu; Yong Tang; Jian-Zhen Ou; Romain Gautier; Hong-Lei Ji; Hao-Chung Kuo (Chemical Engineering Journal, 2023)

Experimental Investigation on the Grouting Diffusion Characteristics and Relative Filling Degree of Chemical Slurry in Fractured Porous Sandstone - Yuan Zhou; Bin Liu; Zhijun Wu; Yalong Jiang; Quansheng Liu; Lei Weng; Mengyi Li (Rock Mechanics and Rock Engineering, 2023)

Application of three-dimensional printing technology in environmental analysis: A review - Junpeng Zhang; Dingyi Wang; Yingying Li; Lihong Liu; Yong Liang; Bin He; Ligang Hu; Guibin Jiang (Analytica Chimica Acta, 2023)

Defects identification and location of underground space for ground penetrating radar based on deep learning - Haobang Hu; Hongyuan Fang; Niannian Wang; Duo Ma; Jiaxiu Dong; Bin Li; Danyang Di; Hongbiao Zheng; Jiang Wu (Tunnelling and Underground Space Technology, 2023)

ID3 regulates progesterone synthesis in bovine cumulus cells through modulation of mitochondrial function - Zi-Bin Liu; Jia-Bao Zhang; Sheng-Peng Li; Wen-Jie Yu; Na Pei; Hai-Tao Jia; Ze Li; Wen-Fa Lv; Jun Wang; Nam-Hyung Kim; Bao Yuan; Hao Jiang (Theriogenology, 2023)

PpeERF115 regulates peach fruit ripening by increasing polyamine turnover through up-regulation of genes involved in polyamine synthesis and catabolism - Xin Cheng; Zhenguo Cui; Yabo Jiang; Yang Chen; Bin Tan; Jun Cheng; Langlang Zhang; Xia Ye; Xiaobei Wang; Haipeng Zhang; Xiaodong Lian; Jidong Li; et al. (Postharvest Biology and Technology, 2023)

Chemical constituents from the leaves of Cinnamomum camphora and their α-glucosidase inhibitory activities - Xing Jiang; Xi-Han Zhang; Yu-Xin Li; Kai Chen; Bin Lin; Tian-Qi Lu; Min Yang; Guang-Tong Chen; Bo-Yi Fan; Wen-Li Wang (Phytochemistry Letters, 2023)

Residual load-bearing capacity of corroded reinforced concrete columns with an annular cross-section - Hua-Peng Chen; Yu Jiang; Wen-Bin Li (Ocean Engineering, 2023)

Preferential extraction of lithium from spent LiCoO2 cathodes and regeneration of LiCoO2 cathodes - Daixiang Wei; Wei Wang; Longjin Jiang; Zhidong Chang; Hira Anwar; Hualei Zhou; Bin Dong; Dekun Gao; Hao Lei; Zhiyi Chen; Wenjun Li (Journal of Environmental Chemical Engineering, 2023)

Experimental study on interlayer interference effect of CBM commingled production in a multi-pressure system under output control mode - Qixian Li; Longyong Shu; Jiang Xu; Shoujian Peng; Fazhi Yan; Zhonggang Huo; Du Liu; Chao Li; Bin Zhou (Fuel, 2023)

Oral bovine serum albumin administration alleviates inflammatory signals and improves antioxidant capacity and immune response under thioacetamide stress in blunt snout bream fed a high-calorie diet - Kenneth Prudence Abasubong; Guang-Zhen Jiang; Hui-xing Guo; Xi Wang; Yang-yang Huang; Yong-Jun Dai; Xiang-Fei Li; Yan-zou Dong; Ndakalimwe Naftal Gabriel; Wen-bin Liu (Fish & Shellfish Immunology, 2023)

Theoretical calculation-guided engineering of Fe-Mn based dual-center single-atom catalysts for synergistic tumor therapy - Xueyang Fang; Decai Yang; Xianlin Wu; Kwok-Ho Lui; Xin Li; Wai-Sum Lo; Chenxi Li; Yuanyuan Zhang; Guohui Nie; Lijun Jiang; Yanjuan Gu; Bin Zhang; et al. (Chemical Engineering Journal, 2023)

New insights into the structure-activity relationship for CO2 capture by tertiary amines from the experimental and quantum chemical calculation perspectives - Ge Gao; Bin Xu; Xiaoyi Gao; Wufeng Jiang; Zhenghong Zhao; Xiaoshan Li; Cong Luo; Fan Wu; Liqi Zhang (Chemical Engineering Journal, 2023)

Nutrient resorption and coupling relationships in two plant species with sulfur addition: A two-year study in a meadow - Xue Feng; Ruzhen Wang; Tianpeng Li; Jiangping Cai; Heyong Liu; Bin Wang; Xiaotao Lü; Yong Jiang (Plant and Soil, 2023)

p-Nrf2/HO-1 Pathway Involved in Methamphetamine-induced Executive Dysfunction through Endoplasmic Reticulum Stress and Apoptosis in the Dorsal Striatum - Tao Wei; Jun-Da Li; Yu-Jing Wang; Wei Zhao; Fan Duan; Yan Wang; Ling-Ling Xia; Zhao-Bin Jiang; Xun Song; Yu-Qiong Zhu; Wen-Yi Shao; Ze Wang; et al. (Neurotoxicity Research, 2023)

Neuroglobin Facilitates Neuronal Oxygenation through Tropic Migration under Hypoxia or Anemia in Rat: How Does the Brain Breathe? - Chun-Yang Li; Hai-Feng Jiang; Li Li; Xiao-Jing Lai; Qian-Rong Liu; Shang-Bin Yu; Cheng-La Yi; Xiao-Qian Chen (Neuroscience Bulletin, 2023)

Preemptive QP001, a fast-acting meloxicam formulation, provides analgesia and reduces opioid consumption following abdominal surgery: a randomized controlled trial - Yingyong Zhou; Bin Wang; Kaiming Duan; Zhihong Bai; Xianwen Hu; Mingjun Xu; Xiaohong Li; Yuanli Gao; Jiangang Li; Mengchang Yang; Ying Zhang; Wei Zhang; et al. (Inflammopharmacology, 2023)

Optical properties and molecular composition of wintertime atmospheric water-soluble organic carbon in different coastal cities of eastern China - Haibiao Chen; Caiqing Yan; Qinglong Fu; Xinfeng Wang; Jiao Tang; Bin Jiang; Honglei Sun; Tiancheng Luan; Qiaoyun Yang; Qianbiao Zhao; Jun Li; Gan Zhang; et al. (Science of The Total Environment, 2023)

Distribution of heavy metals in coastal sediments under the influence of multiple factors: A case study from the south coast of an industrialized harbor city (Tangshan, China) - Wenqin Jiang; Hongxian Chu; Yiyao Liu; Bin Chen; Yongcai Feng; Jixuan Lyu; Jidong Yuan; Lixin Wang; Jialin Li; Weiguo Hou (Science of The Total Environment, 2023)

Vegetation structural shift tells environmental changes on the Tibetan Plateau over 40 years - Yanfen Wang; Kai Xue; Ronghai Hu; Boyang Ding; Hong Zeng; Ruijin Li; Bin Xu; Zhe Pang; Xiaoning Song; Congjia Li; Jianqing Du; Xiuchun Yang; et al. (Science Bulletin, 2023)

Revealing the mechanism underlying the effects of γ-aminobutyric acid-dioscorin interactions on dioscorin structure and emulsifying properties by molecular dynamic simulations - Yun-long Chen; Hao-nan Nie; Hui Dong; Qi Gao; Xue Peng; Ning Wang; Xueling Chen; Qing-zheng Liu; Jiang-kuo Li; Xiang-bin Xu; You-lin Xue (Food Research International, 2023)

The comparison between zein-anthocyanins complex and nanoparticle systems: Stability enhancement, interaction mechanism, and in silico approaches - Zhiying Li; Yidi Wang; Baoge Song; Jiaxin Li; Yiwen Bao; Qiao Jiang; Yi Chen; Shufang Yang; Yiyun Yang; Jinlong Tian; Bin Li (Food Chemistry, 2023)

Utilization of ultrasound and glycation to improve functional properties and encapsulated efficiency of proteins in anthocyanins - Huijun Cui; Zhihuan Zang; Qiao Jiang; Yiwen Bao; Yunan Wu; Jiaxin Li; Yi Chen; Xiaoli Liu; Shufang Yang; Xu Si; Bin Li (Food Chemistry, 2023)

Whey protein isolate nanofibrils as emulsifying agent to improve printability of Cheddar cheese for 3D printing - Dongxu Wang; Jiaxuan Guo; Yexuan Wang; Yue Yang; Bin Jiang; Dongmei Li; Zhibiao Feng; Chunhong Liu (Food Hydrocolloids, 2023)

Fine lithospheric structure controlling Meso-Cenozoic tectono-magmatism in the South China Block: Inference from a multidisciplinary analysis - Feiyu Zhao; Yanhui Suo; Lijun Liu; Xianzhi Cao; Sanzhong Li; Suhua Jiang; Juzhi Deng; Mengxue Dai; Ying Liu; Yaping Hu; Shuzhong Sheng; Bin Hu (Earth-Science Reviews, 2023)

Hydrogen spillover in alkaline solutions for effective nitrogen fixation - Chang Ning Sun; Yan Bin Qu; Zhi Li Wang; Qing Jiang (Chemical Engineering Journal, 2023)

Photocatalytic lignin oils and CO2 upgradation to diesel precursors and syngas over engineered CdSe quantum dots - Heyan Jiang; Zujie Hu; Qian Zhou; Yue Li; Chuan Gan; Meilin Sheng; Xue Gao; Bin Sun (Chemical Engineering Journal, 2023)

Deformation response and mechanical analysis of the Wangjiashan landslide in Baihetan Hydropower Station, China, during initial impoundment - Chen Xiaoting; Li Renjiang; Hu Bin; Yin Yueping; Yang Jianyuan; Jiang Shu; Qin Panpan; Huang Bolin (Bulletin of Engineering Geology and the Environment, 2023)

Genome-wide identification and analysis of MIKC-type MADS-box genes expression in Chimonanthus salicifolius - Fang-Fang Gui; Ge-Ge Jiang; Bin Dong; Shi-Wei Zhong; Zheng Xiao; Qiu Fang; Yi-Guang Wang; Li-Yuan Yang; Hongbo Zhao (Genes & Genomics, 2023)

Current knowledge of anthocyanin metabolism in the digestive tract: absorption, distribution, degradation, and interconversion - Hailong Gui; Lijun Sun; Ruihai Liu; Xu Si; Dongnan Li; Yuehua Wang; Chi Shu; Xiyun Sun; Qiao Jiang; Yanyan Qiao; Bin Li; Jinlong Tian (Critical Reviews in Food Science and Nutrition, 2023)

A Coupled Overlapping Finite Element Method for Analyzing Underwater Acoustic Scattering Problems - Bin Jiang; Jian Yu; Wei Li; Yingbin Chai; Qiang Gui (Journal of Marine Science and Engineering, 2023)
It is found that the classic finite element method (FEM) requires much time for adequate meshes to acquire satisfactory numerical solutions, and is restricted to acoustic problems with low and middle frequencies. In this work, a coupled overlapping finite element method (OFEM) is employed by combining the overlapping finite element and the modified Dirichlet-to-Neumann (mDtN) boundary condition to solve underwater acoustic scattering problems. The main difference between the OFEM and the FEM lies in the construction of the local field approximation. In the OFEM, virtual nodes are utilized to form the partition of unity functions while no degree of freedom is assigned to these virtual nodes, which suppresses the linear dependence issue in other generalized finite element methods. Moreover, the user-defined enrichment functions can be flexibly utilized in the local field, and thus the numerical dispersions can be significantly mitigated. To truncate the infinite problem domain and satisfy the Sommerfeld radiation condition, an artificial boundary is constructed by incorporating the mDtN technique. Several numerical examples are studied and it is shown that the proposed method can greatly diminish the numerical error and is insensitive to distorted meshes, indicating that the proposed method is promising in predicting underwater acoustic scattering.

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Reproductive and developmental toxicity assessments of LPM3480392, a novel mu opioid receptor biased agonist in rats - Bin Liu; Hongyu Chen; Chunmei Li; Yana Guan; Wanglin Jiang; Hanrong Wang; Wei Guo; Wen Wen; Xiaobo Cen; Hongbo Wang; Jingwei Tian (Reproductive Toxicology, 2023)

Anion exchange resin/quartz sand bi-layer composite dynamic membranes in ultrafiltration for algae-laden water treatment - Cong Ma; Xinbin Guo; Tong Li; Xi Jiang; Liang Wang; Bin Zhao; Zhaohui Zhang (Process Safety and Environmental Protection, 2023)

Investigation of the peak punch-through capacity of spudcan on sand overlying spatially variable clay - Jiang Tao Yi; Shi Jie Xu; Xiao Bin Li; Qing Shan Yang; Si Yu Li (Ocean Engineering, 2023)

Determining the degradation mechanism and application potential of benzopyrene-degrading bacterium Acinetobacter XS-4 by screening - Xiaoshuang Zou; Qi Su; Qianwen Yi; Ling Guo; Diyong Chen; Bin Wang; Yancheng Li; Jiang Li (Journal of Hazardous Materials, 2023)

The isolation of anthocyanin monomers from blueberry pomace and their radical-scavenging mechanisms in DFT study - Hailong Gui; Jian Dai; Jinlong Tian; Qiao Jiang; Ye Zhang; Guangyu Ren; Baoge Song; Mingshuang Wang; Mihereban Saiwaidoula; Wenjiang Dong; Bin Li (Food Chemistry, 2023)

First transcriptome profiling in gill and hepatopancrease tissues of Metapenaeus ensis in response to acute ammonia-N stress - Yun-Dong Li; Meng-Ru Si; Shi-Gui Jiang; Qi-Bin Yang; Song Jiang; Li-Shi Yang; Jian-Hua Huang; Fa-Lin Zhou (Fish & Shellfish Immunology, 2023)

Construction of Bi2MoO6/CoWO4 Z-scheme heterojunction for high-efficiency photocatalytic degradation of norfloxacin under visible light: Performance and mechanism insights - Huaikai Yang; Jiang Li; Qi Su; Bin Wang; Zichun Zhang; Yongheng Dai; Yancheng Li; Li'an Hou (Chemical Engineering Journal, 2023)

Micro-mechanism insights into the adsorption of anionic dyes using quaternary ammonium-functionalised chitosan aerogels - Nan Du; Li-Yuan Huang; Yan-Shu Xiong; Run Tian; Jiang-Yu Yin; Dan-Yu Cao; Dong-Bin Hu; Hai-Qin Lu; Wen Li; Kai Li (Carbohydrate Polymers, 2023)

Aerobic co-composting of mature compost with cattle manure: Organic matter conversion and microbial community characterization - Zichun Zhang; Huaikai Yang; Bin Wang; Chao Chen; Xiaoshuang Zou; Tuo Cheng; Jiang Li (Bioresource Technology, 2023)

Effects of climate change and anthropogenic activity on ranges of vertebrate species endemic to the Qinghai–Tibet Plateau over 40 years - Dechun Jiang; Xumao Zhao; Jordi López‐Pujol; Zhiqiang Wang; Yanhua Qu; Yanming Zhang; Tongzuo Zhang; Dayong Li; Ke Jiang; Bin Wang; Chaochao Yan; Jia‐Tang Li (Conservation Biology, 2023)
Over the past 40 years, the climate has been changing and human disturbance has increased in the vast Qinghai–Tibet Plateau (QTP). These 2 factors are expected to affect the distribution of a large number of endemic vertebrate species. However, quantitative relationships between range shifts and climate change and human disturbance of these species in the QTP have rarely been evaluated. We used occurrence records of 19 terrestrial vertebrate species (birds, mammals, amphibians, and reptiles) occurring in the QTP from 1980 to 2020 to quantify the effects of climate change and anthropogenic impacts on the distribution of these 4 taxonomic groups and estimated species range changes in each species. The trend in distribution changes differed among the taxonomic groups, although, generally, ranges shifted to central QTP. Climate change contributed more to range variation than human disturbance (the sum of the 4 climatic variables contributed more than the sum of the 4 human disturbance variables for all 4 taxonomic groups). Suitable geographic range increased for most mammals, amphibians, and reptiles (+27.6%, +18.4%, and +27.8% on average, respectively), whereas for birds range decreased on average by 0.9%. Quantitative evidence for climate change and human disturbance associations with range changes for endemic vertebrate species in the QTP can provide useful insights into biodiversity conservation under changing environments.

A novel continuous all-weather photo-electric synergistic treatment system for refractory organic compounds and its application in degrading enrofloxacin - Bin Qi; Tiantian Chen; Tongfei Zhang; Ruixue Jiang; Wenming Zhang; Xiaochen Li (Chemosphere, 2023)

TRPC6 promotes daunorubicin-induced mitochondrial fission and cell death in rat cardiomyocytes with the involvement of ERK1/2-DRP1 activation - Li-Xia Xu; Rui-Xing Wang; Jian-Feng Jiang; Gao-Cheng Yi; Jin-Jin Chang; Rui-Lan He; Hai-Xia Jiao; Bin Zheng; Long-Xin Gui; Jun-Jin Lin; Zhi-Hong Huang; Mo-Jun Lin; et al. (Toxicology and Applied Pharmacology, 2023)

The distinct plastisphere microbiome in the terrestrial-marine ecotone is a reservoir for putative degraders of petroleum-based polymers - Guan Pang; Xuesong Li; Mingyue Ding; Siqi Jiang; Peijie Chen; Zheng Zhao; Renwei Gao; Bin Song; Xiaowei Xu; Qirong Shen; Feng M. Cai; Irina S. Druzhinina (Journal of Hazardous Materials, 2023)

Construction and characterization of Pickering emulsions stabilized by soy protein hydrolysate microgel particles and quercetin-loaded performance in vitro digestion - Jinjie Yang; Bin Zhu; Keyang Lu; Jingjing Dou; Yijie Ning; Huan Wang; Yang Li; Baokun Qi; Lianzhou Jiang (Food Research International, 2023)

WITHDRAWN: Lithospheric density structure beneath the South China Block and its tectonic implications: Insights from joint inversion of multiple geophysical observations - Feiyu Zhao; Yanhui Suo; Lijun Liu; Sanzhong Li; Xianzhi Cao; Juzhi Deng; Suhua Jiang; Mengxue Dai; Bin Hu (Earth-Science Reviews, 2023)

Combined photothermal and photodynamic therapy enhances ferroptosis to prevent cancer recurrence after surgery using nanoparticle-hydrogel composite - Lu Chen; Gaojie Chen; Kang Hu; Lianxu Chen; Zhiyong Zeng; Bin Li; Guohua Jiang; Yang Liu (Chemical Engineering Journal, 2023)

Climate and topography controls on soil water-stable aggregates at regional scale: Independent and interactive effects - Wei-Chun Zhang; Wei Wu; Jiang-Wen Li; Hong-Bin Liu (CATENA, 2023)

Activation of cellulose with CO2 and/or H2O: Evolution of functionalities of the biochar and environmental impacts - Cong Ming; Yuchen Jiang; Chao Li; Qifeng Chen; Shu Zhang; Shuang Wang; Bin Li; Zhenhua Cui; Yonggui Tang; Xun Hu (Biomass and Bioenergy, 2023)

Novel biphasic mechanism of the canonical Wnt signalling component PYGO2 promotes cardiomyocyte differentiation from hUC-MSCs - Yan Shi; Bin Qin; Xiongwei Fan; Yongqing Li; Yuequn Wang; Wuzhou Yuan; Zhigang Jiang; Ping Zhu; Jimei Chen; Yu Chen; Fang Li; Yongqi Wan; et al. (Cell and Tissue Research, 2023)
Human umbilical cord–derived mesenchymal stem cells (hUC-MSCs) are used to regenerate the myocardium during cardiac repair after myocardial infarction. However, the regulatory mechanism underlying their ability to form mesodermal cells and differentiate into cardiomyocytes remains unclear. Here, we established a human-derived MSCs line isolated from healthy umbilical cords and established a cell model of the natural state to examine the differentiation of hUC-MSCs into cardiomyocytes. Quantitative RT-PCR, western blotting, immunofluorescence, flow cytometry, RNA Seq, and inhibitors of canonical Wnt signalling were used to detect the germ-layer markers T and MIXL1 ; the markers of cardiac progenitor cells MESP1 , GATA4 , and NKX2.5 and the cardiomyocyte-marker cTnT to identify the molecular mechanism associated with PYGO2, a key component of the canonical Wnt signalling pathway that regulates the formation of cardiomyocyte-like cells. We demonstrated that PYGO2 promotes the formation of mesodermal-like cells and their differentiation into cardiomyocytes through the hUC-MSC-dependent canonical Wnt signalling by promoting the early-stage entry of β-catenin into the nucleus. Surprisingly, PYGO2 did not alter the expression of the canonical-Wnt, NOTCH, or BMP signalling pathways during the middle–late stages. In contrast, PI3K-Akt signalling promoted hUC-MSCs formation and their differentiation into cardiomyocyte-like cells. To the best of our knowledge, this is the first study to demonstrate that PYGO2 uses a biphasic mechanism to promote cardiomyocyte formation from hUC-MSCs.

Correction to: Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2023)

Characteristics of antibiotic resistance genes and microbial community distribution in Wanfeng Lake, upper Pearl River, China - Yuntao Zhang; Jiang Li; Tianyu Wu; Kai Ma; Zhentao Cheng; Qianwen Yi; Yongheng Dai; Bin Wang; Yu Chen; Bin Wang; Xia Hu; Aijiang Yang; et al. (Environmental Science and Pollution Research, 2023)

Extraction of scattered and precious metals from lead anode slime: A short review - Zhe Gao; Xiangfeng Kong; Bin Yang; Jiafei Yi; Kai Fan; Tongyu San; Keke Cheng; Shaoxiong Li; Dachun Liu; Baoqiang Xu; Wenlong Jiang (Hydrometallurgy, 2023)

Cu(Ⅰ) anchoring in MOF-808 as a stable catalyst in ultra-deep oxidation desulfurization - Juan Li; Xiaolei Jiang; Mingyuan Zhu; Bin Dai (Fuel, 2023)

Effects of dietary oat supplementation on carcass traits, muscle metabolites, amino acid profiles, and its association with meat quality of Small-tail Han sheep - Li-wei Wang; Shao-feng Su; Jie Zhao; Xiao-long He; Shao-yin Fu; Biao Wang; Yun-fei Wang; Da-qing Wang; Na-na Yun; Xin Chen; Damien P Belobrajdic; Terigele; et al. (Food Chemistry, 2023)

Cooperative simultaneous inversion of satellite-based real-time PM2.5 and ozone levels using an improved deep learning model with attention mechanism - Xing Yan; Chen Zuo; Zhanqing Li; Hans W. Chen; Yize Jiang; Bin He; Huiming Liu; Jiayi Chen; Wenzhong Shi (Environmental Pollution, 2023)

Efficient photocatalytic hydrogen evolution reaction promoted via a synergistic strategy of S-scheme heterojunction structure combined with surface plasmon resonance effect - Siyi Li; Yushu Wang; Jingchao Wang; Chin Ho Kirk; Haimei Wang; Jianguo Sun; Yu Liu; Binbin Liu; Tianyong Zhang; Shuang Jiang; John Wang; Bin Li (Chemical Engineering Journal, 2023)

Bioinformatic and functional analysis of OsDHN2 under cadmium stress - Wen-jun Jiang; Meng-ting Wang; Zhi-ye Du; Jia-hao Li; Yang Shi; Xin Wang; Long-ying Wu; Ji Chen; Min Zhong; Ju Yang; Bin-hua Hu; Jin Huang (Functional & Integrative Genomics, 2023)

Genomic variations in polymyxin-resistant Pseudomonas aeruginosa clinical isolates and their effects on polymyxin resistance - Yuan Liang; Jie Li; Yunmin Xu; Yuan He; Bo Jiang; Chunyan Wu; Bin Shan; Hongqiong Shi; Guibo Song (Brazilian Journal of Microbiology, 2023)

Effect of warming on rice yield and methane emissions in a Chinese tropical double-rice cropping system - Nan Zhang; Haoyu Qian; Huixin Li; Junqi Tang; Taotao Yang; Zhuoshu Liu; Yunlong Liu; Bin Zhang; Yanfeng Ding; Yu Jiang (Agriculture, Ecosystems & Environment, 2023)

Another Year of Record Heat for the Oceans - Lijing Cheng; John Abraham; Kevin E. Trenberth; John Fasullo; Tim Boyer; Michael E. Mann; Jiang Zhu; Fan Wang; Ricardo Locarnini; Yuanlong Li; Bin Zhang; Fujiang Yu; et al. (Advances in Atmospheric Sciences, 2023)
Changes in ocean heat content (OHC), salinity, and stratification provide critical indicators for changes in Earth’s energy and water cycles. These cycles have been profoundly altered due to the emission of greenhouse gasses and other anthropogenic substances by human activities, driving pervasive changes in Earth’s climate system. In 2022, the world’s oceans, as given by OHC, were again the hottest in the historical record and exceeded the previous 2021 record maximum. According to IAP/CAS data, the 0–2000 m OHC in 2022 exceeded that of 2021 by 10.9 ± 8.3 ZJ (1 Zetta Joules = 10 21 Joules); and according to NCEI/NOAA data, by 9.1 ± 8.7 ZJ. Among seven regions, four basins (the North Pacific, North Atlantic, the Mediterranean Sea, and southern oceans) recorded their highest OHC since the 1950s. The salinity-contrast index, a quantification of the “salty gets saltier—fresh gets fresher” pattern, also reached its highest level on record in 2022, implying continued amplification of the global hydrological cycle. Regional OHC and salinity changes in 2022 were dominated by a strong La Niña event. Global upper-ocean stratification continued its increasing trend and was among the top seven in 2022.

A LSSVR Interactive Network for AUV Motion Control - Chunmeng Jiang; Lei Wan; Hongrui Zhang; Jian Tang; Jianguo Wang; Shupeng Li; Long Chen; Gongxing Wu; Bin He (Journal of Marine Science and Engineering, 2023)
In view of the requirements on control precision of autonomous underwater vehicles (AUVs) in different operations, the improvement of AUV motion control accuracy is the focus of this paper. In regard to the unsatisfying robustness of traditional control methods, an interactive network based on Least Square Support Vector Regression (LSSVR) is therefore put forward. The network completed the identification of the strong nonlinear AUV dynamic characteristics based on the LSSVR theory and by virtue of the interactions between the offline and online modules, it achieved offline design and online optimization of the AUV control law. In addition to contrastive numerical simulations and sea trials with the classic S-plane method in AUV velocity and heading control, the LSSVR network was also tested in path following and long-range cruise. The precision and robustness and of the proposed network were verified by the high-accuracy control results of the aforesaid simulations and trials. The network can be of practical use in AUV control especially under unfamiliar water conditions with access to a limited number of control samples or little information of the operation site.

Occurrence and risk levels of antibiotic pollution in the coastal waters of eastern China - Ning Xu; Yi Shen; Lei Jiang; Bin Jiang; Ying Li; Qingbin Yuan; Yunhai Zhang (Environmental Science and Pollution Research, 2023)

Pyrolysis of banana peel with microwave and furnace as the heating sources: The distinct impacts on evolution of the pyrolytic products - Yuchen Jiang; Chao Li; Lijun Zhang; Mengjiao Fan; Shu Zhang; Wenran Gao; Bin Li; Shuang Wang; Xun Hu (Process Safety and Environmental Protection, 2023)

Effects of transglutaminase and glucose oxidase on the properties of frozen dough: Water distribution, rheological properties, and microstructure - Wen-Tao Guo; Xue-Fei Yang; Yi-Shun Ji; Bin Hu; Wan-Guang Li; Xi-Yang Zhong; Shao-Tong Jiang; Zhi Zheng (Journal of Cereal Science, 2023)

pH and ultrasound driven structure-function relationships of soy protein hydrolysate - Jinjie Yang; Bin Zhu; Jingjing Dou; Yijie Ning; Huan Wang; Yuyang Huang; Yang Li; Baokun Qi; Lianzhou Jiang (Innovative Food Science & Emerging Technologies, 2023)

Preparation of high-quality alkylated gasoline with low alkane-to-alkene ratio catalyzed by polyether-based Brønsted-Lewis acidic deep eutectic solvent - Ying-Bin Jiang; Feng-Li Yu; Bing Yuan; Cong-Xia Xie; Shi-Tao Yu (Fuel, 2023)

Effects of spray drying and freeze drying on the structure and emulsifying properties of yam soluble protein: A study by experiment and molecular dynamics simulation - Hao-nan Nie; Hui Dong; Yun-long Chen; Miao-miao Hao; Jia-nan Chen; Zi-cheng Tang; Qing-zheng Liu; Jiang-kuo Li; Xiang-bin Xu; You-lin Xue (Food Chemistry, 2023)

Evaluating the performance of a novel ventilated embankment structure in warm permafrost regions by numerical simulation - Zhanyuan Zhu; Zonghang He; Fei Luo; Bin Luo; Chenxuan Tang; Zuyin Zou; Zihong Guo; Weimin Xiao; Xiangang Jiang; Lin Li (Cold Regions Science and Technology, 2023)

Synthesis and biological evaluation of esculetin derivatives as potential anti-HBV agents - Zhen Ye; Tong-Shi-Yao Zhao; Shan-Bin Li; Xian-Li Zhou; Qin Luo; Jiang-Ke Qin; Cheng-Qin Liang; Ping Wang; Guang-Bo Ge (Medicinal Chemistry Research, 2023)

Quercetin alleviates tubulointerstitial inflammation by inhibiting exosomes-mediated crosstalk between tubular epithelial cells and macrophages - Di Yin; Jing-Yuan Cao; Yan Yang; Zhong-Tang Li; Hong Liu; Tao-Tao Tang; Wei-Jie Ni; Yi-Lin Zhang; Wei Jiang; Yi Wen; Zuo-Lin Li; Jing Zhao; et al. (Inflammation Research, 2023)

Elevated Interleukin-37 Associated with Dengue Viral Load in Patients with Dengue Fever - Jun-Ai Zhang; Jia-Jun Wang; Wen-Ting Zhang; Li Zhang; Bi-Ying Zheng; Gan-Bin Liu; Jing Liang; Yuan-Bin Lu; Xian-Jin Wu; Shu-Ying Yao; Guo-Ying Chen; Yun-Qi Xie; et al. (Current Microbiology, 2023)
Dengue remains a public health issue worldwide. Similar to chronic infectious diseases, stimulation of cytokine production is not enough to drive immune effector cells for effective virus clearance. One possible mechanism is the virus induces a large number of negative stimulatory cytokines inhibiting immune response. Interleukin 37 (IL-37) plays a crucial regulatory role in infection and immunity, inhibits innate and adaptive immunity as an anti-inflammatory cytokine by inhibiting proinflammatory mediators and pathways. To date, there are few studies reporting correlations between dengue fever (DF) and IL-37. In this study we found that the serum IL-37b and IL-37b-producing monocytes in patients were significantly increased in DF patients. A majority of the IL-37b produced by DF patients was produced by monocytes, not lymphocytes. Increased levels of IL-6, IL-10, and IFN-α were also found in DF patients. However, we failed to detect IL-1β, IL-17A and TNF-α in plasma, because of off-target. In our study, there was no relation between IL-6, IL-10, and IFN-α expressions and IL-37b in serum ( P > 0.05). The IL-37b-producing monocytes were negatively correlated with the level of IFN-α in serum and platelet count, and positively correlated with lymphocytes percentage ( P < 0.05, respectively). Additionally, serum DENV nonstructural protein 1 levels were positively correlated with monocytes percentages ( P < 0.05). Our data represents findings for IL-37b expression and its potential mechanisms in DF patients’ immune response.

Cyanidin-3- O -glucoside and its phenolic metabolites ameliorate intestinal diseases via modulating intestinal mucosal immune system: potential mechanisms and therapeutic strategies - Zhen Cheng; Xu Si; Hui Tan; Zhihuan Zang; Jinlong Tian; Chi Shu; Xiyun Sun; Zhiying Li; Qiao Jiang; Xianjun Meng; Yi Chen; Bin Li; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Molecular tracers, mass spectral tracers and oxidation of organic aerosols emitted from cooking and fossil fuel burning sources - Chengrui Liang; Shuxiao Wang; Ruolan Hu; Guanghan Huang; Jinzi Xie; Bin Zhao; Yuyang Li; Wenfei Zhu; Song Guo; Jingkun Jiang; Jiming Hao (Science of The Total Environment, 2023)

Insight into tetrahydrofuran lignans from Isatis indigotica fortune with neuroprotective and acetylcholinesterase inhibitor activity - Yu-Fei Xi; Ming Bai; Xin Zhang; Zi-Lin Hou; Bin Lin; Guo-Dong Yao; Li-Li Lou; Xiao-Bo Wang; Shao-Jiang Song; Xiao-Xiao Huang (Phytochemistry, 2023)

Numerical simulation of failure properties of interbedded hydrate-bearing sediment and their implications on field exploitation - Mingtao Chen; Yanlong Li; Penghui Zhang; Guigang Yu; Zhun Zhang; Yajuan Zhang; Haiyang Jiang; Bin Gong; Nengyou Wu (Ocean Engineering, 2023)

A critical review on graphene oxide membrane for industrial wastewater treatment - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2023)

A new automatic quality control system for ocean profile observations and impact on ocean warming estimate - Zhetao Tan; Lijing Cheng; Viktor Gouretski; Bin Zhang; Yanjun Wang; Fuchao Li; Zenghong Liu; Jiang Zhu (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Salvia miltiorrhiza polysaccharide and its related metabolite 5-methoxyindole-3-carboxaldehyde ameliorate experimental colitis by regulating Nrf2/Keap1 signaling pathway - Yu-Ping Fu; Xi Peng; Chao-Wen Zhang; Quan-Xing Jiang; Cen-Yu Li; Berit Smestad Paulsen; Frode Rise; Chao Huang; Bin Feng; Li-Xia Li; Xing-Fu Chen; Ren-Yong Jia; et al. (Carbohydrate Polymers, 2023)

Nonlinear dynamical modeling of neural activity using volterra series with GA-enhanced particle swarm optimization algorithm - Siyuan Chang; Jiang Wang; Yulin Zhu; Xile Wei; Bin Deng; Huiyan Li; Chen Liu (Cognitive Neurodynamics, 2023)

A global gridded ocean salinity dataset with 0.5° horizontal resolution since 1960 for the upper 2000 m - Guancheng Li; Lijing Cheng; Yuying Pan; Gongjie Wang; Hailong Liu; Jiang Zhu; Bin Zhang; Huanping Ren; Xutao Wang (Frontiers in Marine Science, 2023)
A gridded salinity dataset with high resolution is essential for investigating global ocean salinity variability and understanding its role in climate and the ocean ecosystem. In this study, a new version of the Institute of Atmospheric Physics gridded salinity dataset with a higher resolution (0.5° by 0.5°) is provided by using a revised ensemble optimal interpolation scheme with a dynamic ensemble. The performance of this dataset is evaluated using “subsample test” and the high-resolution satellite-based data. Compared with the previous 1° by 1° resolution IAP product, the new dataset is more capable of representing regional salinity changes with the meso-scale and small-scale signals (i.e., in the coastal and boundary currents regions), meanwhile, maintains the large-scale structure and variability. Therefore, the new dataset complements the previous data product. Besides, the new dataset is compared with in situ observations and several international salinity products for the salinity multiscale variabilities and patterns. The comparison shows the smaller magnitude of mean difference and Root-mean-square deviation (RMSD) in basin scale for the new dataset, some differences in strength and fine structure of the “fresh gets fresher, salty gets saltier” surface and subsurface salinity pattern amplification trends from 1980 to 2017, a broad similarity for the salinity changes associated with El Niño-Southern Oscillation (ENSO) and a consistent salinity dipole mode in the tropical Indian Ocean (S-IOD). These results support the future use of gridded salinity data.

Improving the humification by additives during composting: A review - Li Chen; Yaoning Chen; Yuanping Li; Yihuan Liu; Hongjuan Jiang; Hui Li; Yu Yuan; Yanrong Chen; Bin Zou (Waste Management, 2023)

Cascading effects of Pb on the environmental and symbiotic microbiota and tadpoles' physiology based on field data and laboratory validation - Wei Zhu; Yan Lv; Qun-De Zhang; Li-Ming Chang; Qi-Heng Chen; Bin Wang; Jian-Ping Jiang (Science of The Total Environment, 2023)

Transformation of hydroxylamine to nitrosated and nitrated products during advanced oxidation process - Zi-jun Dong; Cheng-chun Jiang; Yue Zhou; Jie-bin Duan; Li-hong Wang; Su-yan Pang; Jin Jiang; Xiao-hui Sun (Journal of Hazardous Materials, 2023)

Storage stability of scallop (Patinopecten yessoensis) male gonad hydrolysates/κ-carrageenan composite hydrogels embeded curcumin - Jia-Nan Yan; Xin-Yu Jiang; Lin Li; Wen Sun; Bin Lai; Hai-Tao Wu (Food Hydrocolloids, 2023)

Experimental and two-scale numerical studies on the behavior of prestressed concrete-steel hybrid wind turbine tower models - Zeyu Li; Bin Xu; Jiang Wang; Hongbing Chen; Hanbin Ge (Engineering Structures, 2023)

GRK5 Deficiency in the Hippocampus Leads to Cognitive Impairment via Abnormal Microglial Alterations - Hongtao Shen; Tianzhen Zhang; Yao Ji; Yu Zhang; Yongxiang Wang; Yuling Jiang; Xiongjin Chen; Qiuhao Liang; Kefeng Wu; Yunfeng Li; Xingyu Lu; Lili Cui; et al. (Molecular Neurobiology, 2023)

Transient analysis of the CiADS reactor core loaded with nitride fuel - Bo Liu; Song Li; You-Peng Zhang; Janne Wallenius; Bin Xi; Long Gu; Jin-Yang Li; Di-Si Wang; Wei Jiang; Lu Zhang (Annals of Nuclear Energy, 2023)

Contribution of the TGFβ signaling pathway to pigmentation in sea cucumber (Apostichopus japonicus) - Linlin Yao; Bin Zhao; Qi Wang; Xuyang Jiang; Sha Han; Wei Hu; Chenglin Li (Frontiers in Marine Science, 2023)
Pigmentation mediated by the transforming growth factor β (TGFβ) signaling pathway is a key trait for understanding environmental adaptability and species stability. In this study, TGFβ signaling pathway members and their expression patterns in different color morphs of the sea cucumber Apostichopus japonicus were evaluated. Using a bioinformatics approach, 22 protein sequences of TGFβ signaling pathway members in A. japonicus were classified, including 14 that were identified for the first time in the species, including 7 ligands, 6 receptors, and 1 R-Smad. We further evaluated mRNA expression data for different color morphs and pigmentation periods. These results support the hypothesis that both subfamilies of the TGFβ superfamily, i.e., the TGFβ/activin/Nodal and BMP/GDF/AMH subfamilies, are involved in the regulation of pigmentation in A. japonicus . The former subfamily was complete and contributes to the different color morphs. The BMP/GDF/AMH subfamily was incomplete. BMP2/4-induced differentiation of white adipocytes was regulated by the BMP2/4–ACVR2A–Smad1 signaling pathway. These findings provide insight into the TGFβ family in early chordate evolution as well as the molecular basis of color variation in an economically valuable species.

Recycling of ferronickel slag tailing in cementitious materials: Activation and performance - Lin Chi; Shuang Lu; Zhenming Li; Chendong Huang; Hui Jiang; Bin Peng (Science of The Total Environment, 2023)

RETRACTED: Boronic acid-modified bacterial cellulose microspheres as packing materials for enveloped virus removal - Zhiyang Lin; Linhan Li; Kaige Song; Bin Yang; Guoqing Zhou; Gengrong Zhang; Jiang Teng; Erlong Wang; Xiaoqiang Liu; Fei Ling; Gaoxue Wang; Tianqiang Liu (Science of The Total Environment, 2023)

Synergy of directional oxidation and vacuum gasification for green recovery of As2O3 from arsenic-containing hazardous secondary resources - Kai Fan; Xiangfeng Kong; Jiafei Yi; Zhe Gao; Shaoxiong Li; Bin Yang; Baoqiang Xu; Wenlong Jiang (Science of The Total Environment, 2023)

Cross-scale sensing of field-level crop residue cover: Integrating field photos, airborne hyperspectral imaging, and satellite data - Sheng Wang; Kaiyu Guan; Chenhui Zhang; Qu Zhou; Sibo Wang; Xiaocui Wu; Chongya Jiang; Bin Peng; Weiye Mei; Kaiyuan Li; Ziyi Li; Yi Yang; et al. (Remote Sensing of Environment, 2023)

HSQC-based small molecule accurate recognition technology discovery of diverse cytotoxic sesquiterpenoids from Elephantopus tomentosus L. and structural revision of molephantins A and B - Ming Bai; Wei Xu; Xin Zhang; Qian Li; Ning-Ning Du; De-Feng Liu; Guo-Dong Yao; Bin Lin; Shao-Jiang Song; Xiao-Xiao Huang (Phytochemistry, 2023)

Pharmaceuticals and personal care products (PPCPs) in the aquatic environment: Biotoxicity, determination and electrochemical treatment - Li Jiang; Yixiang Li; Yuxin Chen; Bin Yao; Xia Chen; Yuange Yu; Jian Yang; Yaoyu Zhou (Journal of Cleaner Production, 2023)

Enhancing the total nitrogen removal efficiency of anaerobic ammonium oxidation (anammox) with two types of biochars - Suyan Pang; Gan Zhang; Yingbin Hu; Xiaonan Luo; Ning Li; Jialiang Zhu; Jin Jiang; Bin Han; Tong Shen (Journal of Environmental Chemical Engineering, 2023)

Catalytic pyrolysis of 5-Amino-1H-Tetrazole with copper and its oxide: A deep insight into the combustion mechanism for high nitrogen compound - Si-Yuan Zhou; Jiu Chen; Xuan Li; Fan Jia; Dan Zhang; Li-Feng Xie; Bin Li; Lin Jiang (Fuel, 2023)

Embodied carbon emissions induced by the construction of hydropower infrastructure in China - Zewen Ge; Yong Geng; Wendong Wei; Mingkun Jiang; Bin Chen; Jiashuo Li (Energy Policy, 2023)

Using the roughness height and manning number in hydrodynamic model to estimate the impact of intensive oyster aquaculture by floating & fixed rafts on water exchange with an application in Qinzhou Bay, China - Yu Huang; Zenghui Li; Changyang Sun; Zhiwei Feng; Jingyao Li; Danyi Wei; Bin Wang; Shang Jiang; Keliang Chen; Xiang Sun (Ecological Modelling, 2023)

High sensitivity tactile sensors with ultrabroad linear range based on gradient hybrid structure for gesture recognition and precise grasping - Shuai Wang; Zaoxu Zhang; Bin Yang; Xin Zhang; Huiming Shang; Li Jiang; Hong Liu; Jia Zhang; PingAn Hu (Chemical Engineering Journal, 2023)

Mesoscale effect on droplet formation in a step-emulsification microdevice with parallel microchannels - Chengxiang He; Bin Jiang; Wei Zhan; Shouchuan Li; Xiaoda Wang; Chunying Zhu; Youguang Ma; Taotao Fu (Chemical Engineering Journal, 2023)

Short-Term Limited Water Irrigation Influences the Photosynthetic Pigments, Enzymatic and Non-Enzymatic Activities in Saccharum spontaneum L. at Vegetative Stage - Zhi-Nian Deng; Hai-Rong Huang; Cheng-Mei Huang; Krishan K. Verma; Hai-Bin Luo; Sheng-Li Jiang; Yi-Jie Li; Hui-Qing Cao; Kai-Chao Wu; Lin Xu (Sugar Tech, 2023)

Highly Engrafting Cord Blood Hematopoietic Stem Cells are Enriched in CD34+ Cell Population with High Autophagy Activity - Qingwei Ding; Jingchao Zhou; Yu Li; Qin Wang; Chunxu Yao; Rongzhen Jiang; Qingyou Meng; Haitao Wang; Yandan Chen; Bin Guo (Stem Cell Reviews and Reports, 2023)

The interaction of MC3R and MC4R with MRAP2a in rainbow trout (Oncorhynchus mykiss) - Hui-Xia Yu; Yang Li; De-Bin Zhong; Xin Ren; Hao-Lin Mo; Ze-Bin Jiang; Jia-Jia Yu; Dong-Mei Xiong; Hai-Xia Liu; Li-Xin Wang (Fish Physiology and Biochemistry, 2023)

Heat-stress induced sesquiterpenes of Chrysanthemum nankingense attract herbivores but repel herbivore feeding - Dian Wen; Yaqin Guan; Li Jiang; Sumei Chen; Fadi Chen; Bin Liu; Ülo Niinemets; Yifan Jiang (Arthropod-Plant Interactions, 2023)

Massive nutrients offshore transport off the Changjiang Estuary in flooding summer of 2020 - Qianwen Sun; Dewang Li; Bin Wang; Zhongsheng Xu; Yanyi Miao; Hua Lin; Haiyan Jin; Zhibing Jiang; Jiangning Zeng; Feng Zhou; Jianfang Chen (Frontiers in Marine Science, 2023)
Flood events significantly increase water discharges and terrigenous material inputs to coastal waters. Riverine nutrients in the Changjiang Estuary are transported by the dispersion of Changjiang Diluted Water (CDW) plumes and detached low-salinity water patches. However, the effects of flooding on nutrient offshore transports have not been well explored. Here, we present the nutrient conditions in the Changjiang Estuary and adjacent East China Sea in the historical flooding year 2020. Comparisons of nutrient distributions between flooding years, drought year and non-flooding years were also made. Our results showed that nitrate flux from the Changjiang River in August 2020 was 1.5 times that of the multi-year averaged flux in non-flooding years. Enormous riverine nutrient input resulted in much higher nutrient concentrations in the outer estuary than those in non-flooding years. In addition, a detached low-salinity water patch was observed, which made the salinity of the northern estuary even lower than that in the historical flooding year 1998. Surface dissolved inorganic nitrate (DIN) level in the low-salinity water patch was even ~16 times of that at nearby station in the drought year 2006. While phosphate (PO 4 3− ) concentrations were less than 0.1 μmol L −1 east of 123°E, which was probably caused by intensive biological uptake, as indicated by a high Chlorophyll a (Chl a ) concentration (29.08 μg L −1 ). The depleted PO 4 3− and high N/P of the low-salinity water patch suggested PO 4 3− limitation even under flood conditions. A three end-member mixing model was adopted to identify the contributions of the CDW end-member (CDW end-member ) and biological process to nutrient distributions. Our model results showed that the nutrient contribution of the CDW end-member to the estuary (122–124°E, 31–32.5°N) in flooding year 2020 was over double that in drought year 2006. Model-derived biological DIN uptake was as high as 24.65 μmol L −1 at the low-salinity water patch. Accordingly, the estimated net community production was 566–1131 mg C m −2 d −1 within the euphotic zone. The offshore transport of a low-salinity, high-DIN water patch during flooding could probably have a significant influence on biogeochemical cycles in the broad shelf, and even the adjacent Japan Sea.

Observational studies of the effects of wind mixing and biological process on the vertical distribution of dissolved oxygen off the Changjiang Estuary - Yanyi Miao; Bin Wang; Dewang Li; Xiangyu Sun; Zhongsheng Xu; Qianwen Sun; Zhibing Jiang; Xiao Ma; Haiyan Jin; Jianfang Chen (Frontiers in Marine Science, 2023)
Wind mixing is important in regulating dissolved oxygen (DO) variability; however, the transect response of DO dynamics to wind disturbance has seldom been documented with field data. In the summer of 2017, repeat transect observations off the Changjiang Estuary were conducted throughout a fresh wind (the maximum wind speed was 9.8 m s–1) event to reveal the role of physical mixing and biological activity in DO variations. After the wind event, hypoxia was alleviated presenting as the hypoxia thickness decreased from 30 m to 20 m. However, poorly ventilated near-bottom hypoxia was aggravated with a further decrease in DO. Generally, the saturation of dissolved oxygen (DOs) in depth-integrated water column increased by 9%–49% through physical diffusion with a weakened stratification and enhanced phytoplankton bloom. However, in this case, the wind-induced physical water mass mixing by transporting DO downward had a limited contribution to the water-column DO budget, while upwards nutrients induced by mixing fueled the larger vertical area of algae bloom and subsequent substantial oxygen consumption. As the wind speed increased, the air-sea exchange would be important in supplying DO, especially in nearshore areas, which could effectively offset the DO deficiency. In summary, frequently occurring fresh wind-mixing events off the Changjiang Estuary would alleviate hypoxia in the water column but probably exacerbate hypoxia at the bottom, as determined by competing ventilation and respiration roles. Such complex interactions likely occur and perform differently as wind stress varies. Thus, high-spatial and long-term process observations are required to better understand the net effects of bottom hypoxia evolution.

The accumulation of organic contaminants in hair with different biological characteristics - Bin Tang; Jing Zheng; Shi-Mao Xiong; Feng-Shan Cai; Min Li; Yan Ma; Bo Gao; Dong-Wei Du; Yun-Jiang Yu; Bi-Xian Mai (Chemosphere, 2023)

Hypoxia mediates Hif-1α to affect myofiber development and Vc regulates the influence by activating Shh-Gli pathway in channel catfish (Ictalurus punctatus) - Kang Xiao; Xi Wang; Yong-jun Dai; Yang-yang Huang; Mang-mang Wang; Hui-Xing Guo; Wen-Bin Liu; Xiang-fei Li; Kenneth Prudence Abasubong; Guang-Zhen Jiang (Aquaculture, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Nitric oxide effects on postharvest and Alternaria-infected pear fruit - Suhui Zheng; Ruiqiang Xu; Jia Wei; Jia Tian; Qing He; Fulin Zhang; Jiang Li; Bin Wu; Junfeng Guan (Postharvest Biology and Technology, 2023)

Biomass-derived volatiles for activation of the biochar of same origin - Chao Li; Dianqiang Li; Yuchen Jiang; Lijun Zhang; Yong Huang; Bin Li; Shuang Wang; Xun Hu (Fuel, 2023)

Effect of Hofmeister series anions on freeze-thaw stability of emulsion stabilized with whey protein isolates - Hao Lai; Qian Shen; Fuchao Zhan; Sha Jiang; Haomin Sui; Yijie Chen; Bin Li; Jing Li (Food Hydrocolloids, 2023)

Distribution and migration of antibiotic resistance genes, as well as their correlation with microbial communities in swine farm and its surrounding environments - Bin Wang; Lei Song; Wenjia Li; Li'an Hou; Jiang Li; Xiaoyi Xu; Guishang Sheng (Environmental Pollution, 2023)

Impact of the COVID-19 on electricity consumption of open university campus buildings – The case of Twente University in the Netherlands - Sheng Xu; Bin Cheng; Zefeng Huang; Tao Liu; Yuan Li; Lin Jiang; Wei Guo; Jie Xiong (Energy and Buildings, 2023)

Transcurrent tectonic system and deep seismogenic mechanism in the southeastern Tibetan Plateau: A view from gravity and magnetic anomalies - Feiyu Zhao; Sanzhong Li; Suhua Jiang; Lijun Liu; Junjiang Zhu; Mengxue Dai; Ying Liu; Gang Wang; Ze Liu; Bin Hu; Yixin Zhu (Earth-Science Reviews, 2023)

Uncovering expression and functional analysis of newly discovered high-affinity K+ transporter family members from sugarcane - Hai-bin Luo; Cheng-mei Huang; Yuan-wen Wei; Hui-ming Zhu; Hui-qing Cao; Sheng-li Jiang; Zhi-nian Deng; Kai-chao Wu; Lin Xu (Journal of Plant Biochemistry and Biotechnology, 2022)

Trace element signature of hydrothermal quartz: a potential tracer for ore genesis - Juan Dong; Li-Bin Jia; Mei-jia Song; Shu-Teng Xu; Mao-Wen Yuan; Cheng-Lu Li; Yuan-Jiang Yang (Arabian Journal of Geosciences, 2022)

Hazard analysis of landslide blocking a river in Guang’an Village, Wuxi County, Chongqing, China - Qin Panpan; Huang Bolin; Li Bin; Chen Xiaoting; Jiang Xiannian (Landslides, 2022)

Antigenic epitope screening and functional modification of mannose enhance the efficacy of largemouth bass virus subunit vaccines - Yi‐Jun Jia; Jun‐Yao Xia; Fu‐Yi Jiang; Yang Li; Guo Chen; Bin Zhu (Journal of Fish Diseases, 2022)
Major capsid protein (MCP) can be used as a subunit vaccine against largemouth bass virus (LMBV). However, subunit vaccines usually have low immunogenicity. Here, to identify the major immunogenicity determinant region of the MCP gene, we truncated the MCP of the LMBV gene into four parts ( MCP ‐ 1, MCP ‐ 2, MCP ‐ 3 and MCP ‐ 4 ). Enzyme‐linked immunosorbent assay (ELISA) was used to identify the antigenicity of these four truncated MCP proteins. Then, the highly antigenic truncated protein was modified with mannose and connected with functionalized single‐walled carbon nanotubes (SWCNTs) as carriers. Largemouth basses were immunized by bath immersion, challenged with LMBV on the 28th day after immunization and evaluated for related immune indicators. The results indicated that the MCP‐2 protein could induce a higher antibody titre than the other truncated MCP proteins. We found that the levels of immune‐related genes ( TNF‐α, CD40 , IgM , IFNγ and IL‐10 ) in the spleen and kidney were significantly increased in the MCP‐2 and MCP‐2‐Man groups. ELISA results showed that the antibody content in the serum increased significantly in the MCP‐2 group 7 days post‐vaccination and increased with days in all the vaccinated groups, with the highest observed on the 21st day. Notably, the MCP‐2‐Man vaccine (10 mg L −1 ) showed durability of immunoprotection efficacy that could protect largemouth basses from LMBV challenge, and the immune protection rate reached 78.94%. These results suggest that MCP‐2 might be the major immunogenicity determinant region of LMBV and that the mannose‐modified MCP‐2 vaccine can induce stronger adaptive immune responses.

Disruption of Aokap6 near the kojic acid gene cluster affects the growth and kojic acid production in Aspergillus oryzae - Ziming Chen; Tianming Chen; Huilan Wang; Conghua Jiang; Yixue Liu; Xinyu Wu; Yuzhen Li; Bin Zeng; Zhe Zhang (World Journal of Microbiology and Biotechnology, 2022)

Microbial succession and its effect on key aroma components during light-aroma-type Xiaoqu Baijiu brewing process - Bin Lin; Jie Tang; Qiang Yang; Zhixin Su; Liping Zhu; Qun Li; Wei Jiang; Long Zhang; Yuancai Liu; Shenxi Chen (World Journal of Microbiology and Biotechnology, 2022)

Complete chloroplast genomes of two medicinal Swertia species: the comparative evolutionary analysis of Swertia genus in the Gentianaceae family - Qing Du; Jing Li; Liqiang Wang; Haimei Chen; Mei Jiang; Zhuoer Chen; Chuanbei Jiang; Haidong Gao; Bin Wang; Chang Liu (Planta, 2022)

Repeated Sevoflurane Exposures in Neonatal Rats Increased the Brain Vulnerability to Future Stress Exposure and Resulted in Fear Extinction Deficit - Ben-zhen Chen; Li-hua Jiang; Ling Tan; Wen-qin Zhou; Yu-chao Shang; Fang Li; Bin Liu (Neurotoxicity Research, 2022)

Role of Sp1 in atherosclerosis - Jie-Feng Jiang; Zheng-Yang Zhou; Yi-Zhang Liu; Li Wu; Bin-Bin Nie; Liang Huang; Chi Zhang (Molecular Biology Reports, 2022)

Phosphorylation of Truncated Tau Promotes Abnormal Native Tau Pathology and Neurodegeneration - Longfei Li; Yanli Jiang; Gang Wu; Yacoubou Abdoul Razak Mahaman; Dan Ke; Qun Wang; Bin Zhang; Jian-Zhi Wang; Hong-Lian Li; Rong Liu; Xiaochuan Wang (Molecular Neurobiology, 2022)

Rational construction of Co-promoted 1T-MoS2 nanoflowers towards high-efficiency 4-nitrophenol reduction - Cen Zhang; Li Wang; Xi Huang; Liang Bai; Qiyuan Yu; Bin Jiang; Chenlu Zheng; Jing Cao (Environmental Science and Pollution Research, 2022)

Overexpression of PYGO1 promotes early cardiac lineage development in human umbilical cord mesenchymal stromal/stem cells by activating the Wnt/β-catenin pathway - Jie Shen; Xiushan Wu; Ping Zhu; Jian Zhuang; Bin Qin; Fang Sun; Wuzhou Yuan; Xiongwei Fan; Zhigang Jiang; Fang Li; Yongqing Li; Yuequn Wang; et al. (Human Cell, 2022)

Genome-wide association study reveals a NAC transcription factor TaNAC074 linked to pre-harvest sprouting tolerance in wheat - Hao Jiang; Yu Fang; Dong Yan; Si-tong Liu; Jun Wei; Fei-long Guo; Xing-ting Wu; Hong Cao; Chang-bin Yin; Fei Lu; Li-feng Gao; Yong-xiu Liu (Theoretical and Applied Genetics, 2022)

Rhizobium quercicola sp. nov., isolated from the leaf of Quercus variablis in China - Cheng-Bin Wang; Dan-Ran Bian; Ning Jiang; Han Xue; Chun-Gen Piao; Yong Li (Archives of Microbiology, 2022)

Mapping and analysis of a spatiotemporal H3K27ac and gene expression spectrum in pigs - Yaling Zhu; Zhimin Zhou; Tao Huang; Zhen Zhang; Wanbo Li; Ziqi Ling; Tao Jiang; Jiawen Yang; Siyu Yang; Yanyuan Xiao; Carole Charlier; Michel Georges; et al. (Science China Life Sciences, 2022)

Identification of microRNAs related with neural germ layer lineage-specific progenitors during reprogramming - Ruizhen Sun; Tiantian Gong; Hui Liu; Jingling Shen; Bin Wu; Qi Jiang; Qi Wang; Yue Zhang; Lian Duan; Jing Hu; Qiuming Li; Lei Lei; et al. (Journal of Molecular Histology, 2022)

Feed types affect the growth, nutrient utilization, digestive capabilities, and endocrine functions of Megalobrama amblycephala: a comparative study between pelleted and extruded feed - Chao-Fan He; Xiang-Fei Li; Guang-Zhen Jiang; Ling Zhang; Miao Sun; Ya-Ping Ge; Wei-Liang Chen; Wen-Bin Liu (Fish Physiology and Biochemistry, 2022)

PLXDC2 enhances invadopodium formation to promote invasion and metastasis of gastric cancer cells via interacting with PTP1B - Bin Wu; Yan-xia Wang; Jun-jie Wang; Dong-fang Xiang; Meng-si Zhang; Ze-xuan Yan; Wen-ying Wang; Jing-ya Miao; Xi Lan; Jia-jia Liu; Zheng-yan Li; Chuan Li; et al. (Clinical & Experimental Metastasis, 2022)
Plexin-domain containing 2 (PLXDC2) has been reported as an oncoprotein in several human malignancies. However, its expression and roles in gastric cancer remain largely unclear. In this study, we found that PLXDC2 was highly expressed in gastric cancer tissues, and the expression levels were positively correlated with clinicopathological features, but negatively with the patients’ outcome. Cox regression analysis identified PLXDC2 as an independent prognostic indicator for the patients. Knockdown of PLXDC2 markedly suppressed the in vitro invasion and in vivo metastasis of gastric cancer cells, while overexpression of PLXDC2 resulted in opposite effects. Mechanistically, PLXDC2 enhanced the level of phosphorylated Cortactin (p-Cortactin) by physically interacting with protein tyrosine phosphatase 1B (PTP1B), an important dephosphorylase, to prevent its dephosphorylating of p-Cortactin, thereby promoting the formation of invadopodia. Collectively, our results indicate that PLXDC2 contributes to the invasion and metastasis of gastric cancer by inhibiting PTP1B to facilitate the invadopodium formation, and may serve as a potential prognostic biomarker and a therapeutic target for this disease.

Inhibition of AoAur1 increases mycelial growth, hyphal fusion and improves physiological adaptation to high-temperature stress in Aspergillus oryzae - Jinxin Ge; Zhe Zhang; Yuan Li; Zhihong Hu; Bin He; Yongkai Li; Bin Zeng; Chunmiao Jiang (Archives of Microbiology, 2022)

Calcification-Carbonation Method for Bayer Red Mud Treatment: Carbonation Performance of Hydrogarnets - Xiaofeng Zhu; Yongmei Liu; Fengqi Jiang; Bin Li; Guozhi Lv; Ting-an Zhang (Bulletin of Environmental Contamination and Toxicology, 2022)

A stable block adjustment method without ground control points using bound constrained optimization - Yonghua Jiang; Zhen Li; Meilin Tan; Shaodong Wei; Guo Zhang; Zhichao Guan; Bin Han (International Journal of Remote Sensing, 2022)

Multiple indeterminate domain (IDD)–DELLA1 complexes participate in gibberellin feedback regulation in peach - Yajun Jiang; Jiajia Chen; Xianbo Zheng; Bin Tan; Xia Ye; Wei Wang; Langlang Zhang; Jidong Li; Zhiqian Li; Jun Cheng; Jiancan Feng (Plant Molecular Biology, 2022)

A scientometric analysis of agricultural pollution by using bibliometric software VoSViewer and Histcite™ - Bin Li; Kai Hu; Vladimir Lysenko; Kiran Yasmin Khan; Yingkuan Wang; Yongnian Jiang; Ya Guo (Environmental Science and Pollution Research, 2022)

Correction to: Synergistic interactions between zinc and nitrogen addition in promoting plant Zn uptake as counteracted by mowing management in a meadow grassland - Yanyan Li; Ruzhen Wang; Heyong Liu; Xue Feng; Bin Wang; Zhirui Wang; Jiangping Cai; Lijuan Yang; Yong Jiang (Plant and Soil, 2022)

Synergistic interactions between zinc and nitrogen addition in promoting plant Zn uptake as counteracted by mowing management in a meadow grassland - Yanyan Li; Ruzhen Wang; Heyong Liu; Xue Feng; Bin Wang; Zhirui Wang; Jiangping Cai; Lijuan Yang; Yong Jiang (Plant and Soil, 2022)

The complete chloroplast genome sequence of Clerodendranthus spicatus, a medicinal plant for preventing and treating kidney diseases from Lamiaceae family - Qing Du; Mei Jiang; Sihui Sun; Liqiang Wang; Shengyu Liu; Chuanbei Jiang; Haidong Gao; Haimei Chen; Yong Li; Bin Wang; Chang Liu (Molecular Biology Reports, 2022)

Risk assessment study on landslide-generated impulse waves: case study from Zhongliang Reservoir in Chongqing, China - Chen Xiaoting; Huang Bolin; Li Bin; Jiang Xiannian (Bulletin of Engineering Geology and the Environment, 2022)

Assessing the impacts of natural disasters on rice production in Jiangxi, China - Xiao Fu; Guannan Zhao; Weicheng Wu; Bin Xu; Jie Li; Xiaoting Zhou; Xinxin Ke; Yuan Li; Wenjing Li; Cuimin Zhou; Jingheng Jiang; Ming Zhang; et al. (International Journal of Remote Sensing, 2022)

Trends and environmental factors of arsenic in sediments from the five lake ecoregions, China - Jinli Zheng; Bin Zhou; Hao Li; Manshu Gao; Changwei Lü; Jiang He (Environmental Science and Pollution Research, 2022)

Corrigendum: Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2022)

Another Record: Ocean Warming Continues through 2021 despite La Niña Conditions - Lijing Cheng; John Abraham; Kevin E. Trenberth; John Fasullo; Tim Boyer; Michael E. Mann; Jiang Zhu; Fan Wang; Ricardo Locarnini; Yuanlong Li; Bin Zhang; Zhetao Tan; et al. (Advances in Atmospheric Sciences, 2022)
The increased concentration of greenhouse gases in the atmosphere from human activities traps heat within the climate system and increases ocean heat content (OHC). Here, we provide the first analysis of recent OHC changes through 2021 from two international groups. The world ocean, in 2021, was the hottest ever recorded by humans, and the 2021 annual OHC value is even higher than last year’s record value by 14 ± 11 ZJ (1 zetta J = 10 21 J) using the IAP/CAS dataset and by 16 ± 10 ZJ using NCEI/NOAA dataset. The long-term ocean warming is larger in the Atlantic and Southern Oceans than in other regions and is mainly attributed, via climate model simulations, to an increase in anthropogenic greenhouse gas concentrations. The year-to-year variation of OHC is primarily tied to the El Niño-Southern Oscillation (ENSO). In the seven maritime domains of the Indian, Tropical Atlantic, North Atlantic, Northwest Pacific, North Pacific, Southern oceans, and the Mediterranean Sea, robust warming is observed but with distinct inter-annual to decadal variability. Four out of seven domains showed record-high heat content in 2021. The anomalous global and regional ocean warming established in this study should be incorporated into climate risk assessments, adaptation, and mitigation.

Functional characterization of melanocortin-3 receptor in rainbow trout (Oncorhynchus mykiss) - Hui-Xia Yu; Yang Li; Wei-Jia Song; Hui Wang; Hao-Lin Mo; Qiao Liu; Xin-Miao Zhang; Ze-Bin Jiang; Li-Xin Wang (Fish Physiology and Biochemistry, 2022)

Mechanical behavior of underground pipe gallery structure considering ground fissure - Bo-tuan Deng; Pan Li; Xin Li; Jiang-tao Tian; Bin Zhi (Journal of Mountain Science, 2022)

Characterization and Expression Analyses of Callose Synthase Enzyme (Cals) Family Genes in Maize (Zea mays L.) - Qunkai Niu; Peng Zhang; Shuai Su; Bin Jiang; Xiaowei Liu; Chuan Li; Tao Yu; Hongyang Yi; Jin Tang; Moju Cao (Biochemical Genetics, 2022)

Special roles for efflux systems in iron homeostasis of non‐siderophore‐producing cyanobacteria - Ling‐Mei Liu; Ding‐Lan Li; Bin Deng; Xin‐Wei Wang; Hai‐Bo Jiang (Environmental Microbiology, 2022)
Summary In oligotrophic oceans, low bioavailability of Fe is a key factor limiting primary productivity. However, excessive Fe in cells leads to the Fenton reaction, which is toxic to cells. Cyanobacteria must strictly maintain intracellular Fe homeostasis. Here, we knocked out a series of genes encoding efflux systems in Synechocystis sp. PCC 6803, and found eight genes that are required for high Fe detoxification. Unexpectedly, the HlyBD‐TolC efflux system plays an important role in the adaptation of Synechocystis under Fe‐deficient conditions. Mutants of HlyD and TolC grew worse than the wild‐type strain under low‐Fe conditions and showed significantly lower intracellular Fe contents than the wild‐type strain. We excluded the possibility that the low Fe sensitivity of the HlyBD‐TolC mutants was caused by a loss of the S‐layer, the main extracellular protein secreted via this efflux system. Inactivation of the HlyD protein influenced type IV pili formation and direct inactivation of type IV pili related genes affected the adaptation to low‐Fe conditions. HlyBD‐TolC system is likely involved in the formation of type IV pili and indirectly influenced Fe acquisition. Our findings suggest that efflux system in non‐siderophore‐producing cyanobacteria can facilitate Fe uptake and help cells adapt to Fe‐deficient conditions via novel pathways.

Experimental mechanical strength and deformation characteristics of deep damaged–fractured rock - Qing-Bin Meng; Jiang-Feng Liu; Li-Xiang Xie; Hai Pu; Yu-Gui Yang; Bing-Xiang Huang; Wei Qian (Bulletin of Engineering Geology and the Environment, 2022)

Fabrication of Stable Apigenin Nanosuspension with PEG 400 as Antisolvent for Enhancing the Solubility and Bioavailability - Renjie Xu; Cuiping Jiang; Lijing Zhou; Bin Li; Yi Hu; Yujie Guo; Xuecheng Xiao; Shan Lu (AAPS PharmSciTech, 2022)

Mechanical Properties of Limestone After High-Temperature Treatment Under Triaxial Cyclic Loading and Unloading Conditions - Qing-bin Meng; Jiang-Feng Liu; Hai Pu; Li-yuan Yu; Jiang-yu Wu; Cong-kai Wang (Rock Mechanics and Rock Engineering, 2021)

Perception-based sustainability evaluation and development path of ecotourism: Taking Pulau Perhentian in Malaysia and Weizhou Island in China as examples - Fenggui Chen; Jinwen Liu; Jianwei Wu; Jinlong Jiang; Li Yan; Phaik-Eem Lim; Mohammed Rizman Bin Idid; Sze Wan Poong; Sze Looi Song (Environment, Development and Sustainability, 2021)

Australian propolis ethanol extract exerts antibacterial activity against methicillin-resistant Staphylococcus aureus by mechanisms of disrupting cell structure, reversing resistance, and resisting biofilm - Fei Wang; Hui Liu; Junya Li; Wenwen Zhang; Bin Jiang; Hongzhuan Xuan (Brazilian Journal of Microbiology, 2021)

Feasibility Research on Fish Pose Estimation Based on Rotating Box Object Detection - Bin Lin; Kailin Jiang; Zhiqi Xu; Feiyi Li; Jiao Li; Chaoli Mou; Xinyao Gong; Xuliang Duan (Fishes, 2021)
A video-based method to quantify animal posture movement is a powerful way to analyze animal behavior. Both humans and fish can judge the physiological state through the skeleton framework. However, it is challenging for farmers to judge the breeding state in the complex underwater environment. Therefore, images can be transmitted by the underwater camera and monitored by a computer vision model. However, it lacks datasets in artificial intelligence and is unable to train deep neural networks. The main contributions of this paper include: (1) the world’s first fish posture database is established. 10 key points of each fish are manually marked. The fish flock images were taken in the experimental tank and 1000 single fish images were separated from the fish flock. (2) A two-stage attitude estimation model is used to detect fish key points. The evaluation of the algorithm performance indicates the precision of detection reaches 90.61%, F1-score reaches 90%, and Fps also reaches 23.26. We made a preliminary exploration on the pose estimation of fish and provided a feasible idea for fish pose estimation.

The joint driving effects of climate and weather changes caused the Chamoli glacier-rock avalanche in the high altitudes of the India Himalaya - Yushan Zhou; Xin Li; Donghai Zheng; Zhiwei Li; Baosheng An; Yingzheng Wang; Decai Jiang; Jianbin Su; Bin Cao (Science China Earth Sciences, 2021)

Combined use of lime, bentonite, and biochar for immobilization of Cd and mobilization of Se in paddy soil - Zhiqiang Xu; Bin Liang; Zhonghui Li; Hui Jiang; Ting Liu; Qiubo Wang; Jiaxin Duan (Environmental Science and Pollution Research, 2021)

Corticosterone Can Be an Essential Stress Index in Channel Catfish (Ictalurus punctatus) - Kang Xiao; Xi Wang; Wen-Bin Liu; Ding-Dong Zhang; Xiang-Fei Li; Chun-Nuan Zhang; Wei-Hua Chen; Kenneth Prudence Abasubong; Guang-Zhen Jiang (Frontiers in Marine Science, 2021)
Although cortisol is considered the main glucocorticoid involved in regulating stress in fish by elevating the serum glucose, the presence of serum corticosterone and whether its level can be used as an indicator for fish stress activation and reflect the degree of fish stress remains to be determined. To comprehensively and accurately evaluate the performance of two glucocorticoids after stress, in this study, seven of the most common stressors (ammonia nitrogen, high-temperature, acid, alkali, Aeromonas hydrophila, and salinity) in aquaculture were selected. The levels of serum corticosterone, cortisol, and glucose were detected within 48 h, and then the dynamic changes were analyzed. In addition, the kidneys were collected to detect the expression of corresponding proteins involved in corticosterone and cortisol synthesis (3 β-HSD and CYP17A1) for further exploration. From the results obtained, the content of serum corticosterone was about 100 times higher than that of cortisol, and it was found that corticosterone and cortisol showed different dynamic changes within 48 h among the seven kinds of stress. In the subsequent detection of glucose, it was found that the dynamic shift in glucose was not consistent with the dynamic changes of corticosterone or cortisol entirely but seemed to be caused by the combination of the two. In the follow-up protein expression detection, we found that corticosterone seemed to respond to stress earlier. Therefore, it is concluded that the responses of corticosterone and cortisol to stress are independent, corticosterone may be more sensitive in the current seven acute stresses, and then they regulate glucose together to resist stress. The study aimed to fill the vacancy of corticosterone in fish research and provide a reference for the complete evaluation of fish stress degree.

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

Association of Single Nucleotide Polymorphism at rs2275294 in the ZNF512B Gene with Prognosis in Amyotrophic Lateral Sclerosis - Haixia Jiang; Baiyuan Yang; Fang Wang; Kelu Li; Yongyun Zhu; Bin Liu; Hui Ren; Sijia Tian; Yanming Xu; Ailan Pang; Xinglong Yang (NeuroMolecular Medicine, 2021)

Determining the critical blasting load of cracked strip bauxite pillars - Li-chun Jiang; Bin-bin Shen; Luan-luan Xue (Bulletin of Engineering Geology and the Environment, 2021)

Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2021)

Antibacterial and anti-biofilm effects of fatty acids extract of dried Lucilia sericata larvae against Staphylococcus aureus and Streptococcus pneumoniae in vitro - Jing Liu; Jun Jiang; Junwei Zong; Bin Li; Taowen Pan; Yunpeng Diao; Zhen Zhang; Xueyang Zhang; Ming Lu; Shouyu Wang (Natural Product Research, 2021)

Establishment and characterization of 38 novel patient-derived primary cancer cell lines using multi-region sampling revealing intra-tumor heterogeneity of gallbladder carcinoma - Feiling Feng; Qingbao Cheng; Bin Li; Chen Liu; Huizhen Wang; Bin Li; Xiaoya Xu; Yong Yu; Zishuo Chen; Xiaobing Wu; Hua Dong; Kaijian Chu; et al. (Human Cell, 2021)
Gallbladder carcinoma (GBC) is a lethal biliary tract malignant neoplasm. Patient-derived primary cancer cell lines (PDPCs) are appropriate models to explore biological characteristics and potential therapeutics; however, there is a lack of PDPCs in GBC. In this study, we aimed to establish and characterize the GBC PDPCs, and further investigated the intra-tumor heterogeneity (ITH). Multi-region sampling (3–9 regions) of the operable tumor tissue samples was used to establish PDPCs. Short tandem repeat genotyping for cell authentication and karyotyping was performed, followed by whole-exome sequencing and RNA sequencing to assess the ITH at the genetic and transcriptional levels, respectively. Thirty-eight PDPCs were successfully established from seven GBC patients and characterized. ITH was observed with a median of 38.3% mutations being heterogeneous (range, 26.6–59.4%) across all patients. Similar with other tumor types, TP53 mutations were always truncal. In addition, there were three genes, KMT2C , CDKN2A , and ARID1A , with truncal mutations in at least two patients. A median of 370 differentially expressed genes (DEGs) was identified per patient. Distinct expression patterns were observed between major histocompatibility complex (MHC) class I and II genes. We found the expression of MHC class II genes in the PDPC samples was closely regulated by CIITA , while that of MHC class I genes were not correlated with CIITA expression. The PDPCs established from GBC patients can serve as novel in vitro models to identify the ITH, which may pave a crucial molecular foundation for enhanced understanding of tumorigenesis and progression.

Physical Simulations of Gas Production Mechanism in Constant-Rate Co-production from Multiple Coal Reservoirs - Qixian Li; Jiang Xu; Shoujian Peng; Fazhi Yan; Bin Zhou; Ende Han; Cheng Jiang (Natural Resources Research, 2021)

Elemental mercury capture from industrial gas emissions using sulfides and selenides: a review - Dongjing Liu; Bin Li; Jiang Wu; Yangxian Liu (Environmental Chemistry Letters, 2021)

Identification of genetic variants in m6A modification genes associated with pancreatic cancer risk in the Chinese population - Pingting Ying; Yao Li; Nan Yang; Xiaoyang Wang; Haoxue Wang; Heng He; Bin Li; Xiating Peng; Danyi Zou; Ying Zhu; Rong Zhong; Xiaoping Miao; et al. (Archives of Toxicology, 2021)

Experimental Study on Rock Strength and Deformation Characteristics Under Triaxial Cyclic Loading and Unloading Conditions - Qing-bin Meng; Jiang-Feng Liu; Li Ren; Hai Pu; Yan-long Chen (Rock Mechanics and Rock Engineering, 2021)

MicroRNA-1246 regulates proliferation, invasion, and differentiation in human vascular smooth muscle cells by targeting cystic fibrosis transmembrane conductance regulator (CFTR) - Diguang Pan; Guiyong Liu; Bin Li; Jingbo Jiang; Wei Chen; Wei Li; Lin Zhang; Yubao Hu; Shuyun Xie; Huayun Yang (Pflügers Archiv - European Journal of Physiology, 2021)

3,5,4′-Trimethoxy-trans-stilbene loaded microemulsion for cutaneous melanoma therapy by transdermal drug delivery - Jun-Yong Wu; Jia-Xin Cai; Yong-Jiang Li; Xiong-Bin Hu; Xin-Yi Liu; Jie-Min Wang; Tian-Tian Tang; Da-Xiong Xiang (Drug Delivery and Translational Research, 2021)

Modes of genetic adaptations underlying functional innovations in the rumen - Xiangyu Pan; Yudong Cai; Zongjun Li; Xianqing Chen; Rasmus Heller; Nini Wang; Yu Wang; Chen Zhao; Yong Wang; Han Xu; Songhai Li; Ming Li; et al. (Science China Life Sciences, 2021)

A unique porin meditates iron‐selective transport through cyanobacterial outer membranes - Guo‐Wei Qiu; Hai‐Bo Jiang; Hagar Lis; Zheng‐Ke Li; Bin Deng; Jin‐Long Shang; Chuan‐Yu Sun; Nir Keren; Bao‐Sheng Qiu (Environmental Microbiology, 2021)
Summary Cyanobacteria are globally important primary producers and nitrogen fixers with high iron demands. Low ambient dissolved iron concentrations in many aquatic environments mean that these organisms must maintain sufficient and selective transport of iron into the cell. However, the nature of iron transport pathways through the cyanobacterial outer membrane remains obscure. Here we present multiple lines of experimental evidence that collectively support the existence of a novel class of substrate‐selective iron porin, Slr1908, in the outer membrane of the cyanobacterium Synechocystis sp. PCC 6803. Elemental composition analysis and short‐term iron uptake assays with mutants in Slr1908 reveal that this protein is primarily involved in inorganic iron uptake and contributes less to the accumulation of other metals. Homologues of Slr1908 are widely distributed in both freshwater and marine cyanobacteria, most notably in unicellular marine diazotrophs. Complementary experiments with a homologue of Slr1908 in Synechococcus sp. PCC 7002 restored the phenotype of Synechocystis knockdown mutants, showing that this siderophore producing species also possesses a porin with a similar function in Fe transport. The involvement of a substrate‐selective porins in iron uptake may allow cyanobacteria to tightly control iron flux into the cell, particularly in environments where iron concentrations fluctuate.

The Knowledge, Attitude, and Self-Reported Behaviors of Oncology Physicians Regarding Fertility Preservation in Adult Cancer Patients - Hanfeng Zhang; Guorong Wang; Bin Jiang; Maoqiu Cao; Qinghua Jiang; Li Yin; Bencui Fu; Jian Zhang (Journal of Cancer Education, 2020)
There is a growing concern about the fertility preservation for adult cancer patients of reproductive age. Very little literature exists about fertility preservation of cancer survivors in Chinese text. This study is first to describe the knowledge level, attitude, and practice behaviors among physicians concerning fertility preservation in adult cancer patients in China. A cross-sectional survey with 30-item was conducted to assess Chinese oncology physicians’ knowledge, attitude, and behaviors regarding fertility issues. Of 360 oncology physicians, 206 (57.2%) submitted valid questionnaires. With possible overall scores for knowledge and attitude of 9 and 15, respectively, physicians’ responses to the questionnaires were 3.91 ± 1.67 and 12.29 ± 1.23. Only 49.5% of physicians routinely informed their cancer patients of childbearing age about the risk of infertility with cancer treatment. The knowledge score of the men physicians was 2-fold that of the women. Physicians aged 20–29 years were significantly more likely than other age groups to prioritize cancer treatment over fertility concerns. Men physicians were significantly more comfortable than the women discussing fertility preservation issues and cooperating with fertility specialists. The oncology physicians in China had limited knowledge of fertility preservation and rarely discussed these issues with their patients, although their attitude was positive. Results suggest that oncology physicians would welcome an in-house fertility-related training program. Key Messages This is the first study to address the topic of fertility preservation as it relates to the care that oncologists provide to cancer patients in China. These results revealed the importance of providing fertility-related training program to oncology physicians. Moreover, this study should provide useful information for other Asian countries, and highlight both the similarities and differences between China and Western countries concerning the reproductive rights of patients. This study should encourage international cooperation with institutions of scientific research and education.

GC usage of SARS-CoV-2 genes might adapt to the environment of human lung expressed genes - Yue Li; Xinai Yang; Na Wang; Haiyan Wang; Bin Yin; Xiaoping Yang; Wenqing Jiang (Molecular Genetics and Genomics, 2020)

Model test of the stability degradation of a prestressed anchored rock slope system in a corrosive environment - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Zhi-jun Liu; Bo Lu; Bin Wang; Yu-zhou Jiang; Jie-sheng Liu; Ping Zeng (Journal of Mountain Science, 2020)

Structural characteristics and anti-complement activities of polysaccharides from Sargassum hemiphyllum - Weihua Jin; Qiufu Fang; Di Jiang; Tongtong Li; Bin Wei; Jiadong Sun; Wenjing Zhang; Zhongshan Zhang; Fuming Zhang; Robert J. Linhardt; Hong Wang; Weihong Zhong (Glycoconjugate Journal, 2020)

Protein extraction and database construction in tea rhizosphere soil - Hai-bin Wang; Chun-lian Zhu; Yu-hua Wang; Qing-xu Zhang; Peng Wang; Ding Li; Xiao-li Jia; Jiang-hua Ye; Hai-bin He (Acta Physiologiae Plantarum, 2020)

Initial chest CT findings in COVID-19: correlation with clinical features - Zhu-jing Shen; Nan Lu; Lu-lu Gao; Jian Lv; Hua-fu Luo; Ji-feng Jiang; Chao Xu; Shi-ya Li; Ju-jiang Mao; Kai Li; Xiao-pei Xu; Bin Lin (Journal of Zhejiang University-SCIENCE B, 2020)

The undrained vertical and horizontal bearing capacity of internal skirted foundation in clay - Chong Jiang; Liu Lin; Chen Li; Tian-Bin Li; Jiali He (European Journal of Environmental and Civil Engineering, 2020)

Haploidentical hematopoietic cell transplantation for severe acquired aplastic anemia: a case-control study of post-transplant cyclophosphamide included regimen vs. anti-thymocyte globulin & colony-stimulating factor-based regimen - Lanping Xu; Bin Fu; Wenjing Wang; Yajing Xu; Depei Wu; Shunqing Wang; Qifa Liu; Linghui Xia; Sujun Gao; Ming Jiang; Jianmin Wang; Xi Zhang; et al. (Science China Life Sciences, 2020)

Combined Effects of Straw Returning and Chemical N Fertilization on Greenhouse Gas Emissions and Yield from Paddy Fields in Northwest Hubei Province, China - Quanyi Hu; Tianqi Liu; Songsong Jiang; Cougui Cao; Chengfang Li; Bin Chen; Junbo Liu (Journal of Soil Science and Plant Nutrition, 2020)

Screening of three Chlorella mutant strains with high lipid production induced by 3 types of lasers - Kang Wang; Bin Lin; Chunxiao Meng; Zhengquan Gao; Zhe Li; Haonan Zhang; Huanmin Du; Fei Xu; Xiao Jiang (Journal of Applied Phycology, 2020)

Correction to: Simulated microgravity significantly altered metabolism in epidermal stem cells - Bin-Bin Li; Zheng-Yang Chen; Nan Jiang; Song Guo; Jia-Qi Yang; Shao-Bin Chai; Hong-Feng Yan; Pei-Ming Sun; Gang Hu; Tao Zhang; Bing-Xin Xu; Hong-Wei Sun; et al. (In Vitro Cellular & Developmental Biology - Animal, 2020)

Plastic pollution in croplands threatens long‐term food security - Dan Zhang; Ee Ling Ng; Wanli Hu; Hongyuan Wang; Pablo Galaviz; Hude Yang; Wentao Sun; Chongxiao Li; Xingwang Ma; Bin Fu; Peiyi Zhao; Fulin Zhang; et al. (Global Change Biology, 2020)
Plastic pollution is a global concern given its prevalence in aquatic and terrestrial ecosystems. Studies have been conducted on the distribution and impact of plastic pollution in marine ecosystems, but little is known on terrestrial ecosystems. Plastic mulch has been widely used to increase crop yields worldwide, yet the impact of plastic residues in cropland soils to soil health and crop production in the long term remained unclear. In this paper, using a global meta‐analysis, we found that the use of plastic mulch can indeed increase crop yields on average by 25%–42% in the immediate season due to the increase of soil temperature (+8%) and moisture (+17%). However, the unabated accumulation of film residues in the field negatively impacts its physicochemical properties linked to healthy soil and threatens food production in the long term. It has multiple negative impacts on plant growth including crop yield (at the mean rate of −3% for every additional 100 kg/ha of film residue), plant height (−2%) and root weight (−5%), and soil properties including soil water evaporation capacity (−2%), soil water infiltration rate (−8%), soil organic matter (−0.8%) and soil available phosphorus (−5%) based on meta‐regression. Using a nationwide field survey of China, the largest user of plastic mulch worldwide, we found that plastic residue accumulation in cropland soils has reached 550,800 tonnes, with an estimated 6%–10% reduction in cotton yield in some polluted sites based on current level of plastic residue content. Immediate actions should be taken to ensure the recovery of plastic film mulch and limit further increase in film residue loading to maintain the sustainability of these croplands.

Excess DHA Induces Cell Cycle Arrest by Activating the P53/Cycling Pathway in Blunt Snout Bream (Megalobrama amblycephala) - Cong-cong Wang; Wen-bin Liu; Xiu-fei Cao; Yang-yang Huang; Xi Wang; Kang Xiao; Xiang-fei Li; Ding-dong Zhang; Guang-zhen Jiang (Frontiers in Marine Science, 2020)

Three new dibenzofurans from Cydonia oblonga Mill - Jiao-Jiao Wei; Wen-Qiong Wang; Wei-Bin Song; Li-Jiang Xuan (Natural Product Research, 2020)

Binding Mechanism Between Fulvic Acid and Heavy Metals: Integrated Interpretation of Binding Experiments, Fraction Characterizations, and Models - Zhenrui Zhang; Wenjing Shi; Hua Ma; Bin Zhou; Hao Li; Changwei Lü; Jiang He (Water, Air, & Soil Pollution, 2020)

Influences of glycyrrhetinic acid (GA) dietary supplementation on growth, feed utilization, and expression of lipid metabolism genes in channel catfish (Ictalurus punctatus) fed a high-fat diet - Hesham Eed Desouky; Guang-zhen Jiang; Ding-dong Zhang; Kenneth Prudence Abasubong; Xiangyang Yuan; Xiang-fei Li; Wen-bin Liu (Fish Physiology and Biochemistry, 2020)

Simulated microgravity significantly altered metabolism in epidermal stem cells - Bin-Bin Li; Zheng-Yang Chen; Nan Jiang; Song Guo; Jia-Qi Yang; Shao-Bin Chai; Hong-Feng Yan; Pei-Ming Sun; Gang Hu; Tao Zhang; Bing-Xin Xu; Hong-Wei Sun; et al. (In Vitro Cellular & Developmental Biology - Animal, 2020)
Simulated microgravity can significantly affect various cell types and multiple systems of the human body, such as cardiovascular system, skeletal muscle system, and immune system, and is known to cause anemia and loss of electrolyte and fluids. Epidermal stem cells (EpSCs) were cultured in a rotary cell culture system (RCCS) bioreactor to simulate microgravity. The metabolites of EpSCs were identified by liquid chromatography-mass spectrometry (LC-MS). Compared with normal gravity (NG) group, a total of 57 different metabolites of EpSCs were identified ( P < 0.05, VIP > 1), including lipids and lipid-like molecules (51 molecules), amino acids (5 molecules), nucleosides, nucleotides, and analogues (1 molecule). According to the partial least squares discriminant analysis (PLS-DA) score plot, a VIP > 1 and P < 0.05 were obtained for the 57 different metabolites, of which 23 molecules were significantly downregulated and 34 were significantly upregulated in simulated microgravity (SMG) group. These results showed that SMG has a significant impact on different pathways, and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis indicated that multiple pathways were involved, mainly the amino acid metabolism pathway, lipid metabolism pathway, membrane transport pathway, and cell growth and death pathways. Thus, the metabolic profile of EpSCs was changed under SMG. Exploring the metabolic profile of EpSCs would be helpful to further understand the growth characteristics of EpSCs under SMG, which will provide a new approach to explore the metabolomics mechanism of stress injury and repair trauma under SMG.

Photocatalytic oxidation removal of elemental mercury from flue gas. A review - Dongjing Liu; Bin Li; Jiang Wu; Yangxian Liu (Environmental Chemistry Letters, 2020)

Roles of PTBP1 in alternative splicing, glycolysis, and oncogensis - Wei Zhu; Bo-lun Zhou; Li-juan Rong; Li Ye; Hong-juan Xu; Yao Zhou; Xue-jun Yan; Wei-dong Liu; Bin Zhu; Lei Wang; Xing-jun Jiang; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2020)

Sorbents for hydrogen sulfide capture from biogas at low temperature: a review - Dongjing Liu; Bin Li; Jiang Wu; Yangxian Liu (Environmental Chemistry Letters, 2020)

Contribution of skeletal muscular glycine to rapid antidepressant effects of ketamine in an inflammation-induced mouse model of depression - Niannian Huang; Yue Wang; Gaofeng Zhan; Fan Yu; Shan Li; Dongyu Hua; Riyue Jiang; Shiyong Li; Yeshun Wu; Ling Yang; Bin Zhu; Fei Hua; et al. (Psychopharmacology, 2019)

Autotrophic Bacterial Community and Microbial CO2 Fixation Respond to Vegetation Restoration of Eroded Agricultural Land - Haibing Xiao; Zhongwu Li; Chuxiong Deng; Lin Liu; Jia Chen; Bin Huang; Xiaodong Nie; Chun Liu; Danyang Wang; Jieyu Jiang (Ecosystems, 2019)

A New Neural Pathway from the Ventral Striatum to the Nucleus Basalis of Meynert with Functional Implication to Learning and Memory - Si Yun Shu; Gang Jiang; Zhaocong Zheng; Lin Ma; Bin Wang; Qiyi Zeng; Hong Li; Shen Tan; Bin Liu; Wood Yee Chan; Sheng Wu; Chunhua Zhu; et al. (Molecular Neurobiology, 2019)

Long noncoding RNA LINC00460 aggravates invasion and metastasis by targeting miR-30a-3p/Rap1A in nasopharyngeal carcinoma - Xiaodong Hu; Weiwei Liu; Xue Jiang; Bin Wang; Liping Li; Jian Wang; Jinhua Ma (Human Cell, 2019)

Effects of dietary protein level on growth performance, digestive enzyme activity, and gene expressions of the TOR signaling pathway in fingerling Pelteobagrus fulvidraco - Qin Qin; Xiu-Fei Cao; Yong-jun Dai; Li-Na Wang; Ding-Dong Zhang; Guang-Zhen Jiang; Wen-Bin Liu (Fish Physiology and Biochemistry, 2019)

3D-Printed Wearable Personalized Orthodontic Retainers for Sustained Release of Clonidine Hydrochloride - Heliu Jiang; Junhui Fu; Mingguang Li; Shanshan Wang; Bo Zhuang; Haiyan Sun; Cheng Ge; Bin Feng; Yiguang Jin (AAPS PharmSciTech, 2019)

Different response to middle-Palaeozoic magmatism during intracontinental orogenic processes: evidence from southeastern South China Block - Quan Ou; Jian–Qing Lai; Bruna B. Carvalho; Feng Zi; Hua Kong; Bin Li; Zi–Qi Jiang (International Geology Review, 2019)

MicroRNA-377-3p inhibits growth and invasion through sponging JAG1 in ovarian cancer - Liulin Tang; Bin Yang; Xiaolan Cao; Qin Li; Li Jiang; Dan Wang (Genes & Genomics, 2019)

3D-QSAR modeling of Phosphodiesterase-5 inhibitors: evaluation and comparison of the receptor- and ligand-based alignments - Zan Jiang; Xuehua Zheng; Zhong Li; Shuqiong Pan; Xiaoyu Wang; Chen Zhang; Zhe Li; Hai-Bin Luo; Deyan Wu; Xiong Cai (Medicinal Chemistry Research, 2019)

Associations between the red blood cell distribution width and primary angle-closure glaucoma: a potential for disease prediction - Qiang Chen; Bin Zhao; Meng-ya Wang; Xue-yu Chen; Dong Li; Xin-quan Jiang; Jing-hui Tian; Yong-jun Liu (EPMA Journal, 2019)

Pollution characteristics and ecological risk assessment of 11 unheeded metals in sediments of the Chinese Xiangjiang River - Huan Li; Jinqin Yang; Bin Ye; Dongyi Jiang (Environmental Geochemistry and Health, 2019)

Complete mitogenome of the toad species Oreolalax multipunctatus (Anura: Megophryidae) and phylogenetic analyses of Megophryidae - Shize Li; Xinyu Gao; Jianping Jiang; Bin Wang (Conservation Genetics Resources, 2019)

Influences of soil moisture and salt content on loess shear strength in the Xining Basin, northeastern Qinghai-Tibet Plateau - Jiang-tao Fu; Xia-song Hu; Xi-lai Li; Dong-mei Yu; Ya-bin Liu; You-Qing Yang; Zhao-xin Qi; Shu-xia Li (Journal of Mountain Science, 2019)

D-RADA16-RGD-Reinforced Nano-Hydroxyapatite/Polyamide 66 Ternary Biomaterial for Bone Formation - WeiKang Zhao; Bin He; Ao Zhou; Yuling Li; Xiaojun Chen; Qiming Yang; Beike Chen; Bo Qiao; Dianming Jiang (Tissue Engineering and Regenerative Medicine, 2019)

Mitochondrial superoxide anions induced by exogenous oxidative stress determine tumor cell fate: an individual cell-based study - Hui Pan; Bao-hui Wang; Zhou-bin Li; Xing-guo Gong; Yong Qin; Yan Jiang; Wei-li Han (Journal of Zhejiang University-SCIENCE B, 2019)

The seedling and cutting propagation techniques of Acer fabri Hance - Bihua Chen; Bin Jiang; Yongsheng Deng; Juan Zhang; Mingfang Hu; Huihua Fan; Xin Li (Vegetos, 2019)

Enhanced water solubility, antioxidant activity, and oral absorption of hesperetin by D-α-tocopheryl polyethylene glycol 1000 succinate and phosphatidylcholine - Su-Fang Gu; Li-Ying Wang; Ying-Jie Tian; Zhu-Xian Zhou; Jian-Bin Tang; Xiang-Rui Liu; Hai-Ping Jiang; You-Qing Shen (Journal of Zhejiang University-SCIENCE B, 2019)

Pond-bottom decomposition of leaf litters canopied by free-floating vegetation - Ya-Lin Zhang; Hong-Bin Li; Li Xu; Xu Pan; Wen-Bing Li; Jian Liu; Yue-Ping Jiang; Yao-Bin Song; Ming Dong (Environmental Science and Pollution Research, 2019)

Glucose-6-phosphate dehydrogenase in blunt snout bream Megalobrama amblycephala: molecular characterization, tissue distribution, and the responsiveness to dietary carbohydrate levels - Guang-Zhen Jiang; Hua-Juan Shi; Chao Xu; Ding-Dong Zhang; Wen-Bin Liu; Xiang-Fei Li (Fish Physiology and Biochemistry, 2019)

Topical delivery of 3,5,4′-trimethoxy-trans-stilbene-loaded microemulsion-based hydrogel for the treatment of osteoarthritis in a rabbit model - Xiong-Bin Hu; Rong-Rong Kang; Tian-Tian Tang; Yong-Jiang Li; Jun-Yong Wu; Jie-Min Wang; Xin-Yi Liu; Da-Xiong Xiang (Drug Delivery and Translational Research, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Detection and quantification of Aeromonas schubertii in Channa maculata by TaqMan MGB probe fluorescence real‐time quantitative PCR - Chun Liu; Yanming M. Guo; Jizhen Z. Cao; De‐Feng Zhang; Ou‐Qin Chang; Kaibin Li; Fang Wang; Cun‐Bin Shi; Lan Jiang; Qing Wang; Li Lin (Journal of Fish Diseases, 2019)
Aeromonas schubertii is a major epidemiological agent that threatens cultured snakeheads ( Channidae ) and has caused great economic losses in fish‐farming industries in China in recent years. In present study, a specific TaqMan minor groove binder ( MGB ) probe fluorescence real‐time quantitative PCR ( qPCR ) assay was developed to rapidly detect and quantify A. schubertii . A pair of qPCR primers and a TaqMan MGB probe were selected from the rpoD gene, which were shown to be specific for A. schubertii . A high correlation coefficient ( R 2 = 0.9998) in a standard curve with a 103% efficiency was obtained. Moreover, the qPCR method's detection limit was as low as 18 copies/μl, which was 100 times more sensitive than that of conventional PCR . The detection results for the A. schubertii in pond water and fish tissue were consistent with those of the viable counts. Bacterial load changes detected by qPCR in different tissues of snakeheads infected with A. schubertii showed that the gills and intestines may be the entry for A. schubertii , and the spleen and kidney are major sites for A. schubertii replication. The established method in present study should be a useful tool for the early surveillance and quantitation of A. schubertii .

Transcriptome Reveals Differentially Expressed Genes in Saccharum spontaneum GX83-10 Leaf Under Drought Stress - Kai-Chao Wu; Li-Ping Wei; Cheng-Mei Huang; Yuan-Wen Wei; Hui-Qing Cao; Lin Xu; Hai-Bin Luo; Sheng-Li Jiang; Zhi-Nian Deng; Yang-Rui Li (Sugar Tech, 2018)

Clinical Research on Alzheimer’s Disease: Progress and Perspectives - Bin-Lu Sun; Wei-Wei Li; Chi Zhu; Wang-Sheng Jin; Fan Zeng; Yu-Hui Liu; Xian-Le Bu; Jie Zhu; Xiu-Qing Yao; Yan-Jiang Wang (Neuroscience Bulletin, 2018)

The complete mitochondrial genome of the toad species Oreolalax jingdongensis (Anura: Megophryidae) and related phylogenetic analyses - Liuchenghai Jiang; Shize Li; Le Wang; Xinyu Gao; Gang Wang; Bin Wang (Conservation Genetics Resources, 2018)

Design parameters and treatment efficiency of a retrofit bioretention system on runoff nitrogen removal - Chun-bo Jiang; Jia-ke Li; Bin-hong Zhang; Tian-shun Ruan; Huai-en Li; Wen Dong (Environmental Science and Pollution Research, 2018)

Dendrocoumarin: a new benzocoumarin derivative from the stem of Dendrobium nobile - Xue-Ming Zhou; Bin Zhang; Guang-Ying Chen; Chang-Ri Han; Kun-Chi Jiang; Ming-Yue Luo; Bo-Zheng Meng; Wen-Xin Li; Shi-Dai Lin (Natural Product Research, 2018)

Association between prenatal nickel exposure and preterm low birth weight: possible effect of selenium - Xiaojie Sun; Yangqian Jiang; Wei Xia; Shuna Jin; Wenyu Liu; Xin Lin; Hongxiu Liu; Xiaomei Chen; Yang Peng; Han Li; Bin Lu; Shunqing Xu; et al. (Environmental Science and Pollution Research, 2018)

Decreased plasma levels of gasotransmitter hydrogen sulfide in patients with schizophrenia: correlation with psychopathology and cognition - Jian-wen Xiong; Bo Wei; Yan-kun Li; Jin-qiong Zhan; Shu-zhen Jiang; Hai-bo Chen; Kun Yan; Bin Yu; Yuan-jian Yang (Psychopharmacology, 2018)

Design, synthesis, and biological evaluation of thiomatrine derivatives as potential anticancer agents - Zheng Li; Lichuan Wu; Bin Cai; Mengyang Luo; Mengtian Huang; Haroon Ur Rashid; Yuwen Yang; Jun Jiang; Lisheng Wang (Medicinal Chemistry Research, 2018)

Lysine supplement benefits the growth performance, protein synthesis, and muscle development of Megalobrama amblycephala fed diets with fish meal replaced by rice protein concentrate - Wan-Cun Cai; Wen-Bin Liu; Guang-Zhen Jiang; Kai-Zhou Wang; Cun-Xin Sun; Xiang-Fei Li (Fish Physiology and Biochemistry, 2018)

Molecular cloning of adipose triglyceride lipase (ATGL) gene from blunt snout bream and its expression after LPS-induced TNF-α factor - Yong-Jun Dai; Wen-Bin Liu; Xiang-Fei Li; Man Zhou; Chao Xu; Yu Qian; Guang-Zhen Jiang (Fish Physiology and Biochemistry, 2018)

Variable hydrological effects of herbs and shrubs in the arid northeastern Qinghai-Tibet Plateau, China - Ya-bin Liu; Ying Zhang; Jiang-tao Fu; Dong-mei Yu; Xia-song Hu; Xi-lai Li; Zhao-xin Qi; Shu-xia Li (Journal of Mountain Science, 2018)

Dissecting the genetic basis of heavy panicle hybrid rice uncovered Gn1a and GS3 as key genes - Shiguang Wang; Bingtian Ma; Qiang Gao; Guojing Jiang; Lei Zhou; Bin Tu; Peng Qin; Xueqin Tan; Peixiong Liu; Yunhai Kang; Yuping Wang; Weilan Chen; et al. (Theoretical and Applied Genetics, 2018)

42,573 cases of hepatectomy in China: a multicenter retrospective investigation - Binhao Zhang; Bixiang Zhang; Zhiwei Zhang; Zhiyong Huang; Yifa Chen; Minshan Chen; Ping Bie; Baogang Peng; Liqun Wu; Zhiming Wang; Bo Li; Jia Fan; et al. (Science China Life Sciences, 2018)

Two new polyols from cultures of the fungus Daedaleopsis tricolor - Jiang-Yuan Zhao; Jian-Hai Ding; Zheng-Hui Li; Tao Feng; Hong-Bin Zhang; Ji-Kai Liu (Natural Product Research, 2018)

Postnatal Subacute Benzo(a)Pyrene Exposure Caused Neurobehavioral Impairment and Metabolomic Changes of Cerebellum in the Early Adulthood Period of Sprague-Dawley Rats - Chunlin Li; Jing Wang; Qiuping Su; Kai Yang; Chengzhi Chen; XueJun Jiang; Tingli Han; Shuqun Cheng; Tingting Mo; Ruiyuan Zhang; Bin Peng; Yuming Guo; et al. (Neurotoxicity Research, 2018)

Sevoflurane Affects Oxidative Stress and Alters Apoptosis Status in Children and Cultured Neural Stem Cells - Xue Zhou; Dihan Lu; Wen-da Li; Xiao-hui Chen; Xiao-yu Yang; Xi Chen; Zhi-bin Zhou; Jiang-Hong Ye; Xia Feng (Neurotoxicity Research, 2018)

Effects of probiotic on microfloral structure of live feed used in larval breeding of turbot Scophthalmus maximus - Yan Jiang; Zheng Zhang; Yingeng Wang; Yayun Jing; Meijie Liao; Xiaojun Rong; Bin Li; Guiping Chen; Hesen Zhang (Journal of Oceanology and Limnology, 2018)

Occurrence and health risk assessment of organotins in waterworks and the source water of the Three Gorges Reservoir Region, China - Ting Deng; Lei Wu; Jun-Min Gao; Bin Zhou; Ya-Li Zhang; Wen-Nan Wu; Zhuo-Heng Tang; Wen-Chao Jiang; Wei-Lin Huang (Environmental Science and Pollution Research, 2018)

A new cyclic dipeptide from cultures of Coprinus plicatilis - Jiang-Yuan Zhao; Jian-Hai Ding; Zheng-Hui Li; Tao Feng; Hong-Bin Zhang; Ji-Kai Liu (Natural Product Research, 2018)

U–Pb zircon, geochemical and Sr–Nd–Hf isotopic constraints on age and origin of the intrusions from Wunugetushan porphyry deposit, Northeast China: implication for Triassic–Jurassic Cu–Mo mineralization in Mongolia–Erguna metallogenic belt - Kui-Feng Mi; Zhen-Jiang Liu; Rui-Bin Liu; Chun-Feng Li; Jian-Ping Wang; Run-Min Peng (International Geology Review, 2018)

Molecular characterization of fructose-1,6-bisphosphatase 1b in blunt snout bream Megalobrama amblycephala and the transcriptional response to glucose loading after the adaptation to high-carbohydrate diets - Xiang-Fei Li; Chao Xu; Guang-Zhen Jiang; Ding-Dong Zhang; Wen-Bin Liu (Fish Physiology and Biochemistry, 2017)

An available formula of the sandy beach state induced by plunging waves - Changbo Jiang; Zhiyuan Wu; Jie Chen; Bin Deng; Yuannan Long; Lianjie Li (Acta Oceanologica Sinica, 2017)

Deep Fracturing of the Hard Rock Surrounding a Large Underground Cavern Subjected to High Geostress: In Situ Observation and Mechanism Analysis - Xia-Ting Feng; Shu-Feng Pei; Quan Jiang; Yang-Yi Zhou; Shao-Jun Li; Zhi-Bin Yao (Rock Mechanics and Rock Engineering, 2017)

Novel adefovir mono L-amino acid ester, mono bile acid ester derivatives: Design, synthesis, biological evaluation, and molecular docking study - Ya Chen; Wen Zheng Zhang; Jing Li; Tao Xiao; Jiang Xia Liu; Min Luo; Hang Su; Xiao-Zhong Fu; Ting Liu; Yong-Xi Dong; Yong-Long Zhao; Bin He; et al. (Medicinal Chemistry Research, 2017)

Construction, Selection and Immunogenicity of Recombinant Fowlpox Candidate Vaccine Co-expressing HIV-1 gag and gp145 - Yilong Zhu; Yan Guo; Shouwen Du; Cunxia Liu; Maopeng Wang; Dayong Ren; Fei Zhao; Yanfang Zhang; Wenchao Sun; Yiquan Li; Tingting Cao; Yingyue Jiang; et al. (Indian Journal of Microbiology, 2017)

Multivariate multi-scale weighted permutation entropy analysis of EEG complexity for Alzheimer’s disease - Bin Deng; Lihui Cai; Shunan Li; Ruofan Wang; Haitao Yu; Yingyuan Chen; Jiang Wang (Cognitive Neurodynamics, 2017)

RNAi as a tool to control the sex ratio of mouse offspring by interrupting Zfx/Zfy genes in the testis - YongSheng Zhang; JiFeng Xi; Bin Jia; XiangZu Wang; XuHai Wang; ChaoCheng Li; YaQiang Li; XianCun Zeng; RuiWen Ying; Xin li; Song Jiang; FangYuan Yuan (Mammalian Genome, 2017)

Experimental and numerical investigations of a catastrophic long-runout landslide in Zhenxiong, Yunnan, southwestern China - Yueping Yin; Aiguo Xing; Gonghui Wang; Zhen Feng; Bin Li; Yao Jiang (Landslides, 2017)

Spatio-temporal assessments of rockburst hazard combining b values and seismic tomography - Jing Li; Si-Yuan Gong; Jiang He; Wu Cai; Guang-An Zhu; Chang-Bin Wang; Tian Chen (Acta Geophysica, 2017)

A new patchoulane-type sesquiterpenoid glycoside from the roots of Croton crassifolius - Qing-Qing Yuan; Wei-Bin Song; Wen-Qiong Wang; Li-Jiang Xuan (Natural Product Research, 2017)

Glucocorticoids Prevent Enterovirus 71 Capsid Protein VP1 Induced Calreticulin Surface Exposure by Alleviating Neuronal ER Stress - Dan-Dan Hu; Jian-Ning Mai; Li-Ya He; Pei-Qing Li; Wen-Xiong Chen; Jian-Jiang Yan; Wei-Dong Zhu; Li Deng; Dan Wei; Di-Hui Liu; Si-Da Yang; Zhi-Bin Yao (Neurotoxicity Research, 2017)

Tenuigenin promotes the osteogenic differentiation of bone mesenchymal stem cells in vitro and in vivo - Hua-ji Jiang; Xing-gui Tian; Shou-bin Huang; Guo-rong Chen; Min-jun Huang; Yu-hui Chen; Bin Yan; Sheng-fa Li; Jia-jun Tang; Hui-yu Zhao; Liang Wang; Zhong-min Zhang (Cell and Tissue Research, 2017)

p38 MAPK Participates in the Mediation of GLT-1 Up-regulation During the Induction of Brain Ischemic Tolerance by Cerebral Ischemic Preconditioning - Min Zhang; Jian-Xue Gong; Jia-Lei Wang; Meng-Yang Jiang; Li Li; Yu-Yan Hu; Jie Qi; Ling-Yan Zhang; Hang Zhao; Xin Cui; Xiao-Hui Xian; Wen-Bin Li (Molecular Neurobiology, 2017)

Thrombospondin-4 Promotes Neuronal Differentiation of NG2 Cells via the ERK/MAPK Pathway - Hai Jie Yang; Shuang Ping Ma; Fei Ju; Ya Ping Zhang; Zhi Chao Li; Bin Bin Zhang; Jun Jiang Lian; Lei Wang; Bin Feng Cheng; Mian Wang; Zhi Wei Feng (Journal of Molecular Neuroscience, 2016)

Risk assessment of dietary exposure to aluminium in the Chinese population - Ning Ma; Zhao-Ping Liu; Da-Jin Yang; Jiang Liang; Jiang-Hui Zhu; Hai-Bin Xu; Feng-Qin Li; Ning Li (Food Additives & Contaminants: Part A, 2016)

Identifying minimal hepatic encephalopathy in cirrhotic patients by measuring spontaneous brain activity - Hua-Jun Chen; Ling Zhang; Long-Feng Jiang; Qiu-Feng Chen; Jun Li; Hai-Bin Shi (Metabolic Brain Disease, 2016)

Support Vector Machine Modeling Using Particle Swarm Optimization Approach for the Retrieval of Atmospheric Ammonia Concentrations - Jiawei Zhang; Frank K. Tittel; Longwen Gong; Rafal Lewicki; Robert J. Griffin; Wenzhe Jiang; Bin Jiang; Mingbao Li (Environmental Modeling & Assessment, 2016)

Autotoxicity of the soil of consecutively cultured tea plantations on tea (Camellia sinensis) seedlings - Jiang-Hua Ye; Hai-Bin Wang; Xiao-Yan Yang; Qi Zhang; Jia-Yu Li; Xiao-Li Jia; Xiang-Hai Kong; Hai-Bin He (Acta Physiologiae Plantarum, 2016)

Proteomic Changes in the Stem of Wild Pteridium aquilinum During Development - Jin-song Huang; Yixiang Zhang; Jiang Li; Li-bin Wang; Zhi-fang Yu (Journal of Plant Growth Regulation, 2016)

Controls of seed quantity and quality on seedling recruitment of smith fir along altitudinal gradient in southeastern Tibetan Plateau - Jing-sheng Wang; Ji-guang Feng; Bao-xiong Chen; Pei-li Shi; Jun-long Zhang; Jiang-ping Fang; Zhi-kai Wang; Shuai-chen Yao; Lu-bin Ding (Journal of Mountain Science, 2016)

CLU rs9331888 Polymorphism Contributes to Alzheimer’s Disease Susceptibility in Caucasian But Not East Asian Populations - Shuyan Zhang; Xuling Li; Guoda Ma; Yongshuai Jiang; Mingzhi Liao; Rennan Feng; Liangcai Zhang; Jiafeng Liu; Guangyu Wang; Bin Zhao; Qinghua Jiang; Keshen Li; et al. (Molecular Neurobiology, 2016)

Feeding rates affect growth, intestinal digestive and absorptive capabilities and endocrine functions of juvenile blunt snout bream Megalobrama amblycephala - Chao Xu; Xiang-Fei Li; Hong-Yan Tian; Guang-Zhen Jiang; Wen-Bin Liu (Fish Physiology and Biochemistry, 2016)

SIL1 Rescued Bip Elevation-Related Tau Hyperphosphorylation in ER Stress - Zan-Chao Liu; Jiang Chu; Li Lin; Jie Song; Lin-Na Ning; Hong-Bin Luo; Shu-Sheng Yang; Yan Shi; Qun Wang; Na Qu; Qi Zhang; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2016)

Pattern of NDVI-based vegetation greening along an altitudinal gradient in the eastern Himalayas and its response to global warming - Haidong Li; Jiang Jiang; Bin Chen; Yingkui Li; Yuyue Xu; Weishou Shen (Environmental Monitoring and Assessment, 2016)

Recombinant expression, purification, and characterization of an acyl-CoA binding protein from Aspergillus oryzae - Qing Hao; Xiaoguang Liu; Guozhong Zhao; Lu Jiang; Ming Li; Bin Zeng (Biotechnology Letters, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Effects of salinity on activity and expression of enzymes involved in ionic, osmotic, and antioxidant responses in Eurya emarginata - Jia-Lang Zheng; Lu-Yao Zhao; Bin Shen; Li-Hua Jiang; Ai-Yi Zhu (Acta Physiologiae Plantarum, 2016)

Identifying the Association Between Alzheimer’s Disease and Parkinson’s Disease Using Genome-Wide Association Studies and Protein-Protein Interaction Network - Guiyou Liu; Xinjie Bao; Yongshuai Jiang; Mingzhi Liao; Qinghua Jiang; Rennan Feng; Liangcai Zhang; Guoda Ma; Zugen Chen; Guangyu Wang; Renzhi Wang; Bin Zhao; et al. (Molecular Neurobiology, 2015)

Gadd45b Mediates Axonal Plasticity and Subsequent Functional Recovery After Experimental Stroke in Rats - Bin Liu; Long-ling Li; Xiao-dan Tan; Yan-hong Zhang; Ying Jiang; Guo-qian He; Qian Chen; Chang-qing Li (Molecular Neurobiology, 2015)

Aureoboletus formosus, a new bolete species from Hunan Province of China - Ming Zhang; Tai-Hui Li; Chao-Qun Wang; Bin Song; Jiang Xu (Mycological Progress, 2015)

Integrating Genome-Wide Association Study and Brain Expression Data Highlights Cell Adhesion Molecules and Purine Metabolism in Alzheimer’s Disease - Zimin Xiang; Meiling Xu; Mingzhi Liao; Yongshuai Jiang; Qinghua Jiang; Rennan Feng; Liangcai Zhang; Guoda Ma; Guangyu Wang; Zugen Chen; Bin Zhao; Tiansheng Sun; et al. (Molecular Neurobiology, 2015)

CD33 rs3865444 Polymorphism Contributes to Alzheimer’s Disease Susceptibility in Chinese, European, and North American Populations - Xingwang Li; Ning Shen; Shuyan Zhang; Jiafeng Liu; Qinghua Jiang; Mingzhi Liao; Rennan Feng; Liangcai Zhang; Guangyu Wang; Guoda Ma; Haihong Zhou; Zugen Chen; et al. (Molecular Neurobiology, 2015)

Analyzing 54,936 Samples Supports the Association Between CD2AP rs9349407 Polymorphism and Alzheimer’s Disease Susceptibility - Hongyuan Chen; Guihua Wu; Yongshuai Jiang; Rennan Feng; Mingzhi Liao; Liangcai Zhang; Guoda Ma; Zugen Chen; Bin Zhao; Keshen Li; Chunjiang Yu; Guiyou Liu (Molecular Neurobiology, 2015)

A subduction-related metasomatically enriched mantle origin for the Luoboling and Zhongliao Cretaceous granitoids from South China: implications for magma evolution and Cu–Mo mineralization - Bin Li; Shao-Yong Jiang (International Geology Review, 2015)

Cytotoxicity of benzophenanthridine alkaloids from the roots of Zanthoxylum nitidum (Roxb.) DC. var. fastuosum How ex Huang - Cheng-Fang Wang; Li Fan; Mei Tian; Shu-Shan Du; Zhi-Wei Deng; Jiang-Bin Feng; Yong-Yan Wang; Xu Su (Natural Product Research, 2015)

Pure total flavonoids from Citrus paradisi Macfadyen act synergistically with arsenic trioxide in inducing apoptosis of Kasumi-1 leukemia cells in vitro - Bo Wang; Sheng-yun Lin; Ying-ying Shen; Li-qiang Wu; Zhen-zhen Chen; Jing Li; Zhi Chen; Wen-bin Qian; Jian-ping Jiang (Journal of Zhejiang University-SCIENCE B, 2015)

Mapping and evaluating quantitative trait loci for blast resistance under natural infection conditions using an advanced backcross population in rice - Haichao Jiang; Bin Yan; Taipin Duan; Yibo Li; Guanjun Gao; Qinglu Zhang; Jinghua Xiao; Caiguo Xu; Gonghao Jiang; Yuqing He (Euphytica, 2015)

An Updated Analysis with 85,939 Samples Confirms the Association Between CR1 rs6656401 Polymorphism and Alzheimer’s Disease - Ning Shen; Bin Chen; Yongshuai Jiang; Rennan Feng; Mingzhi Liao; Liangcai Zhang; Fujun Li; Guoda Ma; Zugen Chen; Bin Zhao; Keshen Li; Guiyou Liu (Molecular Neurobiology, 2015)

Cytokine production suppression by culture supernatant of B16F10 cells and amelioration by Ganoderma lucidum polysaccharides in activated lymphocytes - Li-Xin Sun; Wei-Dong Li; Zhi-Bin Lin; Xin-Suo Duan; En-Hong Xing; Miao-Miao Jiang; Ning Yang; Hai-Hua Qi; Yu Sun; Min Li; Yan-Dong Niu; Jie Lu (Cell and Tissue Research, 2015)

Promotion of expression of interferon-stimulated genes in U937 monocytic cells by HIV RNAs, measured using stable isotope labeling with amino acids in cell culture (SILAC) - Yulan Li; Bin Wen; Ran Chen; Feng Jiang; Xiaofang Zhao; Xin Deng (Archives of Virology, 2015)

Protein prenylation and human diseases: a balance of protein farnesylation and geranylgeranylation - Na Xu; Ning Shen; XiuXing Wang; Shan Jiang; Bin Xue; ChaoJun Li (Science China Life Sciences, 2015)

The Marginal Division of the Striatum and Hippocampus Has Different Role and Mechanism in Learning and Memory - Si-Yun Shu; Gang Jiang; Qi-Yi Zeng; Bin Wang; Hong Li; Lin Ma; Harry Steinbusch; Cai Song; Wood-Yee Chan; Xu-Hong Chen; Yon-Ming Wu; Rong Bao; et al. (Molecular Neurobiology, 2015)

Co-transplantation of Hematopoietic Stem Cells and Cxcr4 Gene-Transduced Mesenchymal Stem Cells Promotes Hematopoiesis - Wei Chen; Miao Li; Guizhen Su; Yu Zang; Zhiling Yan; Hai Cheng; Bin Pan; Jiang Cao; Qingyun Wu; Kai Zhao; Feng Zhu; Lingyu Zeng; et al. (Cell Biochemistry and Biophysics, 2015)

Evidence for Visually Mediated Copulation Frequency in the Scarab Beetle Anomala corpulenta - Jin Miao; Yu-Qing Wu; Ke-Bin Li; Yue-Li Jiang; Zhong-jun Gong; Yun Duan; Tong Li (Journal of Insect Behavior, 2015)

In vivo construction of tissue-engineered cartilage using adipose-derived stem cells and bioreactor technology - Hongjun Kang; Shibi Lu; Jiang Peng; Qiang Yang; Shuyun Liu; Li Zhang; Jingxiang Huang; Xiang Sui; Bin Zhao; Aiyuan Wang; Wenjing Xu; Quanyi Guo; et al. (Cell and Tissue Banking, 2015)

Effects of fructooligosaccharide on immune response, antioxidant capability and HSP70 and HSP90 expressions of blunt snout bream (Megalobrama amblycephala) under high ammonia stress - Chun-Nuan Zhang; Xiang-Fei Li; Hong-Yan Tian; Ding-Dong Zhang; Guang-Zhen Jiang; Kang-Le Lu; Guang-Xia Liu; Wen-Bin Liu (Fish Physiology and Biochemistry, 2015)

UKF-based closed loop iterative learning control of epileptiform wave in a neural mass model - Bonan Shan; Jiang Wang; Bin Deng; Xile Wei; Haitao Yu; Huiyan Li (Cognitive Neurodynamics, 2015)

Methylopila henanense sp. nov., a novel methylotrophic bacterium isolated from tribenuron methyl-contaminated wheat soil - Ya-Nan Wang; Wen-Yu Tian; Wei-Hong He; Guo-Can Chen; Ming-Li An; Bin Jia; Li Liu; Yang Zhou; Shuang-Jiang Liu (Antonie van Leeuwenhoek, 2015)

Composition and variation analysis of TCR β-chain CDR3 repertoire in the thymus and spleen of MRL/lpr mouse at different ages - Zhou Li; Ma Long; Liu ChunMei; Shi Bin; Yu Jiang; Ma Rui; Ma Qingqing; Yao XinSheng (Immunogenetics, 2015)

Analyzing Large-Scale Samples Confirms the Association Between the ABCA7 rs3764650 Polymorphism and Alzheimer’s Disease Susceptibility - Guiyou Liu; Fujun Li; Shuyan Zhang; Yongshuai Jiang; Guoda Ma; Hong Shang; Jiafeng Liu; Rennan Feng; Liangcai Zhang; Mingzhi Liao; Bin Zhao; Keshen Li (Molecular Neurobiology, 2014)

Acutissimanide, a new lignan with antioxidant activity isolated from the bark of Quercus acutissima Carruth - Xiao-Li Zeng; Guang-Miao Fu; Kai Tian; Jing-Xian Sun; Hua-Bin Xiong; Xiang-Zhong Huang; Zhi-Yong Jiang (Natural Product Research, 2014)

Protective effect of vitexin compound B-1 against hypoxia/reoxygenation-induced injury in differentiated PC12 cells via NADPH oxidase inhibition - Zhong-Bao Yang; Bin Tan; Ting-Bo Li; Zheng Lou; Jun-Lin Jiang; Ying-Jun Zhou; Jie Yang; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Geochemistry of magmatic and hydrothermal zircon from the highly evolved Baerzhe alkaline granite: implications for Zr–REE–Nb mineralization - Wu-Bin Yang; He-Cai Niu; Qiang Shan; Wei-Dong Sun; Hong Zhang; Ning-Bo Li; Yu-Hang Jiang; Xue-Yuan Yu (Mineralium Deposita, 2014)

The CLU Gene rs11136000 Variant is Significantly Associated with Alzheimer’s Disease in Caucasian and Asian Populations - Guiyou Liu; Haiyang Wang; Jiafeng Liu; Jingbo Li; Hali Li; Guoda Ma; Yongshuai Jiang; Zugen Chen; Bin Zhao; Keshen Li (NeuroMolecular Medicine, 2014)

( − )-Arctigenin as a lead compound for anticancer agent - Gui-Rong Chen; Hong-Fu Li; De-Qiang Dou; Yu-Bin Xu; Hong-Shuai Jiang; Fu-Rui Li; Ting-Guo Kang (Natural Product Research, 2013)

Consistency of the Key Genotypes of Orientia tsutsugamushi in Scrub Typhus Patients, Rodents, and Chiggers from a New Endemic Focus of Northern China - Yun-Xi Liu; Na Jia; Yu-Bin Xing; Ji-Jiang Suo; Ming-Mei Du; Ning Jia; Yan Gao; Li-Jun Xie; Bo-Wei Liu; Shi-Wang Ren (Cell Biochemistry and Biophysics, 2013)

Overexpression of the Mesenchymal Stem Cell Cxcr4 Gene in Irradiated Mice Increases the Homing Capacity of These Cells - Wei Chen; Miao Li; Hai Cheng; Zhiling Yan; Jiang Cao; Bin Pan; Wei Sang; Qingyun Wu; Lingyu Zeng; Zhenyu Li; Kailin Xu (Cell Biochemistry and Biophysics, 2013)

A Murine Model of Hepatic Veno-occlusive Disease Induced by Allogeneic Hematopoietic Stem Cell Transplantation - Lingyu Zeng; Licai An; Ting Fang; Bin Pan; Haiying Sun; Chong Chen; Jiang Cao; Zhenyu Li; Kailin Xu (Cell Biochemistry and Biophysics, 2013)

Isolation and characterization of fifteen microsatellite loci in the Tibetan fox (Vulpes ferrilata) - MIN LI; XIAO MING WANG; WEI BIN JIANG; PAN YU HUA; ZHENG HUAN WANG (Journal of Genetics, 2013)

Identification of differentially expressed genes in American cockroach ovaries and testes by suppression subtractive hybridization and the prediction of its miRNAs - Wan Chen; Guo-Fang Jiang; Shu-Hong Sun; Yong Lu; Fei Ma; Bin Li (Molecular Genetics and Genomics, 2013)

The association of SNPs in Hsp90β gene 5′ flanking region with thermo tolerance traits and tissue mRNA expression in two chicken breeds - Zhuo-Yu Chen; Jian-Kang Gan; Xiong Xiao; Li-Yan Jiang; Xi-Quan Zhang; Qing-Bin Luo (Molecular Biology Reports, 2013)

Novel triterpenoid saponins from the seeds of Celosia argentea L. - Qing Bin Wu; Yan Wang; Lin Liang; Qian Jiang; Mei Li Guo; Jun Jie Zhang (Natural Product Research, 2013)

Quantitative assessment of acute kidney injury by noninvasive arterial spin labeling perfusion MRI: a pilot study - Jian Dong; Li Yang; Tao Su; XueDong Yang; Bin Chen; Jue Zhang; XiaoYing Wang; XueXiang Jiang (Science China Life Sciences, 2013)

PICALM Gene rs3851179 Polymorphism Contributes to Alzheimer’s Disease in an Asian Population - Guiyou Liu; Shuyan Zhang; Zhiyou Cai; Guoda Ma; Liangcai Zhang; Yongshuai Jiang; Rennan Feng; Mingzhi Liao; Zugen Chen; Bin Zhao; Keshen Li (NeuroMolecular Medicine, 2013)

Intergeneric hybrid between Chrysanthemum × morifolium and Artemisia japonica achieved via embryo rescue shows salt tolerance - Wen-ying Zhu; Jia-fu Jiang; Su-mei Chen; Liang Wang; Li-li Xu; Hai-bin Wang; Pei-ling Li; Zhi-yong Guan; Fa-di Chen (Euphytica, 2013)

Three genetic systems controlling growth, development and productivity of rice (Oryza sativa L.): a reevaluation of the ‘Green Revolution’ - Fan Zhang; Yun-Zhu Jiang; Si-Bin Yu; J. Ali; A. H. Paterson; G. S. Khush; Jian-Long Xu; Yong-Ming Gao; Bin-Ying Fu; R. Lafitte; Zhi-Kang Li (Theoretical and Applied Genetics, 2013)

Phylogeographic Patterns of mtDNA Variation Revealed Multiple Glacial Refugia for the Frog Species Feirana taihangnica Endemic to the Qinling Mountains - Bin Wang; Jianping Jiang; Feng Xie; Cheng Li (Journal of Molecular Evolution, 2013)

Functional polymorphisms in PIN1 promoter and esophageal carcinoma susceptibility in Chinese population - Yonghe You; Jieqiong Deng; Jian Zheng; Lan Jiang; Na Li; Hongchun Wu; Wei Li; Jiachun Lu; Yifeng Zhou; Bin Ni (Molecular Biology Reports, 2013)

Multi-scale order recurrence quantification analysis of EEG signals evoked by manual acupuncture in healthy subjects - Guosheng Yi; Jiang Wang; Hongrui Bian; Chunxiao Han; Bin Deng; Xile Wei; Huiyan Li (Cognitive Neurodynamics, 2013)

Reaction temperature alters chorzoxazone metabolism in carp (Cyprinus carpio) hepatic microsomes - Zaijian Li; Weiyuan Zhang; Xiaocong Lu; Jing Li; Bin He; Hui Jiang; Shasha Wang; Zheng Lu; Chunmei Wang; Jiyue Cao (Fish Physiology and Biochemistry, 2012)

Comparative analysis of water stress-responsive transcriptomes in drought-susceptible and -tolerant wheat (Triticum aestivum L.) - Yong Chun Li; Fan Rong Meng; Chun Yan Zhang; Ning Zhang; Ming Shan Sun; Jiang Ping Ren; Hong Bin Niu; Xiang Wang; Jun Yin (Journal of Plant Biology, 2012)

Molecular biomarkers of colorectal cancer: prognostic and predictive tools for clinical practice - Wei-qin Jiang; Fang-fang Fu; Yang-xia Li; Wei-bin Wang; Hao-hao Wang; Hai-ping Jiang; Li-song Teng (Journal of Zhejiang University-SCIENCE B, 2012)

A Highly Sensitive Fluorescent Probe for HClO and Its Application in Live Cell Imaging - Qing-Ping Zuo; Zuo-Jun Li; Yong-Hua Hu; Bin Li; Li-Hua Huang; Chun-Jiang Wang; Shi-Kun Liu; Hai-Qiang Liao (Journal of Fluorescence, 2012)

Seroprevalence of porcine cytomegalovirus and sapovirus infection in pigs in Hunan province, China - Guo-Hua Liu; Run-Cheng Li; Jing Li; Ze-Bin Huang; Chao-Ting Xiao; Wei Luo; Meng Ge; Da-Liang Jiang; Xing-Long Yu (Archives of Virology, 2012)

NnHSP17.5, a cytosolic class II small heat shock protein gene from Nelumbo nucifera, contributes to seed germination vigor and seedling thermotolerance in transgenic Arabidopsis - Yuliang Zhou; Huhui Chen; Pu Chu; Yin Li; Bin Tan; Yu Ding; Edward W. T. Tsang; Liwen Jiang; Keqiang Wu; Shangzhi Huang (Plant Cell Reports, 2012)

Effects of insulin-like growth factor-1 on the properties of mesenchymal stem cells in vitro - Yu-li Huang; Ruo-feng Qiu; Wei-yi Mai; Jian Kuang; Xiao-yan Cai; Yu-gang Dong; Yun-zhao Hu; Yuan-bin Song; An-ping Cai; Zhi-gao Jiang (Journal of Zhejiang University-SCIENCE B, 2012)

A drug-laden elastomer for surgical treatment of anal fistula - Hairui Li; Bin Jiang; Jun Yan; Zhonghua Yang; Yanni Chen; Weiping Zhang; Alex C. Choy; Chi-Ying M. Lee; Lifeng Kang (Drug Delivery and Translational Research, 2011)

Production of transgenic rice new germplasm with strong resistance against two isolations of Rice stripe virus by RNA interference - Jin Ma; Yunzhi Song; Bin Wu; Mingsong Jiang; Kaidong Li; Changxiang Zhu; Fujiang Wen (Transgenic Research, 2011)

Plasma Paraoxonase-1, Oxidized Low-Density Lipoprotein and Lipid Peroxidation Levels in Gout Patients - Xing-Liang Jiang; Min Li; Jing-Guo Zhou; Qi-Bin Yang; Li-Jun Du; Juan Du (Cell Biochemistry and Biophysics, 2011)

Association of a LSP1 gene rs3817198T>C polymorphism with breast cancer risk: evidence from 33,920 cases and 35,671 controls - Min-Bin Chen; Chen Li; Wen-Xiang Shen; Yu-Jiang Guo; Wei Shen; Pei-Hua Lu (Molecular Biology Reports, 2011)

MED19 promotes proliferation and tumorigenesis of lung cancer - Mei Sun; Rui Jiang; Jin-dong Li; Shu-li Luo; Hong-Wen Gao; Cheng-yan Jin; Dong-lei Shi; Chun-guang Wang; Bin Wang; Xing-yi Zhang (Molecular and Cellular Biochemistry, 2011)

Archaeal and bacterial diversity in hot springs on the Tibetan Plateau, China - Qiuyuan Huang; Christina Z. Dong; Raymond M. Dong; Hongchen Jiang; Shang Wang; Genhou Wang; Bin Fang; Xiaoxue Ding; Lu Niu; Xin Li; Chuanlun Zhang; Hailiang Dong (Extremophiles, 2011)

The complete genome sequence of a novel T4-like bacteriophage, IME08 - Huanhuan Jiang; Xiaofang Jiang; Sheng Wang; Cun Li; Bin Chen; Xiaoping An; Zhiqiang Mi; Jiankui Chen; Yigang Tong (Archives of Virology, 2011)

Investigation on the direct radiative effect of fossil fuel black-carbon aerosol over China - Bingliang Zhuang; Fei Jiang; Tijian Wang; Shu Li; Bin Zhu (Theoretical and Applied Climatology, 2011)

Pseudoxanthomonas jiangsuensis sp. Nov., a DDT-Degrading Bacterium Isolated from a Long-Term DDT-Polluted Soil - Guang-li Wang; Meng Bi; Bin Liang; Jian-dong Jiang; Shun-peng Li (Current Microbiology, 2011)

China’s lakes at present: Number, area and spatial distribution - RongHua Ma; GuiShan Yang; HongTao Duan; JiaHu Jiang; SuMin Wang; XueZhi Feng; AiNong Li; FanXiang Kong; Bin Xue; JingLu Wu; ShiJie Li (Science China Earth Sciences, 2011)

Sodium sulfite is a potential hypoxia inducer that mimics hypoxic stress in Caenorhabditis elegans - Bin Jiang; Changhong Ren; Yuan Li; Yiming Lu; Weiguang Li; Yonghong Wu; Yan Gao; Peter J. Ratcliffe; Huqi Liu; Chenggang Zhang (JBIC Journal of Biological Inorganic Chemistry, 2011)

Transgenic barley with overexpressed PTrx increases aluminum resistance in roots during germination - Qiao-yun Li; Hong-bin Niu; Jun Yin; Hong-bo Shao; Ji-shan Niu; Jiang-ping Ren; Yong-chun Li; Xiang Wang (Journal of Zhejiang University-SCIENCE B, 2010)

Hydrolytic Dechlorination of Chlorothalonil by Ochrobactrum sp. CTN-11 Isolated from a Chlorothalonil-Contaminated Soil - Bin Liang; Rong Li; Dong Jiang; Jiquan Sun; Jiguo Qiu; Yanfu Zhao; Shunpeng Li; Jiandong Jiang (Current Microbiology, 2010)

Homologous overexpression of a lipase from Burkholderia cepacia using the lambda Red recombinase system - Bin Jia; Jiang-Ke Yang; Wen-Shan Liu; Xu Li; Yun-Jun Yan (Biotechnology Letters, 2010)

Distribution, development and proliferation of interstitial cells of Cajal in murine colon: an immunohistochemical study from neonatal to adult life - Juan Han; Wen-Hao Shen; You-Zhao Jiang; Bin Yu; Yang-Tao He; Nan Li; Feng Mei (Histochemistry and Cell Biology, 2010)

Coexpression and characterization of the human large-conductance Ca2+-activated K+ channel α + β1 subunits in HEK293 cells - Jun Li; Chang-Lei Deng; Fang Gao; Jiu-Hua Cheng; Zhi-Bin Yu; Li Liu; Man-Jiang Xie (Molecular and Cellular Biochemistry, 2009)

Two new N -oxide Lycopodium alkaloids from Huperzia serrata - Heng-Bin Wang; Chang-Heng Tan; Jun-Jie Tan; Shi-Jin Qu; Yi-Lei Chen; Yi-Ming Li; Shan-Hao Jiang; Da-Yuan Zhu (Natural Product Research, 2009)

A thermophilic and acid stable family-10 xylanase from the acidophilic fungus Bispora sp. MEY-1 - Huiying Luo; Jiang Li; Jun Yang; Hui Wang; Yuhui Yang; Huoqing Huang; Pengjun Shi; Tiezheng Yuan; Yunliu Fan; Bin Yao (Extremophiles, 2009)

Phase I clinical trial on intracoronary administration of Ad-hHGF treating severe coronary artery disease - Zhi-Jian Yang; You-Rong Zhang; Bo Chen; Shu-Lan Zhang; En-Zhi Jia; Lian-Sheng Wang; Tie-Bing Zhu; Chun-Jian Li; Hui Wang; Jun Huang; Ke-Jiang Cao; Wen-Zhu Ma; et al. (Molecular Biology Reports, 2009)

Long-term treatment of l-3-n-butylphthalide attenuated neurodegenerative changes in aged rats - Shiping Ma; Shaofeng Xu; Bin Liu; Jiang Li; Nan Feng; Ling Wang; Xiaoliang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

A suicidal DNA vaccine co-expressing two major membrane-associated proteins of porcine reproductive and respiratory syndrome virus antigens induce protective responses - Yunbo Jiang; Liurong Fang; Shaobo Xiao; Bin Li; Yongfei Pan; Rui Luo; Huanchun Chen (Biotechnology Letters, 2009)

Effects of saltmarsh invasion by Spartina alterniflora on arthropod community structure and diets - Yu-Tong Wu; Cheng-Huan Wang; Xiao-Dong Zhang; Bin Zhao; Li-Fen Jiang; Jia-Kuan Chen; Bo Li (Biological Invasions, 2009)

An age-dependent proliferation is involved in the postnatal development of interstitial cells of Cajal in the small intestine of mice - Feng Mei; Jiang Zhu; Sheng Guo; De-shan Zhou; Juan Han; Bin Yu; Shi-feng Li; Zhong-yong Jiang; Cheng-jie Xiong (Histochemistry and Cell Biology, 2009)

2D-cell experiment on methyl tert-butyl ether transport in saturated zone of groundwater - Hong Li; Xingang Li; Chuanbo Gao; Guoqiang Huang; Bin Jiang (Chinese Geographical Science, 2007)

Mechanism of Lysophosphatidylcholine-Induced Lysosome Destabilization - Jin-Shan Hu; Ying-Bin Li; Jiong-Wei Wang; Lin Sun; Guo-Jiang Zhang (The Journal of Membrane Biology, 2007)

Construction and characterization of a transformation-competent artificial chromosome (TAC) library ofZizania latifolia (Griseb.) - Fan Na Kong; Shao Mei Jiang; Li Xue Shi; Cheng Li Song; Min De Jin; Shao Lin Jiang; Manli Weng; Bin Wang (Plant Molecular Biology Reporter, 2006)

A study on cometabolic bioventing for the in situ remediation of trichloroethylene - Hong Sui; Xingang Li; Guoqiang Huang; Bin Jiang (Environmental Geochemistry and Health, 2006)

Cloning and Characterization of a Second form of the Rice Adenine Phosphoribosyl Transferase Gene (OsAPT2) and its Association with TGMS - Chun-Jiang Zhou; Jun Li; Ji-Cheng Zou; Feng-Shan Liang; Chun-Jiang Ye; De-Min Jin; Man-Li Weng; Bin Wang (Plant Molecular Biology, 2006)

Identification ofporphyra lines (rhodophyta) by AFLP DNA fingerprinting and molecular markers - Jian Wei Sun; Min De Jin; Chun Jiang Zhou; Qing Kai Yang; Man Li Weng; Lin De Duan; Pu Xu; Jia Hai Ma; Bin Wang (Plant Molecular Biology Reporter, 2005)

Genome-wide Introgression Lines and their Use in Genetic and Molecular Dissection of Complex Phenotypes in Rice (Oryza sativa L.) - Zhi-Kang Li; Bin-Ying Fu; Yong-Ming Gao; Jian-Long Xu; J. Ali; H. R. Lafitte; Yun-Zhu Jiang; J. Domingo Rey; C. H. M. Vijayakumar; R. Maghirang; Tian-Qing Zheng; Ling-Hua Zhu (Plant Molecular Biology, 2005)

Evaluation of genetic diversity and germ plasm identification of 44 species, clones, and cultivars from 5 sections of the genusPopulus based on amplified fragment length polymorphism analysis - Chun Jiang Zhou; Hong Zhu Song; Jin Hua Li; Jian Wei Sun; Min De Jin; Qi Wen Zhang; Bin Wang (Plant Molecular Biology Reporter, 2005)

Hydrogenation properties of mechanically milled Mg2Ni0.8Cr0.2-CoO/Al2O3 composites - Xiu-li Wang; Jiang-ping Tu; Chang-pin Chen; Xiao-bin Zhang; Xin-bing Zhao (Journal of Zhejiang University-SCIENCE B, 2005)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)